Colloids with nanoporous structures and devices and systems for non-enzymatic glucose sensing - Patents.com

By using a non-enzymatic electrochemical sensor composed of colloids formed by aggregation of multiple nanoparticles, the problem of insufficient detection accuracy and stability in the prior art is solved, and a more efficient and reliable blood sugar detection is achieved.

JP7654760B2Active Publication Date: 2025-04-01UXN
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023195941
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-12-18
Filing Date
2023-11-17
Publication Date
2025-04-01
Estimated Expiration
2038-12-14

AI Technical Summary

Technical Problem

In the existing blood sugar sensing technology, electrochemical methods rely on enzyme-based electrochemical sensors, and there are problems of insufficient detection accuracy and stability.

Method used

Using a non-enzymatic electrochemical sensor consisting of colloids formed by aggregation of multiple nanoparticles, a nanopore layer with a three-dimensional network structure is formed by dispensing these colloids in the matrix and drying them.

Benefits of technology

It improves the accuracy and stability of blood sugar detection, reduces dependence on enzymes, and enhances the durability and anti-interference ability of the sensor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654760000001
    Figure 0007654760000001
  • Figure 0007654760000002
    Figure 0007654760000002
  • Figure 0007654760000003
    Figure 0007654760000003
Patent Text Reader

Abstract

To provide a device and system for sensing non-enzymatic glucose.SOLUTION: This disclosure relates to a colloid composition containing a number of clusters of nanoparticles dispersed in a liquid, a nanoporous layer formed of the colloid, a glucose-oxidation electrode including the nanoporous layer, and a glucose-sensing device, apparatus and system including the glucose-oxidation electrode. This disclosure also relates to a method of producing the colloid composition, nanoporous layer, glucose-oxidation electrode, and glucose-sensing device and system. Further, this disclosure also relates to devices, systems and methods for continuous glucose monitoring (CGM) and blood glucose monitoring (BGM).SELECTED DRAWING: Figure 5A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to glucose sensing. [Background technology]

[0002] There is a high level of interest in the healthcare community and industry to improve technology for sensing and monitoring blood glucose levels. Today, most glucose sensors use electrochemical methods. Most, if not all, electrochemical sensors use enzyme-based electrochemical sensors. Summary of the Invention

[0003] One embodiment of the invention provides a colloidal composition comprising many clusters of nanoparticles dispersed in a liquid, each cluster comprising many nanoparticles clustered together to form irregularly shaped bodies having nano-sized or micro-sized lengths, each nanoparticle having a separate body of roughly ovoid or spherical shape having a diameter of about 2 nm to about 5 nm, and interparticular gaps formed between adjacent nanoparticles inside each cluster, with an interparticular gap distance of about 0.5 nm to about 2 nm.

[0004] In the colloidal composition, the interparticle gaps may be distributed generally throughout each cluster. The composition may be substantially free of surfactant. The liquid may include water, and the colloidal composition may include surfactant in an amount less than 2 parts by weight per 100 parts by weight of nanoparticles contained therein. The nanoparticles contained in the colloidal composition may be in an amount of about 0.01 wt% to about 2 wt% based on the total weight of the colloidal composition. The nanoparticles contained in the colloidal composition may be in an amount of about 0.01 wt% to about 1 wt% based on the total weight of the colloidal composition.

[0005] In the above-mentioned colloidal composition, the nanoparticles may be mainly made of at least one selected from the group consisting of platinum (Pt), gold (Au), palladium (Pd), rhodium (Rh), titanium (Ti), ruthenium (Ru), tin (Sn), nickel (Ni), copper (Cu), indium (In), thallium (Tl), zirconium (Zr), iridium (Ir), and one or more oxides of each of the above-mentioned elements. The nanoparticles may be mainly made of platinum (Pt), the interparticle gaps may be distributed throughout each cluster, the colloidal composition may contain a surfactant in an amount of less than 1 part by weight per 100 parts by weight of nanoparticles contained therein, and the nanoparticles contained in the colloidal composition may be in an amount of about 0.1 wt% to about 1 wt% based on the total weight of the colloidal composition.

[0006] Another aspect of the invention provides a method of making a nanoporous layer, comprising dispensing a colloidal composition as described above onto a substrate; subjecting the dispensed colloidal composition to drying, such that clusters contained in the dispensed composition are deposited on the substrate and stacked on top of one another, providing a nanoporous layer on the substrate, the nanoporous layer comprising irregularly shaped bodies formed from the clusters stacked on top of one another, the irregularly shaped bodies comprising many nanoparticles clustered together locally and interparticle gaps formed between adjacent ones of the nanoparticles in the irregularly shaped bodies, the irregularly shaped bodies being interconnected to provide a three-dimensional interconnected network of the irregularly shaped bodies, and the irregularly shaped spaces formed between adjacent portions of the irregularly shaped bodies, which are nano-sized or micro-sized.

[0007] In the aforementioned method, the nanoparticles are generally ovoid or spherical with a diameter of about 2 nm to about 5 nm. The interparticle gaps may have an interparticle gap distance of about 0.5 nm to about 2 nm. The irregularly shaped spaces may be interconnected to provide a three-dimensional interconnected network of irregularly shaped spaces. The colloidal composition may be dispensed in a predetermined amount to form a nanoporous layer having a roughness factor of about 100 to about 2500. The nanoporous layer may include less than 0.5 parts by weight of a surfactant for 100 parts by weight of nanoparticles contained therein.

[0008] Another aspect of the invention provides a method of producing a colloidal composition, the method comprising: providing a liquid composition comprising metal ions, a surfactant and a solvent, the surfactant being in a reverse micelle phase defining a hydrophilic space; adding a reducing agent to the liquid composition to cause reduction of the metal ions, forming a first colloid comprising metal nanoparticles and the surfactant, in which the metal nanoparticles are dispersed with the reverse micelle phase of the surfactant; and removing the surfactant from the first colloid to provide a second colloid comprising many clusters dispersed in a liquid, each cluster comprising many nanoparticles clustered together to form irregularly shaped bodies having nano- or micro-sized lengths.

[0009] In the aforementioned manufacturing method, no electric potential may be applied to the liquid composition for reduction of the metal ions therein. The surfactant may be a non-ionic surfactant capable of forming an isotropic reverse micelle phase. The individual nanoparticles may have separate bodies of generally ovoid or spherical shape with a diameter of about 2 nm to about 5 nm, and interparticle gaps may be formed between adjacent nanoparticles inside each cluster and have an interparticle gap distance of about 0.5 nm to about 2 nm. Removing the surfactant removes a substantial amount of the surfactant from the first colloid, causing the second colloid to be substantially free of the surfactant. Removing the surfactant removes a substantial amount of the surfactant from the first colloid, causing the second colloid to contain less than 1 part by weight of the surfactant for 100 parts by weight of the nanoparticles contained therein.

[0010] In the above-mentioned manufacturing method, removing the surfactant may further include: centrifuging the first colloid; and collecting the bottom from the centrifuged composition. Removing the surfactant may further include repeating the series of centrifugation and collection multiple times. Removing the surfactant may further include adding an acid or base to the first colloid before centrifugation. Removing the surfactant may further include repeating the series of addition, centrifugation, and collection multiple times. The nanoparticles contained in the second colloid may be in an amount of about 10 wt% to about 40 wt% based on the total weight of the composition. The nanoparticles may be mainly made of at least one selected from the group consisting of platinum (Pt), gold (Au), palladium (Pd), rhodium (Rh), titanium (Ti), ruthenium (Ru), tin (Sn), nickel (Ni), copper (Cu), indium (In), thallium (Tl), zirconium (Zr), iridium (Ir), and one or more oxides of each of the aforementioned metals. The nanoparticles may be made primarily of platinum (Pt), the interparticle gaps may be distributed generally throughout each cluster, the composition may include a surfactant in an amount less than 2 parts by weight per 100 parts by weight of nanoparticles contained therein, and the nanoparticles contained in the composition may be in an amount of about 0.1 wt % to about 2 wt % based on the total weight of the composition.

[0011] Another aspect of the invention provides a method of producing a nanoporous layer, comprising the steps of: preparing a colloidal composition as described above to provide a second colloid; distributing the second colloid onto a substrate; and subjecting the distributed second colloid to drying such that clusters contained in the distributed composition are deposited on the substrate and stacked on top of each other to provide a nanoporous layer on the substrate, the nanoporous layer comprising irregularly shaped bodies formed from the clusters stacked on top of each other, the irregularly shaped bodies being comprised of many clustered together locally. and interparticle gaps formed between adjacent ones of the nanoparticles in the irregularly shaped bodies, the irregularly shaped bodies being interconnected to provide a three-dimensional interconnected network of the irregularly shaped bodies, and the irregularly shaped spaces being formed between adjacent portions of the irregularly shaped bodies and being nano-sized or micro-sized, and the irregularly shaped spaces being interconnected to provide a three-dimensional interconnected network of the irregularly shaped spaces.

[0012] In the aforementioned method of making a nanoporous layer, the nanoparticles may be generally ovoid or spherical in shape with a diameter of about 2 nm to about 5 nm, and the interparticle gaps have an interparticle gap distance of about 0.5 nm to about 2 nm. The colloidal composition may be dispensed in a predetermined amount to form a nanoporous layer having a roughness factor of about 100 to about 2500. The nanoporous layer may include less than 0.1 parts by weight of surfactant for 100 parts by weight of nanoparticles contained therein.

[0013] Another aspect of the invention provides a nanoporous structure comprising: irregularly shaped bodies including a number of nanoparticles clustered together locally and interparticle gaps formed between adjacent ones of the nanoparticles in the irregularly shaped bodies, where the nanoparticles can be generally ovoid or spherical in shape having a diameter of about 2 nm to about 5 nm, the interparticle gaps have an interparticle gap distance of about 0.5 nm to about 2 nm, and the irregularly shaped bodies can be interconnected to provide a three-dimensional interconnected network of the irregularly shaped bodies, the irregularly shaped spaces formed between adjacent portions of the irregularly shaped bodies and are nano-sized or micro-sized, and the irregularly shaped spaces are interconnected to provide a three-dimensional interconnected network of the irregularly shaped spaces.

[0014] The nanoporous structure may be substantially free of surfactant molecules. In the nanoporous structure, the interparticle gaps may be substantially free of nanosized organic molecules. The three-dimensional network of irregularly shaped bodies and the three-dimensional network of irregularly shaped intercluster gaps may be complementary, forming a nanoporous structure. The interparticle gaps may be substantially interconnected with themselves and may be further connected to the three-dimensional interconnected network of irregularly shaped intercluster gaps. The nanoporous structure may be formed by dispensing a solid-liquid colloid comprising irregularly shaped discrete clusters dispersed in a liquid and drying the dispensed solid-liquid colloid, the irregularly shaped discrete clusters may be stacked, providing a three-dimensional interconnected network of irregularly shaped bodies and a three-dimensional interconnected network of irregularly shaped intercluster gaps. The irregularly shaped intercluster gaps have an average intercluster gap distance. The nanoparticles may be made from at least one selected from the group consisting of platinum (Pt), gold (Au), palladium (Pd), rhodium (Rh), titanium (Ti), ruthenium (Ru), tin (Sn), nickel (Ni), copper (Cu), indium (In), thallium (Tl), zirconium (Zr), iridium (Ir), and one or more oxides of each of the aforementioned metals. The nanoporous structure has a roughness factor of about 100 to about 2500.

[0015] Another embodiment of the invention provides a device comprising: a substrate comprising a surface; and a nanoporous layer formed on the surface, the nanoporous layer comprising the nanoporous structure described above. Yet another embodiment of the invention provides a non-enzymatic glucose sensing electrode comprising at least one conductive layer comprising a surface; and a nanoporous layer formed on the surface, the nanoporous layer comprising the nanoporous structure described above, the non-enzymatic glucose sensing electrode being free of a glucose-specific enzyme.

[0016] In the aforementioned device or electrode, the at least one conductive layer may include a conductive metal layer and a conductive carbon layer formed on the conductive metal layer. The device or electrode does not include a biocompatible polymer material formed on the nanoporous layer. The device or electrode may include a biocompatible polymer material formed on the nanoporous layer.

[0017] Yet another aspect of the invention is a single-use glucose sensing device comprising: and an electrode as described above arranged with the reservoir such that the nanoporous layer can contact the test liquid when the test liquid can be held in the reservoir. In a single-use glucose sensing device, the electrode does not include a biocompatible polymeric material formed on the nanoporous layer.

[0018] Yet another embodiment of the invention provides a continuous glucose monitoring (CGM) device comprising: a hypodermic needle configured to contact interstitial fluid of a subject's body; and an electrical circuit connected to the hypodermic needle, wherein the hypodermic needle includes the aforementioned electrode and another electrode connected to the electrical circuit.

[0019] Yet another aspect of the invention provides a non-enzymatic glucose sensing device comprising a working electrode comprising a substrate and a nanoporous layer formed on the substrate, the working electrode does not comprise a glucose-specific enzyme, the nanoporous layer may comprise irregularly shaped bodies comprising many nanoparticles clustered together locally, interparticle gaps may be formed between adjacent ones of the nanoparticles in the irregularly shaped bodies, the nanoparticles may be generally ovoid or spherical in shape with a diameter of about 2 nm to about 5 nm, the interparticle gaps have an interparticle gap distance of about 0.5 nm to about 2 nm, and the irregularly shaped bodies are spaced apart from each other. to provide a three-dimensional interconnected network of irregularly shaped bodies extending generally throughout the nanoporous layer, the irregularly shaped spaces may be formed between adjacent portions of the irregularly shaped bodies and may be nano-sized or micro-sized, and the irregularly shaped spaces may be interconnected to provide a three-dimensional interconnected network of irregularly shaped spaces extending generally throughout the nanoporous layer, and the nanoporous layer may be configured to cause oxidation of glucose molecules therein in the absence of glucose-specific enzymes at a bias voltage applied thereto of about 0.2 V to about 0.45 V.

[0020] In the aforementioned non-enzymatic glucose sensing device, the nanoporous layer can be substantially free of surfactant molecules, and the substrate can include at least one conductive layer that includes a conductive or semiconductive material. The interparticle gaps can be substantially free of nanosized organic molecules. The three-dimensional network of irregularly shaped bodies and the three-dimensional network of irregularly shaped intercluster gaps can be complementary, forming a nanoporous layer. The interparticle gaps can be substantially interconnected with themselves and can be further connected to the three-dimensional interconnected network of irregularly shaped intercluster gaps.

[0021] In the non-enzymatic glucose sensing device as described above, further, the nanoporous layer may be formed by dispensing a solid-liquid colloid comprising discrete clusters of irregular shapes dispersed in a liquid and drying the dispensed solid-liquid colloid, and the discrete clusters of irregular shapes may be stacked to provide a three-dimensional interconnected network of irregularly shaped bodies and a three-dimensional interconnected network of gaps between the clusters of irregular shapes. The nanoparticles may be made from at least one selected from the group consisting of platinum (Pt), gold (Au), palladium (Pd), rhodium (Rh), titanium (Ti), ruthenium (Ru), tin (Sn), nickel (Ni), copper (Cu), indium (In), thallium (Tl), zirconium (Zr), iridium (Ir), and one or more oxides of each of the aforementioned metals. The nanoporous layer has a roughness factor of about 100 to about 2500. The nanoporous electrode may further include a maltose-blocking layer formed on the nanoporous layer and configured to substantially block the passage therethrough of maltose contained in the test fluid and allow the passage therethrough of glucose. The maltose-blocking layer may include poly-phenylenediamine (poly-PD) in a form that allows the passage therethrough of glucose molecules and effectively blocks the passage therethrough of maltose molecules. The bias voltage may be set to be in the range of 0.2V to 0.45V.

[0022] Yet another aspect of the invention provides a non-enzymatic glucose sensing system comprising: a counter electrode; and a bias voltage source electrically connected between the working electrode and the counter electrode for providing a bias voltage between the working electrode and the counter electrode.

[0023] Yet another aspect of the invention provides a method of non-enzymatic glucose sensing. The method includes: providing a non-enzymatic glucose sensing device as described above; applying a bias voltage between the working and counter electrodes while contacting a test fluid with both the working and counter electrodes, which causes oxidation of glucose contained in the test fluid at the nanoporous layer; measuring a current from the working electrode; and processing the current with or without additional data to provide a glucose level corresponding to the glucose contained in the test fluid. The bias voltage can be set to be in the range of 0.2V to 0.45V.

[0024] Another aspect of the invention provides a glucose sensing electrode, comprising: a substrate; a nanoporous metal layer formed on the substrate and capable of oxidizing both glucose and maltose in the glucose sensing electrode without glucose or maltose specific enzymes; and a maltose-blocking layer formed on the nanoporous metal layer. In the glucose sensing electrode, the maltose-blocking layer has a porosity that allows glucose to pass therethrough and blocks maltose from passing therethrough toward the nanoporous metal layer, such that when a bias voltage of 0.2-0.45 V is applied to the nanoporous metal layer relative to a reference electrode, and when the maltose-blocking layer is in contact with a liquid containing glucose at a concentration of 4-20 mM and maltose at a concentration of 4-20 mM, the current caused by the oxidation of only glucose in the nanoporous metal layer is 10 nA / mMcm. 2 The current induced by the oxidation of maltose alone in the nanoporous metal layer was 5 nA / mMcm 2 Lower.

[0025] In the glucose-sensing electrode described above, the nanoporous metal layer is capable of oxidizing glucose, so that the current caused by the oxidation of glucose alone is 10 nA / mMcm when a bias voltage of 0.2-0.45 V is applied and the electrode is in contact with a liquid containing glucose at a concentration of 4-20 mM without a maltose-blocking layer on top. 2The nanoporous metal layer can further oxidize maltose, so that the current caused by the oxidation of maltose alone is 10 nA / mMcm when it is in contact with a liquid containing maltose at a concentration of 4-20 mM and without a maltose-blocking layer on top, applying a bias voltage of 0.2-0.45 V. 2 higher. The maltose-blocking layer may include poly-phenylenediamine (poly-PD) and have a thickness of 10 to 40 nm. The maltose-blocking layer may consist essentially of poly-phenylenediamine (poly-PD) and have a thickness of 10 nm to 35 nm. The maltose-blocking layer may consist of poly-phenylenediamine (poly-PD) and have a thickness of 10 to 40 nm.

[0026] In the glucose sensing electrode described above, the nanoporous metal layer may include irregularly shaped bodies including many nanoparticles clustered together locally and interparticle gaps formed between adjacent ones of the nanoparticles in the irregularly shaped bodies, where the nanoparticles are generally ovoid or spherical in shape with a diameter of about 2 nm to about 5 nm. The interparticle gaps may have an interparticle gap distance of about 0.5 nm to about 2 nm. The irregularly shaped bodies may be interconnected to provide a three-dimensional interconnected network of the irregularly shaped bodies. The irregularly shaped spaces may be formed between adjacent portions of the irregularly shaped bodies and may be nano-sized or micro-sized. The irregularly shaped spaces may be interconnected to provide a three-dimensional interconnected network of the irregularly shaped spaces.

[0027] The glucose sensing electrode described above may further include an electrolyte ion-blocking layer formed on the maltose-blocking layer and a biocompatible layer formed on the electrolyte ion-blocking layer. The electrolyte ion-blocking layer is configured to block Na ions contained in the liquid. + , K + , Ca 2+ , Cl - , P.O. 4 3- and CO 3 2-from diffusing toward the nanoporous metal layer, so that Na is blocked between above and below the electrolyte ion-blocking layer. + , K + , Ca 2+ , Cl - , P.O. 4 3- and CO 3 2- There is a substantial discontinuity in the total concentration of . The electrolyte ion-blocking layer can facilitate conditioning of the glucose sensing electrode such that conditioning is completed within 30 minutes of contact with the subject's body fluid using an applied bias voltage of 0.2-0.45 V.

[0028] Another aspect of the invention provides an apparatus including a single integral body including a subcutaneous portion and a terminal portion; the subcutaneous portion including the aforementioned glucose sensing electrode and a reference electrode, each of which is exposed to contact with interstitial fluid of a first subject when the subcutaneous portion is subcutaneously inserted into the body of the first subject; and the terminal portion is configured to mate with a corresponding device and include a first terminal electrically connected to the glucose sensing electrode and a second terminal electrically connected to the reference electrode.

[0029] Yet another aspect of the invention provides a device including a single integral body including the glucose sensing electrode and reference electrode as described above, the single integral body further including a reservoir configured to at least temporarily hold a test fluid therein, the glucose sensing electrode and the reference electrode being arranged within the single integral body such that when the test fluid is held within the reservoir, each of the glucose sensing electrode and the reference electrode are configured to contact the test fluid.

[0030] A further aspect of the invention provides a method of making a glucose sensing electrode, the method comprising: providing a nanoporous metal layer capable of oxidizing both glucose and maltose without glucose or maltose specific enzymes in the glucose sensing electrode; forming a poly-phenylenediamine (poly-PD) film on a nanoporous platinum layer, the poly-PD film allowing glucose to pass therethrough and blocking maltose to pass therethrough, wherein the poly-PD film has a porosity that allows glucose to pass therethrough and blocks maltose to pass therethrough towards the nanoporous metal layer, such that when a bias voltage of 0.2-0.45 V is applied to the nanoporous metal layer relative to a reference electrode, and when the poly-PD film is in contact with a liquid containing glucose at a concentration of 4-20 mM and maltose at a concentration of 4-20 mM, the current caused by the oxidation of only glucose at the nanoporous metal layer is 10 nA / mMcm. 2 Moreover, the current induced by the oxidation of maltose alone in the nanoporous metal layer was 5 nA / mMcm 2 Lower.

[0031] In the aforementioned method of fabricating a glucose sensing electrode, forming the poly-PD film may include performing electrochemical polymerization using a nanoporous metal layer as an electrode for electrochemical polymerization. Forming the poly-PD film may include providing a polymer layer including poly-PD, and determining that the polymer layer does not have sufficient porosity to allow glucose to pass therethrough, such that the current caused by the oxidation of glucose alone at the nanoporous metal layer is less than 10 nA / mMcm. 2If the concentration is lower than the predetermined value, the forming of the poly-PD film may include adjusting the porosity of the polymer layer. The adjusting the porosity may include subjecting the polymer layer to at least one electric shock while the polymer layer is in contact with the acidic solution. The forming of the poly-PD film may include polymerizing poly-PD from a liquid composition including phenylenediamine at a concentration, and if the concentration is higher than the predetermined value, the forming of the poly-PD film may further include adjusting the porosity of the polymer layer. The adjusting the porosity may include subjecting the polymer layer to at least one electric shock while the polymer layer is in contact with the acidic solution.

[0032] In the above-mentioned method for fabricating a glucose sensing electrode, the formation of a poly-PD film is The polymer layer can have sufficient porosity to allow glucose to pass therethrough, such that the current caused by the oxidation of glucose alone in the nanoporous metal layer is greater than 10 nA / mMcm. 2 If the concentration is expected to be higher, the method may include providing a polymer layer comprising poly-PD without further adjusting the porosity of the polymer layer. Forming the poly-PD film may include polymerizing poly-PD from a liquid composition comprising phenylenediamine at a concentration, where if the concentration is lower than a predetermined value, the method does not include adjusting the porosity of the polymer layer to form the poly-PD film.

[0033] One embodiment of the invention provides a glucose sensing electrode, which includes: a conductive layer; a nanoporous metal layer formed on the conductive layer; an electrolyte ion-blocking layer formed on the nanoporous metal layer; and a biocompatible layer formed on the electrolyte ion-blocking layer. The glucose sensing electrode does not contain a glucose-specific enzyme. Glucose, Na + , K + , Ca 2+ , Cl - , P.O. 4 3 - and CO 3 2- When the electrolyte ion-blocking layer comes into contact with a liquid containing Na+ , K + , Ca 2+ , Cl - , P.O. 4 3- and CO 3 2- from diffusing toward the nanoporous metal layer, so that Na is blocked between above and below the electrolyte ion-blocking layer. + , K + , Ca 2+ , Cl - , P.O. 4 3 - and CO 3 2- There is a substantial discontinuity in the total concentration of

[0034] The glucose sensing electrode described above is biased at 0.2-0.45 V relative to the reference electrode. When a current is applied to it, the glucose sensing electrode detects the amount of glucose in the nanoporous metal layer. The glucose oxidation is caused only by glucose oxidation. The glucose sensing electrode is configured to generate a current that is the sum of a course-oxidation current and a background current caused by other electrochemical interactions between the liquid and the glucose sensing electrode. When course is included at a concentration of 4-20 mM (approximately 72-360 mg / dL), at steady state is the glucose oxidation current 、1 0nA / mMcm 2 Yo It is at a higher level.

[0035] In the glucose sensing electrode described above, the total concentration below the electrolyte ion-blocking layer is greater than 0% and less than about 10% of the total concentration above the electrolyte ion-blocking layer. The total concentration below the electrolyte ion-blocking layer is greater than 0% and less than about 5% of the total concentration above the electrolyte ion-blocking layer. The electrolyte ion-blocking layer prevents the passage of Na + , K + , Ca2+ , Cl - , P.O. 4 3 - and CO 3 2- The membrane may include a porous and hydrophobic polymer layer configured to restrict the mobility of the membrane but not the mobility of glucose molecules therethrough.

[0036] In the aforementioned glucose sensing electrode, the electrolyte ion-blocking layer may include at least one selected from the group consisting of poly(methyl methacrylate) (PMMA), poly(hydroxyethyl methacrylate) (PHEMA), and poly(methyl methacrylate-co-ethylene glycol dimethacrylate) (PMMA-EG-PMMA). The electrolyte ion-blocking layer may comprise at least one selected from the group consisting of copolymers of methyl methacrylate and butyl methacrylate, and polymers obtained from polymerization of one or more monomers including branched or unbranched C1-C8 alkyl methacrylates, branched or unbranched C1-C8 cycloalkyl methacrylates, branched or unbranched C1-C8 alkyl acrylates, branched or unbranched C1-C8 cycloalkyl acrylates, and branched or unbranched C1-C8 cycloalkyl methacrylates, wherein the one or more monomers are methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, pentyl methacrylate, hexyl methacrylate, cyclohexyl methacrylate, 2-ethylhexyl methacrylate, methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, pentyl acrylate, It is selected from the group consisting of hexyl acrylate, cyclohexyl acrylate, and 2-ethylhexyl acrylate.

[0037] In the glucose sensing electrode described above, the glucose sensing electrode may be a continuous glucose monitoring (CGM) electrode, and the liquid is a body fluid of the subject. The electrolyte ion-blocking layer is configured to facilitate conditioning of the glucose sensing electrode such that conditioning of the glucose sensing electrode is completed within 30 minutes of contact with the body fluid of the subject using application of a bias voltage of 0.2-0.45 V. Conditioning of the glucose sensing electrode may be considered complete when the rate of decrease of the current becomes less than a first predetermined value and / or when the current remains less than a second predetermined value.

[0038] The glucose-sensing electrode is inserted between a nanoporous metal layer and an electrolyte ion-blocking layer. The maltose-blocking layer may further comprise a maltose-blocking layer. The layer may include poly-phenylenediamine (poly-PD). Maltose-Blocking The layer allows glucose to pass through it and prevents maltose from passing through it. can be configured to substantially block glucose at steady state -Oxidation current is 、1 0nA / mMcm 2 Yo On the other hand, the oxidation of maltose is at a higher level. Maltose oxidation current induced by only is 5 nA / mMcm 2 Yo Very low.

[0039] The reference electrode can be configured to provide a reference level of potential for a bias voltage applied to the glucose sensing electrode, regardless of whether reduction of a chemical component occurs at the reference electrode. In a three-electrode electrochemical cell, in addition to the reference electrode, a counter electrode is provided for reduction of a chemical component therein, whereas in a two-electrode electrochemical cell, reduction of a chemical component occurs at the reference electrode.

[0040] In the glucose sensing electrode described above, the nanoporous metal layer can include irregularly shaped bodies including many nanoparticles clustered together locally and interparticle gaps formed between adjacent ones of the nanoparticles in the irregularly shaped bodies, where the nanoparticles are generally ovoid or spherical in shape with diameters of about 2 nm to about 5 nm, and the interparticle gaps have an interparticle gap distance of about 0.5 nm to about 2 nm. Wherein the irregularly shaped bodies can be interconnected to provide a three-dimensional interconnected network of the irregularly shaped bodies. The irregularly shaped spaces can be formed between adjacent portions of the irregularly shaped bodies and can be nano-sized or micro-sized, and the irregularly shaped spaces can be interconnected to provide a three-dimensional interconnected network of the irregularly shaped spaces.

[0041] Another aspect of the invention provides a sensor apparatus that includes: a single, integral body including a subcutaneous portion and a terminal portion; a subcutaneous portion including a glucose sensing electrode and a reference electrode, each of which is exposed to contact with interstitial fluid of a first subject when the subcutaneous portion is subcutaneously inserted into the body of the first subject; and a terminal portion configured to mate with a corresponding device and include a first terminal electrically connected to the glucose sensing electrode and a second terminal electrically connected to the reference electrode. The glucose sensing electrode may include one or more features of the glucose sensing electrodes described above.

[0042] Another aspect of the invention provides a method of continuous glucose monitoring, comprising: providing a sensor device; subcutaneously inserting a subcutaneous portion of a glucose sensing electrode into a body of a first subject such that the glucose sensing electrode and a reference electrode are in contact with interstitial fluid in the body of the first subject; applying a bias voltage of 0.2-0.45 V to the glucose sensing electrode relative to the reference electrode; measuring a current generated by the glucose sensing electrode; measuring the current within less than one hour after subcutaneous insertion of the subcutaneous portion and application of the bias voltage to calculate a glucose level using the resulting current value; and displaying on a display a glucose level of approximately 1.5 V. Presenting a calculated glucose level for the first analyte within the range of about 4 mM to about 20 mM (approximately about 72 mg / dL to about 360 mg / dL). The glucose sensing electrode may include one or more features of the glucose sensing electrodes described above.

[0043] A further aspect of the invention provides a sensor device that includes: a substrate; a first electrode (or glucose sensing electrode) including a first conductive layer formed on the substrate and a glucose-oxidation layer formed on the first conductive layer; a first terminal formed on the substrate and electrically connected to the first electrode; a second electrode including a second conductive layer formed on the substrate; a second terminal formed on the substrate and electrically connected to the second electrode; a reference electrode including a third conductive layer formed on the substrate; and a third terminal formed on the substrate and electrically connected to the reference electrode.

[0044] In the sensor device, when the first electrode is in contact with a liquid containing glucose, ascorbic acid, and acetaminophen, and when a first bias voltage is applied between the first electrode and the reference electrode sufficient to oxidize glucose in the glucose-oxidation layer, the glucose-oxidation layer of the first electrode is configured to cause oxidation of glucose and at least one of ascorbic acid and acetaminophen therein, and further configured to generate a first current including a glucose component caused by glucose oxidation and a first interference component caused by the oxidation of at least one of ascorbic acid and acetaminophen in the glucose-oxidation layer. The second electrode is arranged within the device such that when the first electrode is in contact with a liquid, the second electrode is also in contact with the same liquid. The second electrode does not include a layer configured to cause oxidation of glucose therein, such that upon application of a second bias voltage between the second electrode and the reference electrode, the second electrode is configured to cause oxidation of at least one of ascorbic acid and acetaminophen therein, but not oxidation of glucose therein, and is further configured to generate a second current at the second electrode that includes a second interfering component caused by the oxidation of at least one of ascorbic acid and acetaminophen and not caused by oxidation of glucose. The device is configured to provide a first current at the first terminal and a second current at the second terminal.

[0045] The sensor device as described above may be configured to provide a second current in association with the first current when providing the first current. The sensor device may be configured to generate the first current and the second current simultaneously. The sensor device may be configured to provide the first current and the second current together with information indicative of the time at which the first current and the second current were generated. The sensor device may be configured to provide the second current together with the first current whenever providing the first current. In the sensor device as described above, the first current may further include a first background current caused by other electrochemical interactions of the liquid with the glucose sensing layer, and the second current may further include a second background current caused by other electrochemical interactions of the liquid with the second electrode.

[0046] In the above-mentioned sensor device, when the first bias voltage is 0.2V to 0.32V, the glucose-oxidation layer is configured to oxidize glucose and ascorbic acid but not acetaminophen, and the first interference component is caused by the oxidation of ascorbic acid, not by the oxidation of acetaminophen. When the second bias voltage is 0.2V to 0.32V, the second electrode is configured to oxidize ascorbic acid but not acetaminophen, and the second interference component is caused by the oxidation of ascorbic acid, not by the oxidation of acetaminophen. In the above-mentioned sensor device, when the first bias voltage is 0.34V to 0.45V, the glucose-oxidation layer is configured to oxidize glucose, ascorbic acid, and acetaminophen, and the first interference component is caused by the oxidation of ascorbic acid and acetaminophen. When the second bias voltage is 0.34V to 0.45V, the second electrode is configured to oxidize ascorbic acid and acetaminophen. The interfering component is configured to oxidize acetaminophen, and the second interfering component is caused by the oxidation of both ascorbic acid and acetaminophen.

[0047] In the above-mentioned sensor device, the first electrode is a poly- A maltose-blocking layer containing phenylenediamine (poly-PD) may be further included. A liquid containing glucose having a concentration of 4-20 mM (approximately 72-360 mg / dL) When contacted with maltose and a bias voltage is applied, the maltose-blocking layer becomes allowing the course to pass therethrough and substantially preventing maltose from passing therethrough The ATP-dependent ATPases are configured to block glucose oxidation currents at steady state. 、1 0nA / mMcm 2 Yo The maltose oxidation current induced by the oxidation of maltose alone was at a higher level than that of the control. is 5 nA / mMcm 2 Yo Very low.

[0048] The sensor device may be a continuous glucose monitoring (CGM) electrode module including a subcutaneous portion configured to subcutaneously contact a body fluid of a subject, and the first, second and reference electrodes are formed within the subcutaneous portion. In the sensor device, the glucose-oxidation layer may include a nanoporous metal layer, and the first electrode may further include: an electrolyte ion-blocking layer formed on the nanoporous metal layer and a biocompatible layer formed on the electrolyte ion-blocking layer. The electrolyte ion-blocking layer is configured to block Na ions contained in the fluid. + , K + , Ca 2+ , Cl - , P.O. 4 3 - and CO 3 2- from diffusing toward the nanoporous metal layer, so that Na + , K + , Ca 2+ , Cl - , P.O. 4 3 - and CO 3 2-There is a substantial discontinuity in the total concentration of

[0049] In the above-mentioned sensor device, the electrolyte ion-blocking layer is formed to prevent the passage of Na + , K + , Ca 2+ , Cl - , P.O. 4 3 - and CO 3 2- The electrolyte ion-blocking layer may comprise a porous and hydrophobic polymer layer configured to restrict the mobility of electrolyte ions but not the mobility of glucose molecules therethrough, and the electrolyte ion-blocking layer may comprise at least one selected from the group consisting of poly(methyl methacrylate) (PMMA), poly(hydroxyethyl methacrylate) (PHEMA), and poly(methyl methacrylate-co-ethylene glycol dimethacrylate) (PMMA-EG-PMMA).

[0050] In the above-described sensor device, the electrolyte ion-blocking layer may be configured to facilitate conditioning of the glucose sensing electrode such that conditioning is completed within 30 minutes of contact with the subject's body fluid using application of a bias voltage of 0.2-0.45 V, and conditioning of the glucose sensing electrode is considered complete when the rate of decrease in current becomes less than a first predetermined value and / or when the current remains less than a second predetermined value.

[0051] The aforementioned sensor device is a blood glucose monitoring (BGM) electrode module including a reservoir configured to receive blood, where the first electrode, the second electrode and the reference electrode are configured to contact the blood when the blood is received in the reservoir. The first bias voltage is between 0.2V and 0.45V, and the second bias voltage is the same as or different from the first bias voltage. The glucose-oxidation layer may include a nanoporous metal material or a glucose-specific enzyme configured to oxidize glucose. The glucose-oxidation layer may include irregularly shaped bodies including many nanoparticles locally clustered together and interparticle gaps formed between adjacent ones of the nanoparticles in the irregularly shaped bodies, the nanoparticles being generally ovoid or spherical in shape with a diameter of between about 2 nm and about 5 nm, and the interparticle gaps having an interparticle gap distance of between about 0.5 nm and about 2 nm. Wherein the irregularly shaped bodies may be interconnected to provide a three-dimensional interconnected network of the irregularly shaped bodies. The irregularly shaped bodies may include a nanoporous metal material or a glucose-specific enzyme configured to oxidize glucose. The glucose-oxidation layer may include irregularly shaped bodies including many nanoparticles locally clustered together and interparticle gaps formed between adjacent ones of the nanoparticles in the irregularly shaped bodies, the nanoparticles being generally ovoid or spherical in shape with a diameter of between about 2 nm and about 5 nm, and the interparticle gaps having an interparticle gap distance of between about 0.5 nm and about 2 nm. Wherein the irregularly shaped bodies may be interconnected to provide a three-dimensional interconnected network of the irregularly shaped bodies. Gaps can be formed between adjacent portions of the irregularly shaped bodies, and can be nano- or micro-sized, and the irregularly shaped spaces are interconnected to provide a three-dimensional interconnected network of irregularly shaped spaces.

[0052] Yet another aspect of the invention provides a system including the aforementioned sensor device further including a terminal section with a first, second and third terminal arranged thereon; a corresponding device including a first corresponding terminal, a second corresponding terminal, a third corresponding terminal, a circuitry, and a power connected to the circuitry, the corresponding device further including a corresponding terminal section configured to couple or engage with the terminal section, wherein the first, second and third corresponding terminals are arranged within the corresponding terminal section such that when the terminal section of the sensor device and the corresponding terminal section of the corresponding device are coupled or engaged, the first terminal electrically connects to the first corresponding terminal, the second terminal electrically connects to the second corresponding terminal, and the third terminal electrically connects to the third corresponding terminal. The corresponding device circuitry is configured to provide a first bias voltage between the first and third corresponding terminals, and the corresponding device circuitry is further configured to provide a second bias voltage between the second and third corresponding terminals.

[0053] In the aforementioned system, the corresponding device may include a wireless communication module configured to wirelessly communicate with a wirelessly paired computing device, the wireless communication module including at least one processor and at least one memory. The corresponding device may be configured to receive a first current at a first corresponding terminal and a second current at a second corresponding terminal. The corresponding device may be configured to transmit a second current together or in association with the first current when transmitting the first current. The first current may be transmitted with a first timestamp and the second current may be transmitted with a second timestamp, the first and second timestamps indicating the same time.

[0054] The above-mentioned system may further include software installed and executable by at least one processor of the wirelessly paired computing device, the software being configured, when executed, to perform a method including: storing, in at least one memory of the computing device, a first current and a second current received together or in association with each other from a corresponding device; processing the first current and the second current to provide a value indicative of glucose oxidation in a glucose-oxidation layer of a first electrode of the sensor device; and presenting the value or corresponding information on a display of the computing device.

[0055] In the above system, either or both of the first current and the second current may be in the form of a continuous signal, and processing the first current and the second current may include processing values ​​of the first current and the second current obtained simultaneously. Here, processing the values ​​may include subtracting the second current from the first current. The first current and the second current may be stored in association with each other in at least one memory. The above system may further include software installed and executable on the wirelessly paired computing device. When executed, the software is configured to perform data processing using the first current and the second current received from the corresponding device to obtain a level of glucose contained in a liquid contacted by the first electrode of the sensor device. Here, the software requires the second current when processing to obtain a level of glucose.

[0056] In the above system, the corresponding device may further include at least one processor, at least one memory, and software stored in the at least one memory and executable by the at least one processor, where when executed, the software is configured to perform a method including: causing at least one memory to store a first current and a second current received together or in association with each other from the sensor device; and processing the first current and the second current to provide a value indicative of the oxidation of glucose in the glucose-oxidation layer of the first electrode of the sensor device, where the processing may include subtracting the second current from the first current. Either or both of the first current and the second current may be in the form of a continuous signal, and processing the first current and the second current may include processing values ​​of the first current and the second current obtained simultaneously. The compatible device may further include a display, and the method may further include causing the value or its corresponding information to be presented on the display. The compatible device may further include a wireless communication module configured to wirelessly pair with the device including the display, and the method may further include communicating the data to the wirelessly paired device for presenting the value or its corresponding information on a display of the wirelessly paired device.

[0057] Yet another embodiment of the invention provides a method of electrochemical sensing, the method including: providing a sensor device including a first electrode including a glucose-oxidation layer capable of oxidizing glucose, a second electrode not including a layer capable of oxidizing glucose, and a reference electrode; contacting the first electrode, the second electrode, and the reference electrode with a liquid including glucose, ascorbic acid, and acetaminophen; applying a first bias voltage between the first electrode and the reference electrode sufficient to oxidize glucose at the glucose-oxidation layer, such that glucose and at least one of ascorbic acid and acetaminophen are oxidized at the glucose-oxidation layer; and causing a first current to be generated from the first electrode, the first current being a glucose component caused by glucose oxidation. and a first interfering component caused by oxidation of at least one of ascorbic acid and acetaminophen; applying a second bias voltage between the second electrode and the reference electrode, such that at least one of ascorbic acid and acetaminophen is oxidized at the second electrode, but glucose is not oxidized therein, and causing a second current to be generated from the second electrode, the second current including a second interfering component caused by oxidation of at least one of ascorbic acid and acetaminophen at the second electrode; and providing a first current and a second current for processing, the first current being provided for processing and the second current also being provided in association with the first current.

[0058] In the aforementioned method, the first current and the second current can be generated simultaneously or one after the other within a reasonable period of time during which the glucose level does not change substantially or beyond a predetermined acceptable level. The first current can be provided along with information indicating the time of occurrence of the first current, and the second current can be provided along with information indicating the time of occurrence of the second current. The second current can be provided along with the first current whenever the first current is provided. In the aforementioned method, the first bias voltage is applied between 0.2V and 0.32V, whereby the glucose-oxidation layer oxidizes glucose and ascorbic acid but does not oxidize acetaminophen, in which case the first interfering component is caused by oxidation of ascorbic acid and not by oxidation of acetaminophen; the second bias voltage is applied between 0.2V and 0.32V, whereby the second electrode oxidizes ascorbic acid but does not oxidize acetaminophen, in which case the second interfering component is caused by oxidation of ascorbic acid and not by oxidation of acetaminophen. In another case, a first bias voltage is applied between 0.34V and 0.45V, causing the glucose-oxidation layer to oxidize glucose, ascorbic acid, and acetaminophen, in which case the first interfering component is caused by the oxidation of ascorbic acid and acetaminophen; a second bias voltage is applied between 0.34V and 0.45V, causing the second electrode to oxidize ascorbic acid and acetaminophen, in which case the second interfering component is caused by the oxidation of both ascorbic acid and acetaminophen.

[0059] In the aforementioned method, the sensor device may further include a maltose-blocking layer formed on the glucose-oxidation layer and including poly-phenylenediamine (poly-PD). The sensor device may be a continuous glucose monitoring (CGM) electrode module including a subcutaneous portion configured to subcutaneously contact a body fluid of the subject, the first, second and reference electrodes being formed within the subcutaneous portion, and contacting the first electrode, the second electrode and the reference electrode with the fluid may include subcutaneously inserting the subcutaneous portion into the body of the subject. The glucose-oxidation layer may include a nanoporous metal layer, and the first electrode may further include: an electrolyte ion-blocking layer formed on the nanoporous metal layer and a biocompatible layer formed on the electrolyte ion-blocking layer. The electrolyte ion-blocking layer may be configured to block Na2+ contained in the fluid. + , K + , Ca 2+ , Cl - , P.O. 4 3 - and CO 3 2- from diffusing toward the nanoporous metal layer, so that Na + , K + , Ca 2+ , Cl - , P.O. 4 3 - and CO 3 2- There is a substantial discontinuity in the total concentration of

[0060] In the aforementioned method, the sensor device is a blood glucose monitoring (BGM) electrode module including a reservoir, and contacting the first electrode, the second electrode, and the reference electrode with a liquid may include providing a blood sample into the reservoir. The glucose-oxidation layer may include irregularly shaped bodies including many nanoparticles clustered together locally and interparticle gaps formed between adjacent ones of the nanoparticles in the irregularly shaped bodies, the nanoparticles being generally ovoid or spherical in shape with a diameter of about 2 nm to about 5 nm, and the interparticle gaps having an interparticle gap distance of about 0.5 nm to about 2 nm. The irregularly shaped bodies may be interconnected to provide a three-dimensional interconnected network of the irregularly shaped bodies. The irregularly shaped spaces may be formed between adjacent portions of the irregularly shaped bodies and may be nano-sized or micro-sized, and the irregularly shaped spaces may be interconnected to provide a three-dimensional interconnected network of the irregularly shaped spaces.

[0061] In the above method, the sensor device may further include a first terminal electrically connected to the first electrode, a second terminal electrically connected to the second electrode, and a third terminal electrically connected to the reference electrode. The sensor device may further include a terminal section in which the first, second, and third terminals are arranged, and applying the first bias voltage and the second bias voltage may include coupling with a corresponding device including a first corresponding terminal, a second corresponding terminal, a third corresponding terminal, a circuit network, and a power connected to the circuit network. The corresponding device may further include a corresponding terminal section for coupling or engaging with the terminal section of the sensor device. The first, second, and third corresponding terminals may be arranged in the corresponding terminal section such that when the terminal section of the sensor device and the corresponding terminal section of the corresponding device are coupled or engaged, the first terminal electrically connects to the first corresponding terminal, the second terminal electrically connects to the second corresponding terminal, and the third terminal electrically connects to the third corresponding terminal. The compliant device circuitry can provide a first bias voltage between the first compliant terminal and the third compliant terminal; the compliant device circuitry can provide a second bias voltage between the second compliant terminal and the third compliant terminal.

[0062] Yet another aspect of the invention provides a method of providing or determining a glucose level, the method including: providing software stored in at least one memory and executable by at least one processor provided with the sensor device or another device; executing the software with the at least one processor to process the first current and the second current to provide a value indicative of the oxidation of glucose at a glucose-oxidation layer of a first electrode of the sensor device; and causing the value or corresponding information to be presented on a display provided with the sensor device, the other device, or yet another device.

[0063] In the above method, the at least one memory and the at least one processor are provided in another device. The method may further include: to another device; and storing, prior to execution, in at least one memory the first current and the second current received together or in association with each other. In the aforementioned method, the first current is communicated with a first time stamp and the second current is communicated with a second time stamp, the first and second time stamps indicating the same time. In the aforementioned method, either or both of the first current and the second current may be in the form of a continuous signal, and processing the first current and the second current may include processing values ​​of the first current and the second current obtained simultaneously. In the aforementioned method, the processing may include subtracting the second current from the first current.

[0064] Yet another embodiment of the invention provides a sensor device comprising: a working electrode comprising a nanoporous metal layer; and a reference electrode; and a bias voltage applied between the working electrode and the reference electrode, where no glucose-specific enzyme is present at the working electrode.

[0065] In the sensor device, the nanoporous metal layer includes irregularly shaped bodies including many nanoparticles clustered together locally and interparticle gaps formed between adjacent ones of the nanoparticles in the irregularly shaped bodies, the nanoparticles being generally ovoid or spherical with diameters of about 2 nm to about 5 nm, and the interparticle gaps having an interparticle gap distance of about 0.5 nm to about 2 nm. The irregularly shaped bodies can be interconnected to provide a three-dimensional interconnected network of the irregularly shaped bodies. The irregularly shaped spaces are formed between adjacent portions of the irregularly shaped bodies and are nano-sized or micro-sized, and the irregularly shaped spaces are interconnected to provide a three-dimensional interconnected network of the irregularly shaped spaces. In the sensor device, the bias voltage is set to be sufficient to cause oxidation of glucose in the nanoporous metal layer but not sufficient to cause oxidation of acetaminophen in the nanoporous metal layer, and the bias voltage is set within a range of about 0.20 V to about 0.32 V.

[0066] The sensor device may include a continuous glucose monitoring (CGM) electrode module including a subcutaneous portion configured to subcutaneously contact a body fluid of a subject, and a working electrode and a reference electrode are formed within the subcutaneous portion. The working electrode may further include: an electrolyte ion-blocking layer formed on the nanoporous metal layer; and a biocompatible layer formed on the electrolyte ion-blocking layer. The electrolyte ion-blocking layer is configured to block Na ions contained in the fluid. + , K + , Ca 2+ , Cl - , P.O. 4 3 - and CO 3 2- from diffusing toward the nanoporous metal layer, so that Na + , K + , Ca 2+ , Cl - , P.O. 4 3 - and CO 3 2-There is a substantial discontinuity in the aggregate concentration of . The electrolyte ion-blocking layer can be configured to facilitate conditioning of the working electrode such that conditioning of the working electrode is completed within 30 minutes of contact with the subject's body fluid with application of a bias voltage.

[0067] The aforementioned sensor device includes poly-phenylenediamine (Poly-PD) and nanoporous gold. The electrolyte ion blocking layer may further include a maltose-blocking layer interposed between the electrolyte layer and the electrolyte ion-blocking layer. When the maltose-containing liquid is contacted with the maltose-containing liquid and a bias voltage is applied, The glucose-blocking layer is configured to allow glucose to pass therethrough and to substantially block maltose from passing therethrough, such that at steady state, the glucose-oxidation current is 、1 0nA / mMcm 2 Yo The maltose oxidation current induced by the oxidation of maltose alone was at a higher level than that of the control. is 5 nA / mMcm 2 Yo Very low.

[0068] Yet another aspect of the invention provides a method of glucose sensing, the method comprising: providing one of the aforementioned sensor devices; and a working electrode (or a glucose sensing A bias voltage in the range of about 0.20 V to about 0.32 V is applied between the test electrode and the reference electrode. Here, the application of a bias voltage induces the oxidation of glucose in the nanoporous metal layer. Therefore, the glucose-oxidation current caused by glucose oxidation alone is 1 0nA / mMcm 2 YoThe acetaminophen oxidation current caused by the acetaminophen oxidation in the nanoporous metal layer was at a higher level than that of the control, whereas the application of a bias voltage did not cause sufficient oxidation of acetaminophen in the nanoporous metal layer. is 5 nA / mMcm 2 Yo Very low.

[0069] The patent or application file contains drawings executed in color. Copies of this patent or patent application publication with color drawing(s) will be provided by the Office upon request and payment of the necessary fee. [Brief description of the drawings]

[0070] [Figure 1] 1 illustrates a conceptual electrochemical glucose sensing system according to an embodiment of the invention. [Diagram 2] 1 illustrates a working electrode for an enzymatic glucose sensing system according to one embodiment. [Diagram 3] 1 shows a working electrode including a nanoporous layer for a non-enzymatic sensing system according to one embodiment. [Figure 4] The top surface and depth of the nanoporous layer are shown. [Figure 5A] 1 illustrates a clustered morphology of a nanoporous layer according to one embodiment. [Figure 5B] 1 is a TEM photographic image of a cluster according to one embodiment. [Figure 5C] FIG. 5C is a zoomed-in image of the TEM photograph of FIG. 5B. [Figure 5D] 1 is a SEM photographic image of a nanoporous layer taken from its top surface, according to one embodiment. [Figure 6A] 1 is a flow chart for fabricating a clustered nanoporous layer according to one embodiment. [Figure 6B] 4 is a flow chart for fabricating a clustered nanoporous layer according to another embodiment. [Figure 7] 1 is an example phase diagram of a surfactant showing different phases. [Figure 8]1 illustrates a reverse micelle phase and a nanoparticle-surfactant colloid according to one embodiment. [Figure 9] 1 includes a TEM photographic image of nanoparticle clusters according to one embodiment. [Figure 10A] 1 illustrates a non-clustered morphology of a nanoporous layer according to one embodiment. [Figure 10B] 1 is a TEM photographic image of a non-clustered morphology of a nanoporous layer formed on a metal surface according to one embodiment. [Figure 11] 1 is a flow chart for producing a non-clustered nanoporous layer according to one embodiment. [Figure 12] 1 is a flow chart for fabricating hexagonal nanostructures according to one embodiment. [Figure 13A] 1 illustrates the formation of a hexagonal array according to one embodiment. [Figure 13B] 1 shows the deposition of metals using hexagonal ordering of liquid crystal phases. [Figure 14] 1 shows particle size distributions for nanoparticle-surfactant colloids prepared according to one embodiment. [Figure 15] 1 shows particle size distributions for cluster colloids prepared according to one embodiment. [Figure 16A] 1A-1D show cross sections of electrode-based and non-enzymatic glucose-sensing working electrodes, respectively, according to embodiments. [Figure 16B] 1A-1D show cross sections of electrode-based and non-enzymatic glucose-sensing working electrodes, respectively, according to embodiments. [Figure 17A] 1 is a SEM photograph of a glucose-sensing working electrode according to an embodiment. [Figure 17B] 1 is a SEM photograph of a glucose-sensing working electrode according to an embodiment. [Figure 17C] 1 is a SEM photograph of a glucose-sensing working electrode according to an embodiment. [Figure 18] 11 is a profile of current generated by oxidation of glucose and other materials in PBS according to an embodiment. [Figure 19]1 is a profile of current generated by oxidation of glucose and other materials in human serum according to an embodiment. [Figure 20] This is the structural formula of a maltose molecule. [Figure 21] 1 shows a non-enzymatic working electrode including a maltose-blocking layer according to one embodiment. [Figure 22] 1 shows a scan of oxidation potential during cyclic voltammetric electrochemical polymerization of phenylenediamine according to an embodiment. [Figure 23] 1 shows a chronoamperometry setup for electric shock treatment to adjust the porosity of a porous polymer layer according to one embodiment. [Figure 24] 1 is a flow chart for producing a maltose-blocking layer according to one embodiment. [Diagram 25] 1 shows the current monitored with a glucose sensing electrode having a maltose-blocking layer according to an embodiment, where the current signal is presented in color since it is not easily discernible in black and white. [Figure 26] 1 shows the current monitored with a glucose sensing electrode having a maltose-blocking layer according to an embodiment, where the current signal is presented in color since it is not easily discernible in black and white. [Figure 27] 1 shows the current monitored with a glucose sensing electrode having a maltose-blocking layer according to an embodiment, where the current signal is presented in color since it is not easily discernible in black and white. [Figure 28] 1 shows the current monitored with a glucose sensing electrode having a maltose-blocking layer according to an embodiment, where the current signal is presented in color since it is not easily discernible in black and white. [Figure 29] 1 shows the current monitored with a glucose sensing electrode having a maltose-blocking layer according to an embodiment, where the current signal is presented in color since it is not easily discernible in black and white. [Diagram 30]1 shows the current monitored with a glucose sensing electrode having a maltose-blocking layer according to an embodiment, where the current signal is presented in color since it is not easily discernible in black and white. [Diagram 31] 1 illustrates a CGM working electrode according to one embodiment. [Diagram 32] 1 illustrates an electrolyte concentration drop across the thickness of an electrolyte ion-blocking layer according to one embodiment. [Diagram 33] 1 illustrates a CGM electrode unit according to one embodiment. [Diagram 34] 1 is a flow chart for fabricating a CGM electrode unit according to one embodiment. [Diagram 35] 35 shows top and cross-sectional views of intermediate products at various stages in fabricating the CGM electrode of FIG. 33, where each cross-section is taken about line 3501 and looking in the direction of the arrows. [Diagram 36] 35 shows top and cross-sectional views of intermediate products at various stages in fabricating the CGM electrode of FIG. 33, where each cross-section is taken about line 3501 and looking in the direction of the arrows. [Figure 37] 35 shows top and cross-sectional views of intermediate products at various stages in fabricating the CGM electrode of FIG. 33, where each cross-section is taken about line 3501 and looking in the direction of the arrows. [Figure 38A] 1A and 1B show cross sections of a CGM working electrode having an intermediate product and a functional layer after formation of a nanoporous layer according to an embodiment, respectively. [Figure 38B] 1A and 1B show cross sections of a CGM working electrode having an intermediate product and a functional layer after formation of a nanoporous layer according to an embodiment, respectively. [Figure 39] 1 illustrates a disposable glucose sensing cartridge according to an embodiment. [Diagram 40] 1 illustrates a two-electrode glucose sensing system according to one embodiment. [Diagram 41] 1 illustrates a CGM electrode unit for a two-electrode glucose sensing system according to one embodiment. [Figure 42A]1 is a profile of current generated by the oxidation of glucose according to one embodiment, where the working electrode does not include an electrolyte ion-blocking layer. [Figure 42B] FIG. 42B is an enlarged view of a portion of the profile of FIG. 42A. [Diagram 43] 1 is a profile of current generated by the oxidation of glucose according to one embodiment, where the working electrode includes an electrolyte ion-blocking layer. [Diagram 44] 1 is a comparison of the time to condition a working electrode with and without an electrolyte ion-blocking layer. [Figure 45A] 1 is a photograph of a potentiostat according to one embodiment. [Figure 45B] 1 is a photograph of a potentiostat according to one embodiment. [Figure 45C] 1 is a photograph of a potentiostat according to one embodiment. [Diagram 46] 13 is a graph showing CGM monitoring of glucose levels in a rat using a non-enzymatic CGM electrode module according to one embodiment. [Figure 47] 1 is a Clarke Error Grid for a non-enzymatic CGM electrode module according to one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0071] The presently disclosed subject matter will now be described in more detail with reference to the accompanying drawings in terms of several specific embodiments and examples. Some, but not all, of the embodiments of the invention are shown herein. Like numerals refer to like elements or parts throughout. The presently disclosed subject matter may be embodied in many different forms, and should not be construed as limited to the specific embodiments set forth herein. Rather, these embodiments are provided so that this disclosure will satisfy applicable legal requirements. Indeed, many modifications and other embodiments of the presently disclosed subject matter will occur to those skilled in the art to which the presently disclosed subject matter pertains. Therefore, it is to be understood that the presently disclosed subject matter is not limited to the specific embodiments disclosed, and that modifications and other embodiments are intended to be included within the scope of the appended claims.

[0072] Electrochemical glucose sensing system Electrochemical glucose detection Electrochemical glucose sensing measures the concentration of glucose in an electrolyte solution. FIG. 1 conceptually illustrates an electrochemical glucose sensing system 101 for detecting the concentration of glucose in a test fluid or electrolyte solution 102. The system 101 includes a working or sensing electrode 103, a counter electrode 105, and a reference electrode 106, which are connected to a potentiostat 104 and are in contact with the test fluid 102. In an embodiment, the potentiostat includes electrical circuitry for functioning as a voltage source 109 and a current sensor 108. The voltage source 109 provides a bias voltage that drives the redox reaction at the working electrode 103 and the counter electrode 105. The potentiostat further includes electrical circuitry, such as an operational amplifier 107, for maintaining a bias voltage at the working electrode 103 relative to the reference electrode 106. The current sensor 108 detects a current generated by a redox reaction involving glucose contained in the test fluid 102.

[0073] Enzymatic glucose sensing electrode Most, if not all, electrochemical glucose sensing systems utilize glucose-specific enzymes for the detection of glucose molecules. FIG. 2 shows a working electrode 103E for an enzymatic glucose sensing system, i.e., an enzymatic glucose sensing electrode. The terms "glucose sensing electrode" and "working electrode" are used interchangeably in this disclosure. Enzymatic Working Electrode 103E includes a conductive layer 110 and an enzyme layer 111. Optionally, the enzyme working electrode 103E may include at least one functional layer 112 on the enzyme layer 111, as in FIG. 2. Alternatively, although not shown, at least one functional layer may be disposed between the enzyme layer 111 and the conductive layer 110. The enzyme layer 111 includes glucose-specific enzyme molecules 115, which are held therein by fixtures 113. When a glucose molecule comes into contact with the glucose-specific enzyme, the enzyme catalyzes the oxidation of glucose to gluconolactone. Electrons from glucose oxidation are ultimately transferred to the conductive layer 110, generating a current in the electrical circuit of the electrochemical sensing system 101.

[0074] Glucose oxidase In some enzymatic glucose sensing systems, the enzymatic working electrode 103E contains glucose oxidase (GOx). The glucose oxidase 115 transfers electrons to molecular oxygen that remains near the enzyme, which is reduced to hydrogen peroxide. When the proper bias voltage is applied in the system, the conductive layer 110 oxidizes the hydrogen peroxide and extracts electrons from it, thereby generating a current that is indicative of the glucose concentration in the test fluid 102.

[0075] Glucose dehydrogenase In other enzymatic glucose sensing systems, the enzymatic working electrode 103E includes glucose dehydrogenase (GDH). Unlike glucose oxidase, glucose dehydrogenase does not use oxygen, but instead transfers electrons to another adjacent chemical moiety called an electron mediator, which then transfers electrons from glucose oxidation to the conductive layer 110. The electron mediator can be included in the enzyme layer 111. Alternatively, the electron mediator can be provided in a separate layer (not shown) between the enzyme layer 111 and the conductive layer 110. Although glucose dehydrogenase has some advantages of sensitivity over glucose oxidase, the enzyme oxidizes maltose as well as glucose, which prevents accurate sensing of glucose concentration.

[0076] Non-enzymatic glucose sensing electrodes A non-enzymatic electrochemical glucose sensing system does not use a glucose-specific enzyme or any enzyme to detect glucose. Instead, a non-enzymatic glucose sensing system has a non-enzymatic working electrode that detects glucose without a glucose-specific enzyme. In an embodiment, the non-enzymatic working electrode includes at least one glucose oxidation layer that allows oxidation of glucose molecules at a moderate level of bias voltage. In general, the higher the bias voltage, the more likely glucose oxidation will occur at the at least one glucose oxidation layer. However, there is a limit to the bias voltage because at high bias voltages, other chemical components are also oxidized. Thus, non-enzymatic electrochemical glucose sensing relies on materials that oxidize glucose at bias voltages that do not cause oxidation of other chemical components contained in the test fluid.

[0077] Nanoporous layers for nonenzymatic glucose sensing electrodes 3 shows a non-enzymatic working electrode (simply "working electrode") 103NE comprising a conductive layer 110 and a nanoporous glucose oxidation layer (or nanoporous layer) 117. In an embodiment, the nanoporous layer 117 comprises a nanoporous interior structure to cause, enable or promote oxidation of glucose at a moderate bias voltage. When glucose oxidation occurs, the conductive layer 110 extracts electrons from the glucose oxidation and a current is generated in an electrical circuit. The current can be detected by a current sensor 108 and can be interpreted by the system hardware and software. Optionally, the working electrode 103NE can include at least one functional layer 112 on the nanoporous layer 117 or between the nanoporous layer 117 and the conductive layer 110 (not shown).

[0078] Conductive Layer - Material With a bias voltage, the conductive layer 110 of Figures 2 and 3 extracts electrons from the glucose oxidation and transfers them to the current sensor 108. In an embodiment, the conductive layer 110 includes or is fabricated from at least one conductive material and is connected to the electrical circuitry of the system 101. In some embodiments, assuming a small-scale conductive layer 110, a semiconductive material may be used instead of a conductive material. Non-limiting examples of conductive layer materials include platinum (Pt), gold (Au), silver (Ag), ruthenium (Ru), stainless steel, silicon (amorphous, polycrystalline and single crystal), conductive carbon materials such as graphite, graphene, fluorene, carbon nanotubes. In an embodiment, the conductive layer 110 does not include the nanoporous inner structure of the glucose oxidation layer 117.

[0079] Conductive layer-structure In embodiments, the conductive layer 110 may be formed from a single layer of homogenous material. In other cases, the conductive layer 110 may include multiple sublayers made from different materials. In some embodiments, the conductive layer 110 includes a top sublayer and one or more sublayers below the top sublayer. In embodiments, the top sublayer does not include silver, copper, aluminum, or other conductive materials that have a greater tendency to oxidize than silver, copper, or aluminum. The top sublayer may be less conductive than the other sublayer(s). In some embodiments, the conductive layer 110 includes a conductive carbon layer as a top sublayer and a silver layer as another sublayer below the carbon layer. The conductive layer 110 has a thickness that may vary depending on the particular example. In some embodiments, the conductive layer 110 can be omitted and the nanoporous layer is directly connected to the current sensor via a conductive wire or connection.

[0080] Counter electrode With the bias voltage, reduction of the chemical component occurs at the counter electrode 105. In embodiments, the counter electrode 105 includes at least one conductive or semiconductive material and is connected to the electrical circuit of the system 101. In embodiments, the counter electrode 105 may be formed from a single layer of homogenous material or multiple layers made from different materials. The conductive or semiconductive material for the conductive layer 110 may also be used in the counter electrode 105, although in certain systems, non-identical materials are used in the conductive layer 110 and the counter electrode 105. reference electrode

[0081] The reference electrode 106 provides stability in the electrochemical sensing system by maintaining a bias voltage between the sensing electrode 103 and the reference electrode. As a result, glucose oxidation can continue at the sensing electrode 103 even if the reduction at the counter electrode 105 is not at the same rate as the oxidation at the sensing electrode 103. In some embodiments, the counter electrode 105 can be omitted and the reference electrode 106 can serve the dual function of counter and reference electrodes. In embodiments, the reference electrode 106 can be formed from a single layer of homogenous material or multiple layers made from different materials. A conductive or semiconductive material for the conductive layer 110 can also be used in the reference electrode 105, although in certain systems, non-identical materials are used in the conductive layer 110 and the reference electrode 106. In some embodiments, the reference electrode 106 can include a salt layer on the conductive or semiconductive material layer. For example, the salt layer is made from or includes silver chloride (AgCl).

[0082] Current Sensors The current sensor 108 measures the current flowing from the working electrode 103. The current sensor 108 may amperometrically detect the current flowing at a particular point in time. In the alternative, the current sensor 108 may be a coulometric charge-measuring device.

[0083] Test Fluid In an embodiment, the test fluid is, but is not limited to, a human or animal biological fluid. In some embodiments, the test fluid is a liquid mixture that includes a biological fluid and at least one additional substance added to the biological fluid. Biological fluids include, but are not limited to, blood, interstitial fluid, cerebrospinal fluid, lymphatic fluid, or urine. In some embodiments, the test fluid includes a non-biological liquid prepared for the experiment.

[0084] Bias Voltage The bias voltage applied between the working electrode 103NE and the reference electrode 106 is at or about 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45 or 0.46 V. In an embodiment, the applied bias voltage may be within a range formed by selecting any two numbers (two voltage values) listed in the immediately preceding sentence, e.g., about 0.20 V to about 0.30 V, about 0.30 V to about 0.40 V, about 0.28 V to about 0.40 V, about 0.30 V to about 0.38 V, about 0.28 V to about 0.36 V, etc.

[0085] Nanoporous Layer Nanoporous Layer The nanoporous layer 117 for the working electrode 103NE includes nanosized internal structures, such as cavities, spaces, and openings (collectively "nanopores" or "nanopores"). In an embodiment, the nanopores of the nanoporous layer 117 allow or facilitate the oxidation of glucose, and the glucose concentration can be measured based on the current caused by glucose oxidation. Although no aspect of the invention is bound by any theory or belief, it is believed that glucose oxidation occurs when glucose molecules enter the nanopores and contact the internal surface more frequently and for a longer period of time within the nanoporous layer 117 than on the non-porous surface of the electrode.

[0086] No enzyme and no electron mediator Incorporating the nanoporous layer 117, the working electrode 103NE may not be provided with a glucose-specific enzyme, which requires a more complex fabrication process and is less stable than the solid material of the nanoporous layer 117. Additionally, the enzyme-sensing electrode 103NE may operate without an electron mediator to facilitate electron transfer between different materials. In an embodiment, the working electrode 103NE does not include an enzyme or an electron mediator.

[0087] Materials for nanoporous layers In some embodiments, the nanoporous layer 117 is made of or includes, but is not limited to, platinum (Pt), gold (Au), palladium (Pd), rhodium (Rh), titanium (Ti), ruthenium (Ru), tin (Sn), nickel (Ni), copper (Cu), indium (In), thallium (Tl), zirconium (Zr), iridium (Ir), or oxides of the aforementioned elements. In other embodiments, the nanoporous layer 117 is made of or includes, but is not limited to, an alloy material of two or more metal elements listed in the previous sentence, including Pt-Ir, Pt-Ru, Pt-Pd.

[0088] Roughness coefficient specified Roughness factor or roughness is the ratio of real surface area to geometric surface area of ​​an object, where geometric surface area refers to the projected area of ​​an object projected onto a plane without considering the internal surfaces within the object. Real surface area refers to the total area of ​​the surface taking into account the internal surfaces. With reference to FIG. 4, for example, if the nanoporous layer 117 is a rectangular block having a height or depth 118 and a top rectangular surface 119, the projected area or geometric surface area of ​​the nanoporous layer is the area of ​​the top rectangular surface that is exposed to the outside. The real surface area of ​​the nanoporous layer may be, for example, the area of ​​the top rectangular surface that is exposed to the outside for detecting a current from proton adsorption on the real surface. The electrical conductivity of the electrochemically sensitive ionic liquid can be measured electrochemically using well-known cyclic voltammetry techniques, such as those described herein.

[0089] Roughness coefficient of nanoporous layers The roughness factor value indicates the total amount of internal pores within the nanoporous layer 117. The roughness factor of the nanoporous layer 117 may be related to the sensitivity of the nanoporous layer 117 to glucose oxidation. In general, the higher the roughness factor, the more glucose oxidation may occur. The roughness factor of the nanoporous layer 117 may be at or about 100, 200, 300, 400, 500, 600, 700, 800, 900, 100, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, 2100, 2200, 2300, 2400, or 2500. In embodiments, the roughness factor may be within a range formed by selecting any two numbers (two roughness factor values) recited in the immediately preceding sentence, e.g., from about 100 to about 2500, from about 750 to about 1250, or from about 850 to about 1150.

[0090] Nanoporous layer thickness The roughness factor value does not indicate the level of porosity or density of the nanoporous material at that unit volume, but the value may indicate the total amount of internal pores. Thus, depending on the level of porosity of the nanoporous material, in embodiments, the thickness of the nanoporous layer may be adjusted to achieve a target value for the roughness factor. In embodiments, the thickness of the nanoporous layer 117 may be about 0.03, 0.05, 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10 μm. In some embodiments, the thickness may be within a range formed by selecting any two numbers (two thickness values) listed in the immediately preceding sentence, for example, about 0.05 μm (50 nm) to about 10 μm, about 0.5 μm to about 8 μm, or about 2 μm to about 7 μm.

[0091] form The nanoporous layer 117 may have a different internal morphology in each particular production. In some embodiments, the nanoporous layer 117 may include or be made from nanoparticles that are deposited together and form nanopores between themselves (interparticle nanopores). In other embodiments, the nanoporous layer 117 may include or be made from clusters of nanoparticles deposited together that form interparticle nanopores within the clusters and also spaces between the clusters (intercluster gaps or spaces). In other embodiments, the nanoporous layer 117 may include or be made from repeating nanostructures of a particular shape, such as hexagonal structures that contain nanopores therein. Also, in each particular production, the nanoporous layer 117 may have different levels of porosity per unit volume and different roughness factor values.

[0092] Fabrication of nanoporous layers The nanoporous layer 117 may be prepared using a liquid composition comprising metal ions and a surfactant. In embodiments, different morphologies of the nanoporous layer may be formed using different phases of the surfactant. A micellar, reverse micellar, liquid crystalline or other phase of the surfactant may be used to generate a nanoporous layer of a particular morphology. In these different phases, the metal ions are aligned or locally concentrated adjacent to the hydrophilic portion of the surfactant. The localized metal ions in the liquid composition are subjected to additional processes for reduction and deposition on the surface to provide a nanoporous layer 117 with a different morphology.

[0093] Clustered nanoporous layer Clustering morphology 5A shows a vertical cross section of a nanoporous layer having a clustered morphology 120 on a substrate 129. In the nano-sized reality, the top surface of the substrate 129 may not be straight as shown, and may be uneven. In the clustered morphology 120, many nanoparticles 121 come together to form irregularly shaped clusters 125. For illustration purposes, different shading or Shading is used in the different clusters 125. These irregularly shaped clusters 125 stack randomly to form the nanoporous layer. Figure 5B is a transmission electron microscope (TEM) photographic image of some clusters 125 before they are deposited to form the nanoporous layer. Figure 5C is a zoomed-in image of the circled portion of Figure 5B. Figure 5D is a scanning electron microscope (SEM) photographic image of the nanoporous layer with a clustered morphology taken from the top surface of the nanoporous layer.

[0094] Clustered morphology of pores and spaces With the irregular stacking of irregularly shaped clusters 125, adjacent clusters form intercluster gaps or spaces 127 between them. These intercluster gaps 127 can be nano-sized and micro-sized. In this disclosure, nano-sized means greater than 1 nm and less than 100 nm, and micro-sized means greater than 100 nm and less than 100 μm. Each cluster 125 includes or is made from roughly spherical or ovoid nanoparticles 121. In each cluster, the individual nanoparticles are generally separated from each other and form small gaps 123 between them. The small gaps are nano-sized and are called interparticle nanopores 123. In embodiments, the interparticle nanopores are found throughout the cluster. In embodiments, the interparticle nanopores form interconnected or networked channels within each cluster. Figures 5A and 5D show these interparticle nanopores 123 within each cluster 125.

[0095] Inter-cluster gap / space formation In an embodiment, to generate the clustered morphology, the irregularly shaped clusters 125 are first prepared as a suspension in a liquid. The suspension is then dispensed onto a substrate 129, which is allowed to dry. As the liquid dries, the clusters naturally deposit on the substrate and on other clusters. During drying, no external force can be applied to the clusters. Thus, the clusters do not pack as they deposit. As the clusters deposit and pile up on other clusters, each cluster may contact the substrate surface or adjacent clusters. After drying is complete, the clusters abut or contact adjacent or neighboring clusters. The deposited clusters are interconnected or merged through junctions or contacts. Due to the irregular shape of the individual clusters, irregularly shaped gaps and spaces are formed between adjacent clusters, where the gaps and spaces define the irregular shape of the deposited clusters as if the surface and contour of the deposited clusters were surrounded by the irregularly shaped gaps and spaces. The irregularly shaped gaps and spaces are referred to as inter-cluster gaps or spaces 127.

[0096] Distribution of clusters and intercluster gaps In an embodiment, the irregularly shaped cluster bodies 125 are distributed throughout the clustered morphology 120 of the nanoporous layer 117. The irregularly shaped cluster bodies 125 are interconnected through junctions, meaning that they contact themselves and form a three-dimensional network of cluster bodies generally throughout the nanoporous layer 117. The inter-cluster gaps 127 define the surfaces of the irregularly shaped cluster bodies, surround them, and interconnect with themselves, forming three-dimensional interconnected or networked channels throughout the nanoporous layer 117. The inter-cluster gaps and spaces 127 are well distributed throughout the nanoporous layer 117 from the top surface (not shown) to the bottom surface (on or just above the substrate 129). The three-dimensional network of the irregularly shaped cluster bodies and the three-dimensional network of the irregularly shaped gaps are three-dimensionally complementary, forming a highly networked three-dimensional mesh structure. The three-dimensional network of cluster bodies and channels resembles the three-dimensional internal geometry of a sponge, except that the interparticle gaps and spaces are networked together throughout the nanoporous layer 117. There is a possibility of similarity.

[0097] Distribution of nanoparticles and interparticle nanopores Assuming that each cluster is formed of many nanoparticles 121 and interparticle nanopores 123, the nanoparticles 121 and interparticle nanopores 123 are distributed generally throughout the nanoporous layer 117. The interparticle nanopores 123 are therefore interconnected within each cluster, and with interparticle nanopores of other clusters generally throughout the nanoporous layer 117, via interparticle nanopores in the junctions between clusters, and via intercluster gaps 127 that are interconnected throughout the nanoporous layer 117.

[0098] Intercluster gaps / spaces for glucose diffusion In an embodiment, the interconnection of the inter-cluster gaps 127 is performed by grouping the inter-cluster gaps 127 within the nanoporous layer 117. Provides networked channels for the diffusion of course molecules (0.7-0.8 nm long) Glucose oxidation occurs mainly in the nanopores between nanoparticles rather than in the microspaces. As the inter-cluster gaps 127 become networked or interconnected throughout the nanoporous layer 117, the size of the glucose molecules increases. Considering the large scale cluster Through the inter-cluster spaces, glucose molecules can reach almost anywhere in the nanoporous layer 117. Also, because the inter-cluster gaps 127 are well interconnected to the inter-particle nanopores 123, any inter-particle nanopore 123 in the nanoporous layer 117 may be exposed and open for glucose oxidation. Therefore, the three-dimensional interconnected or networked channels of the inter-cluster gaps can provide more glucose oxidation, i.e., a stronger signal of glucose oxidation (higher current), than a nanoporous layer without such interconnected channels formed in the inter-cluster gaps.

[0099] Two types of particles and two types of pores As depicted, the clustered morphology 120 includes two different types of particles that define two different types of pores. In terms of particles, one is the nanoparticles 121 and the other is the clusters 125 made from the nanoparticles 121. In terms of pores, one is the interparticle nanopores 123 between the nanoparticles 121 within the clusters 125 and the other is the intercluster gaps 127 between the clusters 125.

[0100] Nanoparticle Clusters The TEM photographic image in FIG. 5B shows clusters of irregular shape. The number of nanoparticles 121 in each cluster can vary widely, and the size of the clusters 125 can vary accordingly. In the clustered morphology, some clusters 125 are nano-sized (smaller than 100 nm) and others are micro-sized (100 nm to 100 μm). The clusters 125 have lengths or diameters of about 20, 40, 60, 80, 100, 120, 140, 160, 180, 200, 220, 240, 260, 280, 300, 320, 340, 360, 380, 400, 420, 440, 460, 480, 500, 520, 540, 560, 580, 600, 620, 640, 660, 680 or 700 nm. In an embodiment, the length or diameter of clusters 125 may be within the range formed by selecting any two numbers (two length or diameter values) recited in the immediately preceding sentence, e.g., from about 20 nm to about 300 nm, or from about 60 nm to about 240 nm. Clusters 125 may have an average diameter or length of about 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 280, or 300 nm. In an embodiment, the average diameter of clusters 125 may be within the range formed by selecting any two numbers recited in the immediately preceding sentence, e.g., from about 100 nm to about 220 nm.

[0101] Nanoparticles The TEM photographic image of FIG. 5C shows the nanoparticles in a single cluster. The nanoparticles 121 in the cluster are separate and generally spherical (ball-like) or ovoid (egg-like) in shape, but are not limited thereto. The nanoparticles 121 have a diameter of about 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, or 6.5. In an embodiment, the diameter may be within a range formed by selecting any two numbers (two diameter values) recited in the immediately preceding sentence, for example, from about 2 nm to about 5 nm. The nanoparticles 121 may have an average diameter of about 2.0, 2.25, 2.5, 2.75, 3.0, 3.25, 3.5, 3.75, or 4.0. In embodiments, the average diameter of the nanoparticles 121 may be within the range formed by selecting any two numbers recited in the immediately preceding sentence, e.g., from about 2.5 nm to about 4.0 nm, from about 2.75 nm to about 3.75 nm, or from about 2.25 nm to about 3.5 nm. In embodiments, nanoparticles having an average diameter of 2-5 nm are found throughout the nanoporous layer 117.

[0102] Interparticle Nanopores The TEM photographic image in FIG. 5C also shows interparticle nanopores between the nanoparticles within the cluster. The interparticle nanopores are networked and interconnected within the cluster. Interstitial gaps or nanopores 123 exist between two directly adjacent nanoparticles in the same cluster. The interparticle gap distance is about 0.25, 0.5, 0.75, 1.0, 1.25, 1.5, 1.75, 2.0, 2.5, 3.0, 3.5, 4.0 or 4.5 nm. In an embodiment, the interparticle gap distance is within a range formed by selecting any two numbers (two distance values) listed in the immediately preceding sentence, for example, about 0.5n The interparticle nanopore may be about 1.5 nm to about 4.5 nm, or about 1.5 nm to about 4.0 nm. 123 may have an average interparticle gap distance of about 0.5, 0.75, 1.0, 1.25, 1.5, 1.75, 2.0, 2.25, 2.5, 2.75, 3.0 or 3.5 nm. In an embodiment, the average interparticle gap distance of the nanopores 123 is any of those listed in the immediately preceding sentence. Within the range formed by selecting two numbers, for example, about 0.75 nm to about 1.5 nm, or about 1.0 nm to about 2.5 nm m In an embodiment, inter-particle nanopores 123 are found throughout the nanoporous layer 117, with an average inter-particle gap distance of 1-2.5 nm.

[0103] Inter-cluster gaps / spaces The SEM photographic image in FIG. 5D shows the opening of the networked intercluster gaps visible from the top surface of the nanoporous layer. Although the three-dimensional shape is not well presented in the two-dimensional image in FIG. 5D, the top surface of the nanoporous layer contains valleys and hills formed by the stacked clusters. Inside the nanoporous layer, the valleys and hills form intercluster gaps. The intercluster gaps or spaces are irregularly shaped. The intercluster gaps 127 are nano- to micro-sized. The intercluster gaps 127 have an intercluster gap distance of about 25, 50, 75, 100, 125, 150, 175, 200, 225, 250, 275, 300, 325, 350, 375, 400, 425, 450, 475, 500, 525, 550, 575, 600, 625, 650, 675 or 700 nm. In an embodiment, the inter-cluster gap distance may be within the range formed by selecting any two numbers recited in the immediately preceding sentence, for example, from about 100 nm to about 1000 nm. The inter-cluster gaps 127 have an average inter-cluster gap distance of about 100, 150, 200, 250, 300, 350, 400, 450, or 500 nm. In an embodiment, the average inter-cluster gap distance may be within the range formed by selecting any two numbers recited in the immediately preceding sentence, for example, from about 150 nm to about 400 nm.

[0104] Fabrication of clustered nanoporous layers The whole process In embodiments, nanoporous layers with clustered morphology may be prepared using an isotropic reverse micelle phase (or "reverse micelle phase") of a surfactant. Referring to FIG. 6A, in step 601, an aqueous liquid composition is prepared using a source of metal ions and a surfactant in a reverse micelle phase. The metal ions are locally concentrated within the hydrophilic spaces of the individual reverse micelles. Then, in step 603, a reducing agent is added to the reverse micelle phase to form metal nanoparticles dispersed in a liquid composition that includes the surfactant ("nanoparticle colloid" or "nanoparticle-surfactant colloid"). Then, in step 605, the surfactant is removed from the nanoparticle-surfactant colloid, and the nanoparticle clusters dispersed in the liquid ("cluster colloid" or "cluster-liquid colloid") are collected. Optionally, in step 607, the collected cluster colloids are mixed with a non-surfactant liquid. In step 609, the cluster colloids are distributed onto a surface, for example, by a printing technique, without the use of electroplating. The liquid is then dried in step 611 to form a nano-porous layer 117 on the surface 129 .

[0105] Surfactants Surfactants are amphiphilic organic compounds that have a hydrophilic head (or hydrophilic portion) and a hydrophobic tail (hydrophobic portion) in a single molecule. Surfactants can form different structures or phases in water, depending on the concentration and temperature. Figure 7 is an example phase diagram for a surfactant showing the different phases, including a micellar phase 131, a hexagonal phase 133, a lamellar phase 135, and a two-micellar phase 137.

[0106] Preparation of isotropic reverse micellar phases In step 601, an isotropic reverse micellar phase is prepared using an aqueous liquid composition comprising a surfactant, metal ions, and water. As in the conceptual illustration of FIG. 8, the reverse micellar phase comprises reverse micelles 141 formed by surfactant molecules. Each reverse micelle 141 comprises a hydrophilic core 143 surrounded by hydrophobic tails radiating from the hydrophilic core. The hydrophilic core 143 encapsulates the hydrophilic components of the liquid composition, i.e., water and metal ions. Thus, the metal ions are locally concentrated within the hydrophilic core 143 of the reverse micelles.

[0107] Surfactant Examples The surfactant is selected from those that can form an isotropic reverse micelle phase under reasonable conditions for processing. In some embodiments, non-ionic surfactants are used, but are not limited to them. Non-limiting examples of surfactants include alkylbenzenesulfonates, alkyl-polyglycosides, alkyl sulfates, carboxylates, carboxylate esters, cetomacrogol 1000TM, cetostearyl alcohol, cetyl alcohol, cocamide DEA, cocamide MEA, decyl glucoside, decyl polyglucose, disodium cocoamphodiacetate, ethoxylated fatty alcohols, glycerol monostearate, glycol esters of fatty acids, IGEPAL CA-630™, Isoceteth-20, Lauryl Glucoside, Maltoside, Monolaurin, Mycosubtilin, Naphthalene Sulfonate, Narrow-Range Ethoxylate, Nonidet P-40™, Nonoxynol-9, Nonoxynol, NP-40™, Octaethylene Glycol Monododecyl Ether, N-Octyl β-D-Thioglucopyranoside, Octyl Glucoside, Oleyl Alcohol, PEG-10 Sunflower Glyceride, Pentaethylene Glycol Monododecyl Ether , polidocanol, poloxamer, poloxamer 407, polyethoxylated tallow amine, polyethylene glycol esters, polyglycerol polyricinoleate, polyoxyethylene fatty acid amides, polyoxyethylene surfactants, polysorbates, polysorbate 20, polysorbate 80, sorbitan, sorbitan monolaurate, sorbitan monostearate, sorbitan tristearate, stearyl alcohol, surfactin, sulfated alkanolamides, sulfonates, Triton X-100 (trade name) (trademark), and Tween 80. A person of ordinary skill in the relevant art will recognize what constitutes a reasonable condition.

[0108] Conditions for reversed micellar phases After the surfactant is selected, its concentration and temperature are adjusted to form an isotropic reverse micelle phase. The concentration and temperature of the surfactant can be determined in relation to the phase diagram of the surfactant. If the phase diagram is not available, some experimentation may be required to find the appropriate concentration and temperature using known laboratory techniques and procedures. For example, if Triton X-100 is used for the surfactant, a concentration of 10-60 wt% and a temperature of 40-80°C can provide a reverse micelle phase.

[0109] Metal Ion Source One or more metal ions corresponding to the metal or alloy for the nanoporous layer are selected for the liquid composition. The metal ions are added in the form of a compound containing an ionic metal, such as an acid, base, or salt. Non-limiting examples of metal source compounds include H 2 PtCl 6 , HPt(OH) 6 , H 2 PtCl 2 (OH) 4 , H 2 Pt(SO 4 )(OH) 4 , PtCl 4 , K 2 PtCl 6 , PdCl 2 , and TiCl 4 Examples include:

[0110] Metal ion concentration The concentration of metal ions is also adjusted for best performance: if the concentration is too low, nanoparticles may not be formed; if the concentration is too high, the formation or stability of the reverse micelle phase of the surfactant may be affected. The concentration of the metal ion is about 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.012, 0.014, 0.016, 0.018, 0.02, 0.022, 0.024, 0.026, 0.028, 0.03, 0.032, 0.034, 0.036, 0.038, 0.04, 0.042, 0.044, 0.046, 0.048, 0.05, 0.055, 0.06, 0.065, 0.07, 0.075, 0.08, 0.085, 0.09, 0.095 or 0.1M. In embodiments, the concentration may be within a range formed by selecting any two numbers (two molar concentration values) recited in the immediately preceding sentence, e.g., about 0.01 to about 0.03 M, about 0.02 to 0.03 M, etc. Within the appropriate concentration range, it has been observed that the level of concentration affects the rate of nanoparticle formation.

[0111] Different from plating bath The reverse micelle phase prepared in step 601 differs from plating bath compositions for electroplating in that, unlike plating baths, metal chelating agents may not be required.

[0112] Nanoparticle formation In step 603, a reducing agent is mixed into the aqueous liquid composition of the reverse micelle phase. When the reducing agent enters the hydrophilic core 143 of the reverse micelles 141, it reduces the metal ions to metal atoms within the hydrophilic core 143. Initially, the metal atoms remain within the hydrophilic core 143, as the metal ions are locally concentrated within the hydrophilic core 143. The metal atoms within each hydrophilic core 143 coagulate together and grow to form metal nanoparticles. Although not limited to, one metal nanoparticle can grow from one reverse micelle. The resulting metal nanoparticles are generally uncharged, i.e., neutral. However, some nanoparticles can have a slight positive charge on their surface. Thus far, electricity has not been applied to form metal nanoparticles.

[0113] Nanoparticle colloid The nanoparticles are dispersed in a liquid to provide a nanoparticle colloid. Figure 8 shows the resulting nanoparticle colloid conceptually. During the process of reduction of metal ions and growth of nanoparticles, , some reverse micelles break or collapse, and thus nanoparticles from those collapsed reverse micelles can be dispersed in the hydrophobic space. Some of those nanoparticles 151 can float freely outside the hydrophilic core of the reverse micelles in the resulting colloidal composition. Some other nanoparticles 153 can be surrounded or bound by the hydrophilic heads of the surfactant molecules outside the hydrophilic core of the reverse micelles. Some nanoparticles 155 remain inside the reverse micelles 141. Overall, in the resulting nanoparticle colloid, solid nanoparticles 151, 153, 155 are dispersed in a liquid composition that includes reverse micelles 141, water, and surfactant molecules. Because the nanoparticles 151, 153, 155 are significantly separated from each other in the nanoparticle colloidal composition, it is unlikely that the nanoparticles will aggregate and grow into larger particles.

[0114] Reducing Agent A reducing agent is a chemical moiety that can donate one or more electrons to a metal ion contained within a nanoparticle colloid. The reducing agent is a hydrophilic compound that enters the hydrophilic core of the reverse micelle. Non-limiting examples of hydrophilic reducing agents include ascorbic acid, acetic acid, formaldehyde, citric acid, hydroxylamine, hypophosphites, etc.

[0115] Amount of reducing agent The hydrophilic reducing agent is added to the nanoparticle colloid in an amount sufficient to reduce the metal ions contained therein. In some embodiments, the reducing agent is added in a substantially greater excess than the stoichiometric amount to reduce the total metal ions contained in the nanoparticle colloid, where "substantially greater than" means by 20, 40, 60, 80, 100, 120, 140, 160, 180, 200, 250, 300, or 400% greater.

[0116] stirring During and / or after the addition of the reducing agent, the mixture may be stirred to promote distribution of the reducing agent. Stirring can promote the reducing agent to enter the hydrophilic space of the reverse micelles. Thus, the time to completely reduce the metal ions in the hydrophilic space may be reduced. Stirring may be performed continuously or intermittently. In an embodiment, stirring is performed for a period of 1 hour to 10 hours.

[0117] Removing surfactant and forming clusters In step 605, the surfactant is substantially removed from the nanoparticle colloid composition to form nanoparticle clusters. In the nanoparticle colloid, the surfactant can stabilize the individual nanoparticles, and therefore the nanoparticles cannot cluster together if a significant amount of surfactant is present. To remove the surfactant from the nanoparticles, the nanoparticle colloid is subjected to centrifugation. After centrifugation, most of the nanoparticles will settle to the bottom, and the surfactant molecules can be present in the supernatant and at the bottom. The supernatant is separated from the bottom, which contains most of the nanoparticles. In an embodiment, a liquid can be added to the separated nanoparticles, diluting the surfactant in the collected bottom. The liquid added to the nanoparticles can be water or an aqueous solution, which can be, but is not limited to, an acidic or basic solution. The centrifugation, bottom collection, and liquid addition can be repeated multiple times, and the nanoparticles with the surfactant substantially removed are collected.

[0118] Chemical bonding between surfactants and nanoparticles With surfactants, some nanoparticles have strong chemical bonds with the hydrophilic heads of some surfactant molecules. Surfactant molecules with negatively charged hydrophilic heads can form coordinate bonds with the nanoparticle surface. Also, if surfactant molecules have electron-rich hydrophilic heads (even if they are uncharged), they can form coordinate bonds with the nanoparticle surface. When such surfactants are used, the chemical bonds must be broken to remove the surfactant from the nanoparticle colloid.

[0119] Breaking Chemical Bonds In some embodiments, the acidic or basic solution is Nanoparticles in step 603 After formation, and In step 604 of Before centrifugation, the nanoparticle-surfactant colloid was added The acid or base of the added solution breaks the coordinate bonds between the surfactant and the nanoparticles. This triggers a chemical reaction that frees the nanoparticles. For example, protons from the acid carry a negative charge. The nanoparticles can then bind to the electron-rich surfactant heads, freeing the nanoparticles. Subsequent centrifugation and bottom collection separates the liberated nanoparticles from the surfactant molecules. In an embodiment, the addition of an acidic or basic solution may be performed at least once before centrifugation. In some embodiments, the addition of an acidic or basic solution is performed before each centrifugation. In embodiments, the acid and base may be washed with water or other solvent after centrifugation.

[0120] Acidic or basic solutions In embodiments, the acid or base is selected in consideration of the surfactant, so that the surfactant molecules are effectively desorbed from the nanoparticles. In embodiments, the acidic solution has a pH value less than about 3, but is not limited thereto. For example, non-limiting examples of acids for the acidic solution include HCl, HNO 3 , H 2 SO 4 , HClO 4 In embodiments, the basic solution has a pH value greater than about 10, but is not limited thereto. For example, non-limiting examples of bases for the basic solution include NaOH, KOH, Ca(OH) 2 , etc.

[0121] Cluster colloid After or during the process of removing the surfactant and collecting the nanoparticles, the nanoparticles tend to cluster together or aggregate to form clusters of nanoparticles. In the liquid, the clusters are dispersed and a cluster colloid is formed. Each cluster contains metal nanoparticles that interact with each other and are produced from this to form a larger body. The individual nanoparticles within the cluster are most likely electrically neutral. Although the invention is not bound by any theory or belief, it is believed that protons, hydroxides and other charged electrolytes can be attached to the nanoparticle surface and that the ionic interactions of these electrolytes with neighboring nanoparticles can keep the neighboring nanoparticles together and form clusters. In fact, although the surfactant molecules have been substantially removed, the liquid of the cluster colloid contains a sufficient amount of electrolytes from the metal ion source and the acidic or basic solution used in the previous preparation step.

[0122] Clusters and Nanoparticles Figure 9 provides TEM photographic images of nanoparticle clusters from a dilute sample of cluster colloids. Two of the images in Figure 9 are also seen in Figures 5B and 5C. In these images, the clusters do not have a regular shape and are about 30 to about 500 nm long. The nanoparticles 121 within the clusters are separate, roughly spherical or ovoid, and have diameters of about 2-3 nm. Between adjacent or neighboring nanoparticles 121, there are interparticle gaps 125 with gap distances of about 1-2 nm. These interparticle nanopores 125 are primarily responsible for glucose oxidation in glucose sensing electrodes with clustered nanoporous layers.

[0123] Centrifugation Centrifugation may be carried out at a rotation speed of 3000-5000 rpm. Centrifugation may continue for a period of 3-15 minutes. After centrifugation, the supernatant is removed and the bottom containing the nanoparticles is collected. Liquid is added to the collected bottom to dilute the surfactant contained therein. Centrifugation, bottom collection and liquid addition can be repeated multiple times, for example, three or more times.

[0124] Substantially Removed Surfactant Using multiple rounds of centrifugation, the surfactant is substantially removed. In the resulting cluster colloids, the surfactant concentration is significantly lower, but may not be completely removed. Initially, the reverse micellar phase contains about 10 to about 60 wt of surfactant. The resulting cluster colloids can be completely free of surfactant. In fact, the resulting cluster colloids are substantially free of surfactant. The residual surfactant in the resulting cluster colloid or final collection at the bottom can be greater than 0.0001 parts by weight per 100 parts by weight of nanoparticles and less than about 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4 or 2.6 parts by weight per 100 parts by weight of nanoparticles. In embodiments, the remaining surfactant may be in an amount of less than about 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4 or 0.5 parts by weight per 100 parts by weight of nanoparticles.

[0125] Concentration of nanoparticles in cluster colloids After multiple rounds of centrifugation, the total amount of nanoparticles (as part of clusters and free nanoparticles) in the final bottom collection can be about 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, or 40 wt%. In embodiments, the concentration can be within a range formed by selecting any two numbers recited in the immediately preceding sentence, e.g., about 20 to about 30 wt%, about 15 to 25%, etc.

[0126] Preservation of cluster colloids The clusters are dispersed in the cluster colloid for an extended period of time, for example, longer than one week or one month, without processing. The cluster colloid can be stored in the container after preparation for some time before further processing. Once prepared, the cluster colloid can be sold and transported for processing by others or elsewhere. To maintain colloidal properties for an extended period of time, the concentration of the nanoparticles can be adjusted after the final collection at the bottom. In an embodiment, the cluster colloid of the final collection at the bottom can be stored or transported in the container with or without adjusting the concentration.

[0127] Adjusting the concentration for distribution In step 607, the collected cluster colloids may be stored for a period of time, with or without dilution with a solvent. The dilution may be to adjust the concentration of clusters in the cluster colloids for further processing, e.g., distribution. The solvent may be water or an organic compound. One or more additive compounds may be added. By dilution, the concentration of nanoparticles or clusters is adjusted to about 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.1, 3,2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 11, 12, 13, 14 or 15 wt%. In embodiments, the concentration of nanoparticles or clusters may be within the range formed by selecting any two numbers recited in the immediately preceding sentence, e.g., about 0.5 to about 2 wt%, about 1 to 3 wt%, etc. After dilution, the remaining surfactant may be less than about 0.1, 0.2, 0.4, 0.6, 0.81, 1.2, 1.4, 1.6, 1.8, or 2 wt%.

[0128] Cluster colloid distribution In step 609, the cluster colloids are dispensed onto the substrate 129 to produce a nanoporous layer while maintaining its colloidal properties. A variety of dispensing techniques can be utilized to dispense the cluster colloids. Dispensing can be controlled to form a certain thickness of dispensed cluster colloids, or to provide an appropriate thickness of the resulting nanoporous layer after subsequent drying. In other cases, dispensing can be controlled to provide an appropriate roughness factor value of the resulting nanoporous layer.

[0129] Lower layer substrate The cluster colloids may be applied onto a substrate made of any material. In embodiments for a glucose sensing electrode, the cluster colloids may be applied onto a conductive or semiconductive surface for conductive layer 110, as described above. In some embodiments, the substrate includes two or more conductive layers.

[0130] Drying of liquids to form clustered nanoporous layers In step 611, the dispensed cluster colloids are subjected to conditions to dry the liquid. Once dispensed, the nanoparticle clusters float within the liquid and are free to move horizontally and vertically. As the liquid dries, the height of the cluster colloids decreases. As the liquid continues to dry, the clusters come into contact with neighboring clusters, both vertically and horizontally, between the underlying substrate 129 and the top surface of the cluster colloids. The mobility of the clusters becomes significantly restricted. After a time, the liquid level becomes lower than the clusters located at or near the top surface. Once drying is complete, the nanoparticle clusters are deposited on the substrate 129, forming a nanoporous layer with a clustered morphology 120, as illustrated in FIG. 5A.

[0131] Nanoporous layer thickness The resulting nanoporous layer has a thickness of about 0.4, 0.6, 0.8, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, or 30 μm. In embodiments, the thickness may be within a range formed by selecting any two numbers recited in the immediately preceding sentence, e.g., from about 1 μm to about 10 nm.

[0132] No cleaning of nanoporous layer The resulting nanoporous layer does not require washing with water or other liquids. In embodiments, the resulting nanoporous layer in clustered form is not washed with water or other liquids at all after drying. In embodiments, the nanoporous layer is not subjected to contact with liquids except for subsequent processing to add layers on the nanoporous layer.

[0133] Yield - Metal Recovery When an excess amount of reducing agent is added to the nanoparticle colloid, most of the metal ions in it The surfactant is removed and metal atoms are formed, which solidify to form nanoparticles. Subsequent treatment to remove the nanoparticles also collects most of the nanoparticles in the clusters. Most of the metal ions added in the above process end up in the form of nanoparticle clusters. The nanoporous layer 117 is then collected and deposited in the same manner, resulting in a nanoporous layer 117. 89, 90, 91, 92, 93, 94, 95, 96, 9 7 or more than 98% is collected in the form of nanoparticle clusters prior to distribution.

[0134] Mass production The nanoporous layer 117 can be mass produced by printing the cluster colloids onto the substrate 129. Printing the cluster colloids takes only a second or two. Drying the liquid may take longer, but only requires a large space for drying. In an embodiment, many separate substrates are provided and printing can be performed on each of the separate substrates. Each printed substrate is then dried to form a nanoporous layer. Alternatively, multiple areas can be printed with the cluster colloids onto a single substrate, and the single substrate can then be cut into multiple pieces, each containing a printed area. The single substrate can be dried prior to cutting.

[0135] No electroplating or application of electricity Throughout the process, electroplating is not utilized to form a clustered morphology for the nanoporous layer, and furthermore, electricity is not applied to the substrate 129 on which the nanoporous layer is formed.

[0136] Non-clustered nanoporous layer Non-clustered morphology Figure 10A shows a non-clustered morphology 161 for the nanoporous layer 117. Like the clustered morphology 120, the non-clustered morphology 161 includes both nanoparticles 121 and interparticle nanopores 123 formed between adjacent or neighboring nanoparticles 121. The descriptions of the nanoparticles 121 and the interparticle nanopores 123 generally apply to the non-clustered morphology 161. Figure 10B is a TEM photographic image of the non-clustered morphology of a nanoporous layer formed on a metal surface, in which the dark areas are part of the metal surface. The nanoparticles and interparticle pores in the TEM photographic image are similar to those depicted in Figure 10A.

[0137] No clusters and no intercluster gaps Unlike the clustered morphology 120, the non-clustered morphology 161 does not include clusters 123 or inter-cluster gaps 127. To produce the non-clustered morphology, nanoparticles are deposited by electroplating onto a substrate 129 without preparing clusters prior to electroplating. As a result, neither clusters nor inter-cluster gaps are formed in the resulting structure, i.e., the non-clustered morphology 161. Thus, the non-clustered morphology 161 does not have the properties of the clustered morphology, resulting from the clusters 123 or inter-cluster gaps 127.

[0138] Non-clustered morphology of cavities Although there are no intercluster gaps, the non-clustered morphology 161 may include internal cavities 133 that are significantly larger than the interparticle nanopores 123. The internal cavities 133 may form during the electroplating process because the nanoparticles are not necessarily stacked sequentially on the underlying surface. The internal cavities 133 are irregularly shaped and irregularly sized. The internal cavities 133 may be found throughout the nanoporous layer 117.

[0139] Cavities as distinguished from intercluster gaps or spaces The cavities 133 of the non-clustered morphology are distinct from the inter-cluster gaps 127 of the clustered morphology 120. The cavities 133 are formed because electroplating and nanoparticle deposition are not at the same rate on the surface of the substrate 129. The cavities 133 do not surround or define one or more clusters 125 of nanoparticles 121. Rather, each cavity 133 is surrounded or defined by an aggregate or collection of nanoparticles 121. Although the cavities 133 may be interconnected by interparticle nanopores 123, the cavities 133 themselves are not interconnected throughout the entire nanoporous layer 117 or over any substantial portion thereof. Furthermore, the cavities 133 do not occupy as much of the volume of the nanoporous layer 117 (lower roughness factor in the non-clustered morphology) as the inter-cluster gaps 127 (higher roughness factor in the clustered morphology).

[0140] Substrate substantially coated with nanoparticles 10A and 10B, the top surface of the substrate 129 is substantially coated with nanoparticles 121. In some embodiments, the substantial interior space is above or directly above the substrate 129. The present invention is not limited to, but may be formed on

[0141] Comparison of clustered and non-clustered morphologies Overall, the clustered morphology 120 is much less dense than the non-clustered morphology 161. For the same thickness, the clustered morphology 120 has a higher roughness factor than the non-clustered morphology 161, and therefore, to produce the same roughness factor, the clustered morphology 120 can be made thinner than the non-clustered morphology. Also, given the irregular shape of the clusters, the inter-cluster gaps 127 of the clustered morphology 120 are interconnected generally throughout the nanoporous layer 117, whereas the internal cavities 133 of the non-clustered morphology 161 are not connected in the same way as the inter-cluster gaps 127. Thus, the inter-particle nanopores 125 in the clusters 123 are connected to the network of inter-cluster gaps 127 in the clustered morphology 120, whereas there are no inter-cluster gaps in the non-clustered morphology 161, and the inter-particle nanopores 125 cannot be connected as they are in the clustered morphology 120.

[0142] Fabrication of non-clustered nanoporous layers - electroplating The whole process A nanoporous layer having a non-clustered morphology can be prepared using electroplating. Referring to Figure 11, in step 1101, a plating bath is prepared containing metal ions and a surfactant in a reverse micelle phase. Then, in step 1103, electroplating is performed in the plating bath to deposit a nanoporous layer in a non-clustered morphology. In step 1105, the resulting nanoporous layer is washed to remove the surfactant therefrom.

[0143] Preparation of plating bath In step 1101, the plating bath is similar to the reverse micelle phase of step 601 of FIG. 6A for producing a clustered nanoporous layer without electroplating. The plating bath includes a surfactant and a metal ion source material in a reverse micelle phase, similar to the production of a clustered nanoporous layer. All the descriptions regarding the surfactant and the metal ion source material in step 601 of FIG. 6A are applicable to step 1101 of FIG. 11. However, the plating bath in step 1101 is not the same as the reverse micelle phase of step 601. One important difference may be that the plating bath may require some additional materials in consideration of electroplating in the next step. For many metal source compounds that may be naturally reduced, the plating bath may require a chelating agent to keep the metal ions from being naturally reduced during and before electroplating. In contrast, such a chelating agent may not be required in the reverse micelle phase of step 601.

[0144] Electroplating In step 1103, electroplating is performed in an aqueous liquid composition in a reverse micelle phase containing metal ions. In a plating bath containing the liquid composition, a cathode and an anode electrode are submerged and connected to a power source. When a DC voltage is applied between the cathode and the anode electrodes, the cathode electrode supplies electrons to the aqueous liquid composition. The electrons jump from the cathode electrode to the hydrophilic space in the immediate vicinity of the reverse micelle, and inside the hydrophilic space, they can reduce the positively charged metal ions to metal atoms. The metal atoms come together to form metal particles, which can be deposited on the cathode electrode surface. In the process, the reverse micelle can rupture. The electrons supplied to the cathode electrode move through the deposited nanoparticles and become available on the outer surface of the deposited nanoparticles. The electrons are then available to reduce the nearby metal ions, forming metal nanoparticles, which are deposited on the already deposited nanoparticles.

[0145] Time for electroplating Electroplating is about 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55 or 60 minutes to obtain a nanoporous layer having a roughness factor of 100 to 800. In embodiments, the time for electroplating may be within a range formed by selecting any two numbers recited in the immediately preceding sentence, e.g., from about 10 to about 30 minutes. In embodiments, the time for electroplating is controlled to obtain a nanoporous layer having a roughness factor of 100 or greater.

[0146] Formation of successive layers and cavities In reduction by electroplating, the nanoparticles adjacent to the cathode electrode are deposited first on the surface of the cathode. Additional nanoparticles are then deposited on the previously deposited nanoparticles 121. Thus, the nanoparticles are generally deposited in successive layers on the cathode electrode. However, because the deposition of nanoparticles may not occur at the same rate throughout the cathode surface and the previously deposited layer of nanoparticles, internal cavities 133 may form within the resulting nanoporous layer. The deposition of nanoparticles may grow horizontally or laterally in space, where no nanoparticles are deposited, and some cavities 133 may be enclosed with nanoparticles formed thereon. The cavities 133 may eventually be interconnected via interparticle nanopores 125, but micro-sized channels are not formed throughout or in a substantial portion of the nanoporous layer 117 to interconnect the cavities 133.

[0147] Co-deposited surfactants During the electroplating process, the reverse micelles encapsulating these nanoparticles can be ruptured and the nanoparticles are deposited on the cathode electrode. A significant amount of surfactant molecules from the ruptured reverse micelles are deposited on the cathode electrode together with the nanoparticles. During the electroplating process, the surfactant molecules can be bound to the nanoparticle surface and nanoparticle-surfactant molecule complexes can be deposited together. The surfactant molecules can be intercalated or trapped between the nanoparticles in the resulting nanostructure.

[0148] Remaining surfactants and their effects The surfactant molecules deposited together with the nanoparticles may occupy the gaps and spaces between the nanoparticles, i.e., the interparticle pores. These surfactant molecules may effectively block the nanopores and nanoparticle surfaces involved in glucose oxidation. In addition, the surfactant molecules may decompose on the metal surface, which may contaminate the nanoparticle surface. Overall, the sensitivity of glucose oxidation may be affected by the surfactant remaining in the nanoporous layer.

[0149] Washing In step 1105, the resulting nanoporous layer is washed with water or other liquid to remove the surfactant molecules therefrom. However, washing is not effective at substantially removing the surfactant molecules because many of the surfactant molecules are trapped between adjacent nanoparticles and the washing liquid can only reach a certain level.

[0150] No nanoparticles colloids In the electroplating method, no reducing agent is added to reduce the metal ions to form nanoparticles. During the electroplating process, nanoparticles may be formed in the hydrophilic space of the reverse micelles next to or near the cathode electrode surface. The nanoparticles may then be deposited on the cathode electrode. However, nanoparticles are not formed in the hydrophilic space of the reverse micelles throughout the liquid composition. Therefore, nanoparticle colloids are not formed, as illustrated in FIG. 8.

[0151] No clusters and no cluster colloids In the electroplating method, there is no step to remove the surfactant after forming the nanoparticles. Rather, the surfactant and nanoparticles are deposited together during the electroplating process. Thus, no clusters are formed at any stage of the process, nor are cluster colloids formed.

[0152] Yield - Metal Recovery Upon completion of electroplating, the plating bath contains significant amounts of metal ions, so metal recovery in electroplating methods may not be as high as reduction by adding excess amounts of reducing agent, as in the process for clustered nanoporous layers.

[0153] Fabrication of nanoporous layers using liquid crystal phases Nanoporous metal layers can be made from liquid crystal phases of surfactants. Referring to FIG. 12, in step 1201, an aqueous liquid composition is prepared to include metal ions and surfactants in a liquid crystal phase, e.g., a hexagonal array. Then, in step 1203, the aqueous liquid composition is subjected to electroplating to deposit a nanoporous layer, where metal atoms are deposited using the liquid crystal phase as a template. In step 1205, the surfactant is removed from the deposited hexagonal nanostructures. FIG. 13A shows the formation of a hexagonal array. FIG. 13B shows the deposition of metal using a hexagonal array of a liquid crystal phase.

[0154] Maltose-blocking layer Maltose Maltose is a disaccharide consisting of two glucose units, as illustrated in Figure 20. Maltose can be present in human or animal blood or other bodily fluids. The presence of maltose in the test fluid can interfere with accurate sensing of glucose levels in both enzymatic and non-enzymatic glucose sensing systems.

[0155] Maltose interference in enzymatic glucose sensing. Some enzymes used in enzymatic glucose sensing systems oxidize maltose as well as glucose. Therefore, if maltose is present in the test fluid, the enzymatic glucose sensing system may have an inaccurate reading of the glucose level due to maltose. If the inaccurate reading is used to control or adjust insulin infusion, the consequences can be severe.

[0156] Maltose interference in nonenzymatic glucose sensing. The nanoporous layer 117 of the working electrode 103NE can oxidize maltose at the same bias voltage as glucose sensing. As illustrated in FIG. 20, with a length of about 1.4-1.6 nm, maltose molecules can enter the interparticle nanopores 123 of the nanoporous layer 117, where they can be oxidized along with glucose. Example 9.11 and FIG. 18 confirm that maltose can be detected in PBS along with glucose and other interfering chemicals. Also, Example 10.9 and FIG. 19 confirm that maltose can be detected in serum along with glucose and other interfering chemicals.

[0157] Non-enzymatic working electrodes with maltose-blocking layers 21, the working electrode 103NE includes a nanoporous layer 117 and a maltose-blocking or maltose-screening layer 301 on the nanoporous layer 117. In an embodiment, the nanoporous layer 117 can oxidize both maltose and glucose, regardless of whether it includes a clustered or non-clustered form. The maltose-blocking layer 301 can be in contact with the underlying nanoporous layer 117 or can be separated by an intervening layer. The working electrode 103NE can also include an additional functional layer 112 on the maltose-blocking layer 301. In another case, the additional functional layer 112 can be inserted between the maltose-blocking layer 301 and the nanoporous layer 117.

[0158] Selective blocking of maltose The maltose-blocking layer 301 effectively or substantially blocks or prevents maltose molecules from passing or penetrating therethrough, while allowing glucose molecules to pass therethrough. With the maltose-blocking layer 301, maltose molecules contained in the test fluid cannot reach the underlying nanoporous layer 117 at all or in a concentration significant to interfere with glucose sensing. Given the selective maltose blocking effect of the maltose-blocking layer 301, the presence of maltose in the test fluid is unlikely to affect glucose sensing, even if the nanoporous layer 117 is able to oxidize maltose at the same bias voltage as for glucose oxidation. In addition, the maltose-blocking layer 301 effectively blocks or prevents other molecules and components of the test fluid that are larger than maltose.

[0159] Bias Voltage In a non-enzymatic glucose sensing system, the addition of the maltose-blocking layer 301 does not require an increase or decrease in the bias voltage for glucose sensing.

[0160] Porous polymer layer In an embodiment, the maltose-blocking layer 301 is made from or includes a porous polymeric material that allows the passage of glucose but not maltose. The porous polymeric material contains at least one poly-phenylenediamine (poly-PD), including poly(m-phenylenediamine) (poly-mPD), poly(o-phenylenediamine) (poly-oPD), and poly(p-phenylenediamine) (poly-pPD).

[0161] Nano-sized thickness The maltose-blocking layer 301 has a thickness of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, or 40 nm or about 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, or 40 nm. Throughout the description, the thickness of the maltose-blocking layer refers to the average thickness of the polymer layer, excluding the upper and lower 10% of the thickness variation. In embodiments, the thickness may be within a range formed by selecting any two numbers (two thickness values) listed in the immediately preceding sentence, such as about 15 nm to about 35 nm, about 17 nm to about 33 nm, about 18 nm to about 32 nm, about 20 nm to about 30 nm, about 21 nm to about 29 nm, about 22 nm to about 28 nm, etc.

[0162] Porosity Level In an embodiment, the maltose-blocking layer 301 has a porosity that allows glucose molecules to pass through its thickness, but effectively blocks maltose molecules from passing therethrough. To achieve the goal of allowing glucose to pass and blocking maltose from passing through, the overall porosity of the maltose-blocking layer needs to be adjusted to a desired level. The overall porosity of the maltose-blocking layer 301 is related to the density (or internal morphology, including pores and channels) and thickness of the layer. The concentration of materials for the maltose-blocking layer and the method of forming the maltose-blocking layer may be related to the density. Although there has been some success in adjusting the overall porosity using these parameters, it has been found that the level of porosity generally cannot be defined or described using the concentration of materials and the method of forming the layer. Thickness of the maltose-blocking layer is also related to the total porosity, which depends on the specific porosity or porosity per volume. Thus, the level of porosity needs to be defined in a different way.

[0163] Maltose - Sensitivity for glucose and maltose without blocking layer (electrochemical flow density) For glucose monitoring, at steady state, glucose concentrations of 4-20 mM (human The bias voltage is 0.2-0.45 V in a test fluid with glucose levels typical of bodily fluids. Using the application of a switching voltage, the nanoporous layer 117 in contact with the test fluid (i.e., maltose -No blocking layer) , G Minimum current density (sensitivity) for the radio is 10nA / mMcm 2 A higher level of glucose-oxidation current (current caused by the oxidation of glucose alone) is required to generate this current. According to an embodiment, the same nanoporous layer 117 without the maltose-blocking layer generates a similar level of current (i.e., 10 nA / mMcm) at steady state with an applied bias voltage of 0.2-0.45 V in a test fluid containing maltose at a concentration of 4-20 mM (the same as the glucose concentration above). 2 (higher) would be generated.

[0164] Porosity of maltose-blocking layers as a function of current density for glucose and maltose According to an embodiment, the maltose blocking layer 301 prevents glucose from migrating therethrough. The porosity is sufficient to allow the glucose to flow through the electrode, so that the glucose oxidation current is still higher than the minimum current density for glucose. When a switching voltage was applied in a test fluid having a glucose concentration of 4-20 mM, The working electrode 103NE having the maltose blocking layer 301 is a glucose oxidizer. current of, Minimum current density (sensitivity) for glucose is 10nA / mMcm 2On the other hand, the maltose blocking layer 301 has a porosity that effectively blocks maltose from passing therethrough, so that at steady state, a bias voltage of 0.2-0.45 V is applied in test fluids having maltose concentrations of 4-20 mM, and the current caused by maltose alone (maltose-oxidation current) is 0.01-0.02 V. teeth, Maximum current density for maltose using a maltose-blocking layer is 5nA / mMcm 2 It is at a lower level.

[0165] Electrochemical polymerization The porous polymer material for the maltose-blocking layer 301 can be formed on the nanoporous layer 117 by electrochemical polymerization (electropolymerization) using cyclic voltammetry techniques. In an embodiment, the working electrode containing the nanoporous layer is immersed in a reaction mixture solution containing a monomer for cyclic voltammetry electrochemical polymerization. By applying a bias voltage between the working electrode and the reference electrode within the range of the oxidation voltage of the monomer, polymerization occurs and a polymer layer is formed on the nanoporous layer. For further details on the polymerization of phenylenediamine, see “Electropolymerization of O-Phenylenediamine on Pt-Electrode from Aqueous Acidic Solution: Kinetics, Mechanism, Electrochemical Studies and Characterization of the Polymer Obtained”, Sayyah et al, Journal of Applied Polymer Science, Vol. 112, No. 6, 3695-3706 (2009), and “Electropolymerization of P-Phenylenediamine on Pt-Electrode from Aqueous Acidic Solution: Kinetics, Mechanism, Electrochemical Studies, and Characterization of the Polymer Obtained”, Sayyah et al, Journal of Applied Polymer Science, Vol. 117, Issue 2, 943-952 (2010), each of which is hereby incorporated by reference herein.

[0166] Application of oxidation voltage The bias voltage can be varied during cyclic voltammetry. For example, but not limited to, the bias voltage can be gradually increased within the oxidation voltage range during a first time segment and then gradually decreased within the oxidation voltage range during the next time segment. For phenylenediamine, the bias voltage is applied at 0.5V to 1.0V. Figure 22 shows an example of scanning the bias voltage during cyclic voltammetric electrochemical polymerization of phenylenediamine.

[0167] Bias voltage scanning speed The scanning rate of the bias voltage between the lower and upper limits of the oxidation voltage range, together with the concentration of the monomer described below, can be related to the porosity and thickness of the resulting polymer layer. In embodiments, the scanning rate is about 0.5, 1, 2, 4, 6, 8, 10, 15, 20, 25, 30, 40, 50, 60, 70, 80, 90, 100, 120, 140, 160, 180, 200, 220, 240, 260, 280, 300, 350, or 400 mV / sec. In embodiments, the scanning rate can be within a range formed by selecting any two numbers listed in the immediately preceding sentence, for example, from about 5 mV / sec to about 200 mV / sec.

[0168] Monomer concentration The concentration of the monomer is about 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.2, 1.4, 1.6, 1.8, 2.0, 2.2, 2.4, 2.6, 2.8, 3.0, 3.2, 3.4, 3.6, 3.8, 4.0, 4.2, 4.4, 4.6, 4.8, 5.0, 5.2, 5.4, 5.6, 5.8, 6.0, 6.2, 6.4, 6.6, 6.8, 7.0, 7.2, 7.4, 7.6, 7.8, 8.0, 8.2, 8.4, 8.6, 8.8, 9.0, 9.2, 9.4, 9.6, 9.8 or 10 mM. In embodiments, the concentration of the monomer may be within the range formed by selecting any two numbers recited in the immediately preceding sentence, e.g., from about 0.05 mM to about 0.8 mM, from about 1.0 mM to about 5.0 mM, etc. The foregoing concentrations are applicable to the three phenylenediamines.

[0169] Porosity considering monomer concentration The concentration of the monomer in the reaction mixture solution determines the amount of maltose blocking layer that is obtained. The flow chart for manufacturing the maltose-blocking layer in FIG. In this process, the monomer concentration is first determined in step 2401 and polymerization is carried out in step 2403. In embodiments, less than about 0.7 mM, about 0.6 mM, or about 0.5 mM monomer. The concentration can provide a desired level of overall porosity for the maltose-blocking layer. In embodiments, the monomer concentration is about 0.7 mM, about 0.8 mM, about 0.9 mM, about 1.0 mM M, about 1.1 mM, or about 1.2 mM, the resulting polymer layer does not have sufficient porosity to allow the course to pass therethrough, i.e. , G Minimum current density (sensitivity) for the radio is 10nA / mMcm 2 The resulting polymer layer is subjected to treatment to adjust its porosity, at step 2405.

[0170] Electric shock to adjust porosity If the overall porosity of the polymer layer 302 is not at a desired level, the polymer layer may be further processed to adjust the porosity. For example, the polymer layer may be subjected to an electric shock. In an embodiment, an electric shock may be applied to the polymer layer 302 using a chronoamperometric setup as shown in FIG. 23, where an electric shock electrode 309 and a nanoporous layer 1 are connected to each other. The polymer layer 302 formed on substrate 17 is submerged in electrolyte solution 311. A voltage source 305 and switch 307 are connected between substrate 303 and electroshock electrode 309. Operation of switch 307 causes current to flow through porous polymer layer 302, causing a morphological change that increases the porosity of polymer layer 302. As a result, polymer layer 302 becomes a maltose-blocking layer 301 with a desired level of porosity that allows glucose to pass through its thickness while effectively blocking maltose from passing therethrough.

[0171] Acid solution The electrolyte solution for the electric shock may be, but is not limited to, an acidic solution having a pH of less than about 2, 3, or 4. In some embodiments, the acidic solution may include at least one acid. Non-limiting examples of acids for the acidic solution include phosphoric acid (H 3 PO 4 ), nitric acid (HNO 3 ), chloric acid (HCl), formic acid, lactic acid, malic acid, citric acid, carbonic acid, sulfonic acid, etc.

[0172] Shock Waveforms The potential may be applied in a variety of waveforms. In embodiments, the potential is applied in AC or DC. In embodiments, the potential is applied in multiple pulses or a single pulse. In embodiments, the potential may be applied in other shapes of voltage signals.

[0173] Shock potential The potential applied to the polymer layer 302 is about 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, or 4.0 V. In embodiments, the maximum voltage may be within a range formed by selecting any two numbers recited in the immediately preceding sentence, e.g., from about 0.5 to about 2.5 V, from about 1.0 to about 2.0 V, etc.

[0174] Duration for electric shock The duration of application of the potential is between about 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, or 4.5 seconds. In embodiments, the duration may be within a range formed by selecting any two numbers recited in the immediately preceding sentence, such as, for example, between about 0.5 and about 2.5 seconds, between about 1.0 and about 2.0 seconds, etc.

[0175] Maltose-blocking layer also applicable to enzyme sensing In an embodiment, the maltose-blocking layer 301 may be applied to an enzymatic glucose sensing system. Referring back to FIG. 2, the maltose-blocking layer 301 may be added as an additional functional layer 112 on the enzyme layer 111, where maltose is blocked and glucose can pass through.

[0176] CGM working electrode CGM system A continuous glucose monitoring (CGM) system includes glucose sensing electrodes that are in in vivo contact with a subject's biological fluid for measuring the glucose levels contained therein. In practice, the CGM electrodes are inserted or implanted into the subject's body for measurements over an extended period of time, such as days, a week, weeks or months.

[0177] Non-enzymatic CGM working electrode 31 shows a cross-section of a non-enzymatic CGM working electrode 501 according to one embodiment. The illustrated CGM working electrode 501 has a laminated structure including a base 503, a conductive layer 110, a nanoporous layer 117, a maltose-blocking layer 301, an electrolyte ion-blocking layer 505, and a biocompatible layer 507.

[0178] Electrode Base The base, base substrate or electrode base 503 provides support for the laminate structure of the CGM working electrode 501. In embodiments, the base 503 is an electrically insulating layer and may be made from or include materials such as, but not limited to, polyimide, polypropylene, polyethylene glycol, polyhydroxyethyl methacrylate (pHEMA) and other biocompatible polymers. In embodiments, the base 503 may be in the form of a flexible film of an electrically insulating and biocompatible material. The base 503 has a thickness ranging from, but not limited to, about 30 μm to about 200 μm. The base 503 is an optional layer for the CMG sensing electrode 501 and may be omitted in some embodiments.

[0179] Conductive layer The conductive layer 110 may be disposed on the base 503 with or without an intervening layer therebetween. In embodiments, the conductive layer 110 is formed by, but is not limited to, printing or dispensing a conductive or semiconductive material on the base 503. In the CGM working electrode 501, the conductive layer 110 may have a thickness in the range of about 100 nm to 100 μm, but is not limited to such. In some embodiments, the conductive layer 119 may include two or more sublayers of conductive or semiconductive material. In embodiments where the base 503 is omitted, the conductive layer 119 may function as a support for the laminated structure above it.

[0180] Nanoporous Layer A nanoporous layer 117 may be formed on the conductive layer 110. In the CGM working electrode 501, the nanoporous layer 117 has a thickness ranging from about 500 nm to about 10 μm, but is not limited to such. The nanoporous layer 117 may have at least one of a clustered morphology, a non-clustered morphology, a hexagonal nanostructure, or other nanoporous morphology.

[0181] Maltose-blocking layer The maltose-blocking layer 301 can be formed on the nanoporous layer 117 to block maltose molecules from reaching the underlying nanoporous layer 117 but allow glucose molecules to pass therethrough. In an embodiment, the maltose-blocking layer 301 includes a polymeric material such as poly-PD having nano-sized pores to allow glucose molecules to pass therethrough and not allow maltose molecules to pass therethrough. The maltose-blocking layer can have a thickness ranging from about 5 nm to about 40 nm, but is not limited thereto. The maltose-blocking layer 301 is an optional layer for the CMG sensing electrode 501 and can be omitted in some embodiments.

[0182] Electrolyte ion-blocking layer (electrode conditioning enhancement / promotion layer) The electrolyte ion-blocking layer 505 is a layer that blocks small electrolyte ions, such as Na + , K + , Ca 2+ , Cl - , P.O. 4 3- and CO 3 2- The electrolyte ion-blocking layer 505 effectively restricts or prevents the passage of ions therethrough or diffusing toward the underlying nano-porous layer 117. As described below, the electrolyte ion-blocking layer 505 enhances the conditioning of the CGM working electrode and is also referred to as a working electrode conditioning enhancement or promotion layer. The electrolyte ion-blocking layer 505 is porous, so that glucose molecules can freely pass therethrough. When implemented, the electrolyte ion-blocking layer 505 is porous to allow the glucose molecules to pass freely through the test fluid. It is hydrophobic so that it does not swell readily upon absorbing water. The electrolyte ion-blocking layer 505 may have a thickness ranging from about 0.1 μm to about 10 μm, but is not limited thereto.

[0183] Materials for Electrolyte Ion-Blocking Layers The electrolyte ion-blocking layer 505 can include or be made of, for example, at least one of poly(methyl methacrylate) (PMMA), poly(hydroxyethyl methacrylate) (PHEMA), and poly(methyl methacrylate-co-ethylene glycol dimethacrylate) (PMMA-EG-PMMA). The electrolyte ion-blocking layer 505 can also be formed from or can additionally include, a copolymer of methyl methacrylate and butyl methacrylate, and a polymer resulting from polymerization of one or more monomers including methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, pentyl methacrylate, hexyl methacrylate, cyclohexyl methacrylate, 2-ethylhexyl methacrylate, methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, pentyl acrylate, hexyl acrylate, cyclohexyl acrylate, 2-ethylhexyl acrylate.

[0184] Biocompatible Layer When the CGM sensor is implanted or inserted into the subject's body, the biocompatible or biologically protective layer 507 contacts the subject's tissues and bodily fluids. The biocompatible layer 507 includes at least one biocompatible material that is not toxic to the subject's tissues and does not cause immune rejection by the subject's body. The at least one material of the biocompatible layer 507 must also allow bodily fluids to pass therethrough to reach the underlying nanoporous layer 117 such that the sensing of glucose concentration is not significantly impaired by its presence. The biocompatible layer 507 may have a thickness ranging from about 5 μm to about 30 μm, but is not limited thereto.

[0185] Materials for the biocompatible layer The biocompatible layer 507 can include or be fabricated from, for example, at least one of poly(vinyl alcohol), poly(ethylene oxide-co-propylene oxide) (PEO-PPO), poly(ethylene oxide) (PEO), poly(sulfone) (PS), poly(ethylene terephthalate) (PET), poly(ether-urethane) (PU), poly(dimethylsiloxane) (PDMS), ethylene-co-vinyl acetate (EVA), poly(methyl methacrylate), poly(tetrafluoroethylene) (PTFE), poly(propylene) (PP), poly(ethylene) (PE), polyethylene glycol, and polyhydroxyethyl methacrylate (pHEMA).

[0186] Modifications The CGM working electrode 501 may include one or more additional functional layers, not shown in Figure 31. In some embodiments, one or more of the maltose-blocking layer 301, the electrolyte ion-blocking layer 505, and the biocompatible layer 507 may be omitted. In other embodiments, two or more of the maltose-blocking layer 301, the electrolyte ion-blocking layer 505, and the biocompatible layer 507 may be combined into one layer, or their positions may be changed.

[0187] No enzyme layer The CGM working electrode 501 does not contain an enzyme layer that contains a glucose-specific enzyme. The CGM working electrode 501 does not contain such an enzyme in any of the layers.

[0188] No oxygen-absorbing layer The CGM working electrode 501 does not include an oxygen-capturing material or layer that would be required to collect and supply molecular oxygen if glucose oxidase were used for the oxidation of glucose.

[0189] No electron carrier The CGM working electrode 501 does not contain an electron transfer material that would be required to transfer electrons if glucose dehydrogenase were used to oxidize glucose.

[0190] Conditioning the CGM working electrode or system Current Transient Signal When an electrochemical cell using a CGM working electrode is constructed with the application of a bias voltage, the CGM working electrode generates a current. The current from the CGM working electrode represents the sum of the background noise at the CGM working electrode and the current from glucose oxidation. Initially, the current exhibits a transient behavior. As shown in Figures 25-30, initially, the current is very high compared to that caused by glucose oxidation alone and decreases rapidly. Thereafter, the rate of decrease slows. Eventually, the current settles down to a certain level, i.e., a steady state, but in vivo, the current may fluctuate slightly within an acceptable range.

[0191] Current for glucose sensing For accurate glucose sensing, the current must be measured when the electrochemical cell and / or the CGM working electrode are in a steady state. In other words, the current from the CGM working electrode should not change significantly with time (i.e., settle at a certain level after an initial decrease) if the glucose concentration does not change. Furthermore, for accurate glucose sensing, the background current (noise) should not be too high compared to the current caused by glucose oxidation alone. In other words, the total current should not be too high compared to the current resulting from glucose oxidation alone.

[0192] Conditioning the CGM working electrode or electrochemical cell The CGM working electrode requires conditioning before glucose sensing. Here, conditioning refers to the process of stabilizing the CGM working electrode for accurate glucose sensing. Once conditioning of the CGM working electrode is completed, the current from it should settle at a certain level, which should not be too high compared to the glucose-derived current. To provide an accurate glucose level, the CGM system must use the current measured after conditioning is completed. Conditioning of the CGM working electrode can take a long time. Commercially available enzymatic CGM working electrodes require several hours to several days for conditioning.

[0193] Desired rate of change of current Assuming that the current from glucose oxidation in vivo is about tens of nanoamperes, for accurate glucose sensing, the rate of decrease of the current from the CGM working electrode must be, for example, less than 20nA (nanoamperes) per minute. To provide a reference point, the desired rate of change of current should be 20, 19, 18, 17, 16, 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, 4, 3 or 2nA or less per minute. In embodiments, the rate of change of current can be determined at shorter or longer periods.

[0194] Desired level of current The current resulting from glucose oxidation in vivo is typically in the tens of nanoamperes. The desired level of total current may vary depending on a variety of factors, including measurement accuracy, signal processing capabilities, data throughput, etc. As these factors are further developed, the desired level will increase. It may be possible. Nevertheless, assuming that the current from glucose oxidation in vivo is about tens of nanoamperes, for accurate glucose sensing, the current from the CGM working electrode must be, for example, less than 500 nA. To provide a reference point, the desired current should be 500, 490, 480, 470, 460, 450, 440, 430, 420, 410, 400, 390, 380, 370, 360, 350, 340, 330, 320, 310, 300, 290, 280, 270, 260, 250, 240, 230, 220, 210, 200, 190, 180, 170, 160, 150, 140, 130, 120, 110 or 100 nA or less.

[0195] Conditioning complete The CGM system determines that conditioning of the CGM working electrode or its electrochemical cell is complete. The CGM system may determine conditioning completion when the current change rate is at or below or remains at a predetermined value, e.g., the desired current change or decrease rate specified above. The CGM system may determine conditioning completion when the total current change remains at or below a predetermined value, e.g., the desired current level specified above, for a predefined time. The CGM system may determine conditioning completion when the current change rate is at or below or remains at a predefined value, and further when the total current change remains at or below the predetermined value for a predefined time, e.g., when the current change rate is less than 5 nA / min and the total current remains less than 400 nA for 1 min.

[0196] Conditioning completion notification The CGM system can notify the user of the completion of conditioning. Upon forming, or some time after forming, an electrochemical cell for glucose oxidation, the CGM system can begin monitoring the current from the CGM working electrode. When the current meets one or more requirements for the completion of conditioning, the CGM system can provide a notification to the user to notify the completion of conditioning. The notification can be in any form, including sound, vibration, light, or information display. Additionally or alternatively, the CGM system cannot provide information indicative of glucose levels prior to the completion of conditioning.

[0197] Reducing the time for conditioning the CGM working electrode Concentration discontinuities of small electrolyte ions Human body fluids contain significant amounts of Na + , K + , Ca 2+ , Cl - , P.O. 4 3 - and CO 3 2- In an embodiment, the electrolyte ion-blocking layer 505 contains Na + , K + , Ca 2+ , Cl - , P.O. 4 3 - and CO 3 2- 32 conceptually illustrates the concentration discontinuity on either side of the electrolyte ion-blocking layer 505. With the electrolyte ion-blocking layer 505, the total concentration of small electrolyte ions is significantly less in the nanoporous layer 117 than in the biocompatible layer 507. Without the electrolyte ion-blocking layer 505, the total concentration of small electrolyte ions in the nanoporous layer 117 would be similar to that in the biocompatible layer 507.

[0198] Electrolyte ions - Concentration of small electrolyte ions beneath the blocking layer In embodiments, the total concentration of electrolyte ions below the electrolyte ion-blocking layer 505 is greater than 0% but less than about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20% of the total concentration of the same electrolyte ions above the electrolyte ion-blocking layer 505. The total concentration below the electrolyte ion-blocking layer 505 can be selected by selecting any two numbers (two percentage values) listed in the immediately preceding sentence. 32, for example, the total concentration of electrolyte ions in human interstitial fluid (i.e., above the electrolyte ion-blocking layer 505) is about 0.1 M or greater; in contrast, the total concentration of electrolyte ions below the electrolyte ion-blocking layer 505 is about 0.01 M or less. The total concentration of electrolyte ions below the electrolyte ion-blocking layer 505 can be determined by measuring the double layer capacitance of the nano-porous layer 117 and comparing the measurements to the Ionic Strength-Controlled Virtual It can be obtained by applying the Gouy-Chapman equation as described in detail in Area of ​​Mesoporous Platinum Electrode, Boo et al, J. AM. CHEM. Soc. 2004, 126, 4524-4525.

[0199] Acceleration of ionic equilibria in nanoporous layers As described, the ion-blocking layer 505 establishes or creates a substantial discontinuity in the total concentration of small electrolyte ions between above the electrolyte ion-blocking layer 505 and below the same layer. A low concentration of small electrolyte ions is significantly better for conditioning the CGM working electrode 501, and in particular for conditioning the nanoporous layer 117. Although no aspect of the invention is bound by any theory or belief, a low concentration of small electrolyte ions can accelerate ionic equilibrium in the nano-sized structures and surfaces of the nanoporous layer 117 that would not occur at larger scales, such as micro-sized structures and surfaces. As ionic equilibrium is accelerated in the nanoporous layer 117, the time to reach ionic equilibrium or steady state inside the nanostructures of the nanoporous layer 117 will be shorter with the presence of the electrolyte ion-blocking layer 505 at lower concentrations of electrolyte ions than at higher concentrations without the electrolyte ion-blocking layer 505.

[0200] Significantly shorter time for conditioning With the acceleration of ionic equilibrium in the nano-porous layer 117, the electrolyte ion-blocking layer 505 significantly enhances and accelerates the conditioning of the non-enzymatic CGM working electrode 501 of Figure 31, i.e., shortens the time to reach a desired current and / or a desired rate of current change, i.e., a steady state. According to an embodiment, less time is required for completion of conditioning when using a non-enzymatic CGM working electrode 505 having an electrolyte ion-blocking layer 505 compared to using the same non-enzymatic CGM working electrode without the electrolyte ion-blocking layer 505.

[0201] Conditioning Time If the desired rate of current change is 5 nA / min or less, a non-enzymatic CGM working electrode without an electrolyte ion-blocking layer 505 takes about 3 hours in serum containing 0.1 M or more electrolyte ions; in contrast, a non-enzymatic CGM working electrode with an electrolyte ion-blocking layer 505 takes about 1 hour 30 minutes, 1 hour 25 minutes, 1 hour 20 minutes, 1 hour 15 minutes, 1 hour 10 minutes, 1 hour 5 minutes, 1 hour, 55 minutes, 50 minutes, 45 minutes, 40 minutes, 35 minutes, or 30 minutes or less in the same serum. When the desired rate of current change is 3 nA / min or less, a non-enzymatic CGM working electrode without an electrolyte ion-blocking layer 505 takes more than 5 hours in serum containing 0.1 M or more electrolyte ions; in contrast, a non-enzymatic CGM working electrode with an electrolyte ion-blocking layer 505 takes about 1 hour 30 minutes, 1 hour 25 minutes, 1 hour 20 minutes, 1 hour 15 minutes, 1 hour 10 minutes, 1 hour 5 minutes, 1 hour, 55 minutes, 50 minutes, 45 minutes, 40 minutes, 35 minutes, 30 minutes, 25 minutes, 15 minutes, or 10 minutes or less in the same serum. When the desired rate of current change is 2 nA / min or less, a non-enzymatic CGM working electrode without an electrolyte ion-blocking layer 505 takes more than 5 or 10 hours in serum containing electrolyte ions at 0.1 M or more; in contrast, a non-enzymatic CGM working electrode with an electrolyte ion-blocking layer 505 takes about 1 hour 30 minutes, 1 hour 25 minutes, 1 hour 20 minutes, 1 hour 15 minutes, 1 hour 10 minutes, 1 hour 5 minutes, 1 hour, 55 minutes, 50 minutes, 45 minutes, 40 minutes, 35 minutes, 30 minutes, 25 minutes, 40 minutes, 5 ... It will take minutes, 15 minutes or even 10 minutes or less.

[0202] Unexpected results Without proper conditioning, the CGM working electrode cannot provide a current for accurate glucose levels. Reducing the time for conditioning is a very important practical consideration when developing and manufacturing a CGM working electrode. This is because proper conditioning of a CGM working electrode can take hours, if not tens of minutes, and because people tend to want to know their glucose levels immediately after inserting the electrode into their body. With reference to the examples described later, the time for conditioning a CGM working electrode is reduced from about 3, 5 or 10 hours to less than 30 minutes by simply including the electrolyte ion-blocking layer 505, all other conditions remaining the same. This is a very significant improvement and an unexpectedly high achievement.

[0203] Electrolyte ion-blocking layer details The electrolyte ion-blocking layer 505 of the non-enzymatic CGM working electrode includes or is fabricated from at least one porous hydrophobic polymer including poly(methyl methacrylate) (PMMA), poly(hydroxyethyl methacrylate) (PHEMA), and poly(methyl methacrylate-co-ethylene glycol dimethacrylate) (PMMA-EG-PMMA). Additional examples of porous hydrophobic polymers include copolymers of methyl methacrylate and butyl methacrylate, and polymers derived from polymerization of one or more monomers including methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, pentyl methacrylate, hexyl methacrylate, cyclohexyl methacrylate, 2-ethylhexyl methacrylate, methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, pentyl acrylate, hexyl acrylate, cyclohexyl acrylate, 2-ethylhexyl acrylate, and the like. The average molecular weights for these polymers are about 5,000, 10,000, 20,000, 30,000, 40,000, 50,000, 60,000, 70,000, 80,000, 90,000, 100,000, 110,000, 120,000, 130,000, 140,000, 150,000, 160,000, 170,000, 180,000, 190,000, In an embodiment, the molecular weight may be within a range formed by selecting any two numbers recited in the immediately preceding sentence. The electrolyte ion-blocking layer can have a thickness of about 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5 or 10 μm.In embodiments, the thickness may be within a range formed by selecting any two numbers (two thickness values) recited in the immediately preceding sentence, e.g., a range of about 2 to about 5 μm, about 1 to about 3 μm, etc.

[0204] Dropping ion concentration has no effect on enzymatic glucose-sensing electrodes. In an enzymatic CGM system, the CGM working electrode includes a glucose-specific enzyme for the oxidation of glucose molecules. The enzymatic CGM working electrode may include a functional layer containing a porous hydrophobic material that can effectively drop the concentration of electrolyte ions under the functional layer. However, in an enzymatic CGM system, the concentration drop by the functional layer cannot provide a reduction in time for conditioning the CGM electrode for ionic equilibrium in the nano-sized surface or structure. This is because the enzymatic CGM system uses enzymes to oxidize glucose molecules and does not require a nano-porous layer for glucose oxidation. Therefore, even if a porous hydrophobic layer is included in the enzymatic CGM working electrode, such a layer will not be able to be used for a long time due to its thickness. Even if this causes a discontinuity in electrolyte ion concentration across the thickness, and even if there is some reduction in the time for conditioning of the enzymatic CGM working electrode, such reduction would not be equal to the reduction in the time for conditioning in the non-enzymatic CGM working electrode 501 having both an electrolyte ion blocking layer 505 and a nanoporous layer 117.

[0205] CGM Subcutaneous Electrode Module CGM electrode unit In an embodiment, the CGM system includes an electrode unit or module that is in subcutaneous contact with the subject's bodily fluids. The electrode unit may include a unitary body that houses one or more electrodes that contact the bodily fluids when inserted into the subject's body. The unitary body may be flexible.

[0206] Configuration of CGM electrode unit FIG. 33 shows a CGM electrode unit 701 according to one embodiment. The CGM electrode unit 701 includes a subcutaneous portion 703 and a contact terminal portion 705. The subcutaneous portion 703 is for insertion into the subject's body and includes a working electrode 501, a counter electrode 105, and a reference electrode 106 exposed through an opening formed through an insulating layer 707 for subcutaneous contact with bodily fluids. The contact terminal portion 705 is for remaining outside the subject's body and for engaging or connecting with a corresponding device. The contact terminal portion 703 includes a working electrode terminal 501T, a counter electrode terminal 105T, and a reference electrode terminal 106T electrically connected to the working electrode 501, the counter electrode 105, and the reference electrode 106, respectively, under the insulating layer 707. Here, each of the working electrode 501, the counter electrode 105, and the reference electrode 106 may have, but is not limited to, the features and characteristics described in this disclosure.

[0207] Fabrication of CGM electrode unit FIG. 34 is a flow chart for making a CGM electrode unit 701, according to one embodiment. In step 3401, an electrically insulating, flexible film is provided for a base or electrode base 503 (also shown in FIG. 31). Then, in step 3403, a conductive layer is formed on the base 503 in predetermined shapes 110R, 110W and 110C, as shown in FIG. 35. Then, as step 3405, an insulating film 707 is applied on the conductive layer, selectively exposing portions or areas of the conductive layer, as in FIG. 36. Then, in step 3407, the intermediate product is cut, providing the shape shown in FIG. 37. In step 3409, a nano-porous layer 117 is formed on the exposed areas for the working electrode 501. Then, in 3411, one or more functional layers are formed on the nano-porous layer 117, providing the stacked configuration of the non-enzymatic CGM working electrode 501, as in FIG. 31. Additionally, a salt layer may be formed on the exposed area for the reference electrode 106. In an embodiment, cleavage of the intermediate product in step 3407 may be performed after steps 3409 or 3411.

[0208] Conductive layer - multiple conductive elements 35 provides a top view of an intermediate product after step 3403 and its cross section taken along the arrow direction about line 3501 according to one embodiment. As shown, the conductive layer formed on the base 503 has three separate elements 110C, 110W and 110R of predetermined shapes, namely, a conductive layer element 110C for a counter electrode, a conductive layer element 110W for a working electrode, and a conductive layer element 110R for a reference electrode. Each of the conductive layer elements 110C, 110W and 110R includes a conductive portion reserved for a contact terminal (at the contact terminal portion 705 in FIG. 33), a conductive portion reserved for an electrode (at the subcutaneous portion 703 in FIG. 33), and a conductive connection between the two conductive portions.

[0209] Fabrication of the conductive layer The conductive layer may be a single layer of conductive material or may be formed from multiple sublayers of different conductive materials. In an embodiment, either or both of the conductive layer element 110C for the counter electrode and the conductive layer element 110W for the working electrode are formed with at least two sublayers, for example, a silver layer and a conductive carbon layer on the silver layer. In an embodiment, the conductive layer element 110R for the reference electrode is formed with a single layer, for example, a silver layer. The conductive layer 110 or its sublayers may be formed by printing a conductive ink on or above the base 503 and then drying. A sublayer formed on another sublayer may also be formed by printing a conductive material for that sublayer. The conductive layer elements 110W, 110C and 110R in FIG. 35 are all single layer; however, for purposes of illustrating alternatives, in FIGS. 36-38, the conductive layer elements 110W and 110C have a two-sublayer configuration, i.e., a carbon layer 1605 above a silver layer 1603 (see also FIG. 16A).

[0210] Insulating Film Fig. 36 shows an intermediate product after placing an insulating film according to an embodiment. The insulating film 707 may be pre-cut with openings in the subcutaneous area 703 of Fig. 33 to expose the conductive parts reserved for the counter electrode 105, the working electrode 501 and the reference electrode 106. The insulating film 707 does not cover the contact terminal portion 705 of Fig. 33, thus exposing the terminal portion of each of the conductive layer elements 110C, 110W and 110R (which will be 105T, 501T and 106T, respectively). The conductive connections of the conductive layer elements 110C, 110W and 110R are covered with the insulating film 707. An adhesive layer (not shown) may be inserted between the base film 503 and the insulating film 707. The insulating film 707 may be an adhesive coated film.

[0211] Disconnect In step 3407, the intermediate product of FIG. 36 is subjected to cutting, and unnecessary portions of the insulating film 707 and the base 503 are removed, for example, by die cutting. FIG. 37 shows the resulting product, where the contact terminal portion 705 (the proximal end portion of the CGM electrode unit 701) is wider than the subcutaneous portion 703 (the distal end portion of the CGM electrode unit 701). In an embodiment, the distal portion has a width of about 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, or 2.0 mm in a direction along line 3501. In an embodiment, the width may be within a range formed by selecting any two numbers recited in the immediately preceding sentence, for example, from about 1.0 mm to about 1.5 mm. In embodiments, the CGM electrode unit 701 has a length in a direction between its distal and proximal ends of about 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, or 30 mm. In embodiments, the length may be within a range formed by selecting any two numbers recited in the immediately preceding sentence, e.g., from about 10 mm to about 20 mm.

[0212] Formation of nanoporous layer In step 3409, a nanoporous layer 117 is formed on the conductive layer element 110W exposed for the working electrode. FIG. 38A shows a cross section of the intermediate product in the direction of the arrow about line 3501 after forming the nanoporous layer 117. In an embodiment, the nanoporous layer 117 is formed by dispensing a cluster colloid comprising nanoparticle clusters dispersed in a liquid onto the conductive layer 110 and drying the liquid therefrom. In other cases, different forms of the nanoporous layer 117 can be formed using different methods disclosed herein. In some embodiments, the cutting in step 3407 can be performed after the formation of the nanoporous layer 117.

[0213] Functional layer(s) for the working electrode After the nano-porous layer 117 is formed, one or more functional layers are formed on the nano-porous layer 117, as shown in FIG. A non-enzymatic CGM working electrode 501 is provided as in 31. Maltose Blocking Layer 301 may be formed on nanoporous layer 117, but is not limited to this. The resulting blocking layer 505 is CGM Conditioning of the Working Electrode 501 It may be formed on the nano-porous layer 117 for improving the quality of the material. The biocompatible layer 507 is formed on the nanoporous layer 117, more specifically, on the electrolyte ion-blocking layer 117. 38B shows an electrolyte ion-blocking layer 505. A cross section of a CGM working electrode 501 including a bonding layer 505 and a biocompatible layer 507 is shown.

[0214] Reference and Counter Electrodes In an embodiment, a salt layer, e.g., AgCl, may be formed on the exposed conductive layer element 110R for the reference electrode 106. The formation of the salt layer may be performed any time after forming the conductive layer element 110R. In an embodiment, the counter electrode 105 may not require additional processing on the conductive layer element 110C.

[0215] Subcutaneous insertion of the CGM electrode unit In an embodiment, the subcutaneous portion 703 (distal portion) of the CGM electrode unit 701 is inserted subcutaneously into the subject's body with or without the use of an insertion tool known in the art or to be developed in the future. With proper subcutaneous insertion, the working electrode 501, reference electrode 106 and counter electrode 105 of the subcutaneous portion 703 contact the subject's interstitial fluid, while the terminal portion 705 of the CGM electrode unit 701 remains outside the subject's body.

[0216] Supported Devices Thereafter, in embodiments, the terminal portion 705 is engaged or connected to a compatible device (not shown) that includes compatible ports or terminals corresponding to the working electrode terminal 501T, the counter electrode terminal 105T, and the reference electrode terminal 106T. In embodiments, the compatible device further includes electrical circuitry that completes the electrochemical cell of FIG. 1 together with the CGM electrode unit 701 for the continuous monitoring glucose module. In some embodiments, in addition to the electrical circuitry to complete the electrochemical cell, the compatible device may include at least one processor for processing data including the current obtained from the electrochemical cell for conversion to a standardized number representing the glucose level. In some embodiments, the compatible device includes a wireless module for wirelessly transmitting data to another wireless device, such as a smartphone or computing device.

[0217] BGM disposable strip Single Point in Time Device Glucose sensing can be performed in vitro at a single time point. Single time point glucose sensing systems measure glucose levels in a test fluid, most commonly blood. The systems are therefore called blood glucose monitoring (BGM) systems. BGM systems include single-use disposable cartridges or strips.

[0218] Disposable Cartridges 39 shows a BGM disposable cartridge 901 and sensing module 911 for a single-time point glucose sensing system according to an embodiment. The disposable cartridge 901 includes a test fluid reservoir 903, a counter electrode 105, a reference electrode 106, and a cartridge working electrode 905 formed on a base 907 that provides structural support for the electrodes 105, 106, and 905. Electrical connections (not shown) are made between the electrodes and a connector 909 through the base 907.

[0219] Sensing Module In an embodiment, the disposable cartridge 901 includes a sensing module 911 and a connector 90 9. The sensing module 911 may include electrical circuitry (not shown) for the voltage source 109 and the current sensor 108. When the disposable cartridge 901 is properly connected to the sensing module 911, the electrodes 105, 106 and 905 are connected to the circuitry of the sensing module 911, as in FIG.

[0220] working electrode The working electrode 905 according to one embodiment includes a conductive layer 110 and a nanoporous layer 117. The working electrode 905 further includes a filter layer 913 to filter and screen cells, lipids and large molecules contained in the test fluid. In an embodiment, the filter layer 913 may be made of or include woven fabric, cotton or other materials capable of screening cells, lipids and other large components of blood but allowing glucose to pass therethrough.

[0221] Working electrode not included In an embodiment, the working electrode 905 does not include a glucose-specific enzyme. Additionally, the working electrode 905 does not include a surfactant and an electron carrier that may be required in enzymatic glucose sensing. Additionally, given that the working electrode 905 is an in vitro device, it does not require a biocompatible layer.

[0222] Calibration of the working electrode Current from the working electrode According to an embodiment, the non-enzymatic working electrode having a nanoporous glucose-oxidation layer generates a current caused by the oxidation of glucose contained in the test fluid. In practice, the current from the non-enzymatic working electrode includes 1) a current caused only by glucose oxidation (glucose-oxidation current), 2) a current caused by interfering chemical components, if the test fluid contains such interfering chemical components, and 3) a current caused by interactions between the electrochemical cell and other chemical components contained in the test fluid.

[0223] Glucose levels in body fluids Normal glucose levels in healthy individuals are 4.0-6.0 mM (72-108 mg / dL). When considering diabetic patients, glucose levels may range from 4.0-20 mM (72-360 mg / dL).

[0224] Glucose oxidation current In an embodiment, at steady state in a test fluid containing 4.0-20 mM glucose ( After conditioning, when a bias voltage of about 0.2 V to about 0.45 V was applied, a current derived only from glucose oxidation (glucose-oxidation current) was observed. is 1 0nA / mMcm 2 YoIn the glucose concentration range of 4.0-20 mM, the nanoporous glucose-oxidation layer (and thus the non-enzymatic working electrode) generates a glucose-oxidation current of about 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, or 6.0 nA for 1 mM glucose in the test fluid. In embodiments, the glucose-oxidation current from 1 mM glucose in the test fluid may be within the range formed by any two numbers in the immediately preceding sentence, for example, about 1.5 nA to 2.5 nA. Thus, in the glucose concentration range of 4.0-20 mM, the glucose-oxidation current from the non-enzymatic working electrode may be from about 2.0 nA (4.0 x 0.5) to about 120 nA (20 x 6.0). In embodiments, the glucose-oxidation current can be about 2.0, 4.0, 8.0, 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, 30, 32, 34, 36, 38, 40, 42, 44, 46, 48, 50, 52, 54, 56, 58, 60, 62, 64, 66, 68, 70, 72, 74, 76, 78, 80, 82, 84, 86, 88, 90, 92, 94, 96, 98, 100, 102, 104, 106, 108, 110, 112, 114, 116, 118, or 120Na. In embodiments, the glucose-oxidation current from 4.0-20 mM glucose contained in the test fluid may be within the range formed by any two numbers in the immediately preceding sentence, for example, about 1.5 nA to 2.5 nA.

[0225] Calibration of current and glucose concentration In embodiments, for the same glucose concentration in a test fluid, the glucose-oxidation current may be different from one nanoporous glucose-oxidation layer to another depending on their particular manufacturing conditions. Also, for a particular nanoporous glucose-oxidation layer, the glucose-oxidation current generally correlates linearly with the glucose concentration, but may not be so linear over the entire concentration or current range. In embodiments, for each batch of nanoporous glucose-oxidation layers manufactured using the same conditions, one or more nanoporous glucose-oxidation layers are tested and a correlation profile between glucose-oxidation current and glucose concentration is determined for the particular batch. Later in the process of glucose sensing or monitoring using nanoporous glucose-oxidation layers from the same batch, the correlation profile is used in calculating or determining the glucose level in the test fluid.

[0226] Second Working Electrode Ascorbic acid Ascorbic acid, also known as vitamin C, plays an important role in the human body. Ascorbic acid is prone to oxidation and is easily oxidized at low oxidation potentials. Ascorbic acid may interfere with glucose sensing from body fluids.

[0227] Currently there are no layers available to block ascorbic acid Given that ascorbic acid is negatively charged, a negatively charged layer has been proposed to repel ascorbic acid but allow glucose to pass through, however, to date there are no commercially available glucose-sensing electrodes that block ascorbic acid.

[0228] Two working electrodes In an embodiment, the glucose sensor or sensing system includes at least one additional working electrode in addition to the working electrode 103 of Figure 1. Figure 40 conceptually illustrates a two-working electrode glucose sensing system 4101. In this system, a first working electrode 4103A, a second working electrode 4103B, a counter electrode 105 and a reference electrode 106 are connected to a potentiostat 4104, which includes electrical circuitry to function as operational amplifiers 4107A and 4107B, current sensors 4108A and 4108B, and voltage sources 4109A and 4109B for the two working electrodes 4103A and 4103B.

[0229] Operation of the two-working electrode system In an embodiment, oxidation of both glucose and ascorbic acid occurs at the first working electrode 4103A. Thus, the current from the first working electrode 4103A represents the total concentration of glucose and ascorbic acid in the test fluid 102. On the other hand, oxidation of ascorbic acid occurs at the second working electrode 4103B, but not oxidation of glucose. Thus, the current from the second working electrode 4103B represents only the concentration of ascorbic acid in the same test fluid 102. The difference between the two current values ​​represents the concentration or level of glucose contained in the test fluid 102.

[0230] First working electrode (glucose working electrode) In some embodiments, the first working electrode (glucose working electrode) 4103A includes a nanoporous layer 117 on the conductive layer 110, as in FIG. In another embodiment, the first working electrode 4103A may include, but is not limited to, a gated nanoporous structure. In another embodiment, the first working electrode 4103A may include, as in Figure 2, an enzyme layer containing a glucose-specific enzyme for oxidizing glucose, instead of the nanoporous layer 117 of Figure 3. In either embodiment, the first working electrode 4103A does not include a negatively charged membrane or any other membrane to prevent ascorbic acid from passing therethrough.

[0231] Second Working Electrode (Non-Glucose Working Electrode) The second working electrode (non-glucose working electrode) 4103B includes a conductive layer 110, but does not include any layers or features to effectively cause oxidation of glucose. In an embodiment, the second working electrode 4103B does not include a nanoporous layer 117 or a glucose-specific enzyme to oxidize glucose. However, oxidation of ascorbic acid occurs at the conductive layer 110. In an embodiment, the conductive layer 110 includes, but is not limited to, a conductive carbon layer formed on a silver layer.

[0232] Same bias voltage for both electrodes In an embodiment, the same bias voltage is applied to both the first and second working electrodes 4103A and 4103B relative to the reference electrode 106. This is to provide an environment that causes roughly the same level of oxidation of ascorbic acid to occur at both the first and second working electrodes 4103A and 4103B. Assuming that the same level of oxidation of ascorbic acid occurs at each of the first and second working electrodes 4103A and 4103B, the difference between the current from the first working electrode 4103A and the current from the second working electrode 4103B should represent the oxidation of glucose at the first working electrode 4103A.

[0233] Addressing additional chemical interferences The two-electrode system 4101 can be used to address interferences of more than one chemical component. In an embodiment, by adjusting the bias voltage, the first working electrode 4103A can oxidize not only glucose and ascorbic acid, but also additional interfering chemical components, such as acetaminophen. Similarly, the second working electrode 4103B oxidizes not only ascorbic acid, but also the additional interfering chemical components at the same time. Here, neither the first nor the second working electrode includes a membrane to block the additional interfering chemical components. Thus, the current from the first working electrode 4103A represents the oxidation of glucose, ascorbic acid, and acetaminophen, and the current from the second working electrode 4103B represents the oxidation of ascorbic acid and acetaminophen. The difference between the currents represents the oxidation of glucose, and the interferences of acetaminophen and ascorbic acid are cancelled.

[0234] Bias Voltage In embodiments, any bias voltage value in the range of 0.2-0.45 V can be used to address interferences. In some embodiments, bias voltage values ​​in the range of 0.2-0.32 V can be used to address interferences of ascorbic acid only, assuming that acetaminophen cannot be oxidized within the nanoporous metal layer in that bias voltage range, as described in more detail below.

[0235] Different bias voltages In embodiments, the two-electrode system 4101 can employ different bias voltages for the first and second working electrodes. For example, a first bias voltage is applied to the first working electrode 4103A and a second bias voltage is applied to the second working electrode 4103B. With different bias voltages, the current resulting from the oxidation of ascorbic acid at the second working electrode 4103B may not be the same or equivalent to the current component due to the oxidation of ascorbic acid at the first working electrode 4103A. Thus, the current resulting from glucose oxidation may not be a simple difference between the currents from the two electrodes. However, in embodiments, The two-electrode system 4101 has or is connected to hardware and software for calculating accurate glucose concentrations using different bias voltages, current values ​​from the first and second working electrodes 4103A and 4103B, data indicative of the oxidation potential of ascorbic acid at different bias voltages, and the like.

[0236] Simultaneous detection In some embodiments, the detection of current from the first working electrode 4103A and the detection of current from the second working electrode 4103B occur at the same time, simultaneously, in parallel, or concomitantly. In other embodiments, using either one current sensor or two current sensors, the detection can occur at different times with a time gap, as long as the concentration fluctuation of the relevant chemical component is negligible over the time gap. One skilled in the art will recognize how long a time gap is possible without significant risk of inaccuracy. For example, the time gap is less than 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 seconds, or the time gap is less than 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 minutes.

[0237] Recording concentrations of interfering chemicals In embodiments, the two-electrode system 4101 includes or is connected to hardware and software (not shown) configured to store current values ​​from the first and second working electrodes 4103A and 4103B, and / or store individual concentrations of glucose and ascorbic acid derived from the current values. In some embodiments, where oxidation of both ascorbic acid and acetaminophen occurs at the second working electrode 4103B, the hardware and software is configured to store the concentration of glucose as well as the aggregate concentration of ascorbic acid and acetaminophen.

[0238] Applicable to CGM The two-electrode system 4101 can be incorporated into a CGM electrode unit for in vivo glucose sensing. Figure 41 shows a CGM electrode unit 4201 including first and second working electrodes 4103A and 4103B, which are connected to first and second working electrode terminals 4103AT and 4103BT, respectively.

[0239] Applicable to BGM The two-electrode system 4101 may be incorporated into a BGM disposable cartridge or strip for in vitro glucose sensing. In an embodiment, the disposable cartridge 901 of FIG. 39 may include two working electrodes. In such an embodiment, the cartridge working electrode 905 serves as the first working electrode 4103A. The second working electrode 4103B may be added to the base 907 for contacting the test fluid. Additionally, the corresponding sensing module 911 may include circuitry for receiving signals from the first and second working electrodes from the BGM disposable cartridge.

[0240] The first and second working electrodes must work together In a two-electrode system 4101, to obtain the glucose level in the test fluid, there must be two current values: one from the first working electrode 4103A and one from the second working electrode 4103B. In a CGM, each of the first and second working electrodes 4103A and 4103B must operate sequentially or repeatedly to provide the glucose level. Thus, the system is distinguished from any electrochemical sensing system that has a spare sensing electrode that is occasionally used for various reasons.

[0241] Acetaminophen interference Acetaminophen Acetaminophen is one of the most commonly used over-the-counter medications. Additionally, acetaminophen is widely used as an active ingredient in combination drugs.

[0242] Commonly recognized problems Given the popularity of acetaminophen, the drug may be taken by patients who also need to detect their blood glucose levels. Given that many glucose sensing devices are used by the patients themselves, rather than by medical professionals, inaccurate readings caused by acetaminophen could have serious consequences. The electrochemical glucose sensing industry is aware of this problem and has expressed an interest in solving it.

[0243] No good solution Many attempts have been made to solve this problem. However, to date, no solution has been able to convince the industry to adopt it. No membrane has been employed to selectively screen acetaminophen from reaching the electrode. Thus, a long-standing but unmet need exists.

[0244] Explanation for no good solution No commercially available electrochemical glucose sensing technology can easily address this problem at all. This is at least in part because electrochemical glucose sensing systems are technically very complex. The working electrode has stacked components, each of which has its own function and does not interfere with the other components. It would be difficult to find a solution to address this problem involving acetaminophen without affecting the function of the other components and the overall performance of the working electrode. In addition to the complexity of the technology, the development of such a product for market launch would be very costly, given the rigorous regulatory approval process in this industry. Thus, once a viable product is approved and launched on the market, it would be difficult to make significant changes to any of the working components of the approved product.

[0245] A nonenzymatic glucose sensing system for dealing with acetaminophen. In an embodiment, the non-enzymatic electrochemical glucose sensing system selectively oxidizes glucose and simultaneously does not oxidize acetaminophen without introducing an additional membrane to this end. Referring back to Figures 3 and 31, the working electrode 103NE, 501 includes a conductive layer 110 and a nanoporous layer 117. The working electrode may include one or more additional functional layers on the nanoporous layer 117.

[0246] Acetaminophen cleaning membrane not included In an embodiment, the working electrode 103NE does not include a membrane, film, or layer over the nanoporous layer 117 designed to selectively screen, repel, or block acetaminophen but allow glucose to pass therethrough. Thus, when the working electrode 103NE contacts a test fluid containing acetaminophen, both glucose and acetaminophen will contact the nanoporous layer 117 and can enter the nano-sized pores therein for oxidation.

[0247] Bias voltages for the oxidation of glucose and acetaminophen In glucose sensing systems according to embodiments, glucose is oxidized at the nanoporous layer 117 at bias voltages between about 0.2 V and about 0.45 V. On the other hand, acetaminophen is oxidized at bias voltages above 0.33, 0.34, 0.35 or 0.36 V. The bias voltage can be adjusted to cause oxidation of glucose while at the same time avoiding oxidation of acetaminophen.

[0248] Bias voltage for selective oxidation of glucose and no oxidation of acetaminophen In an embodiment, the bias voltage applied to the conductive layer 110 relative to the reference electrode 106 is set to cause oxidation of glucose but not oxidation of acetaminophen when either is in contact with the nanoporous layer 117. For selective oxidation of glucose and selective non-oxidation of acetaminophen, in an embodiment, the bias voltage is set at or about 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, or 0.32 V. In an embodiment, the bias voltage may be within a range formed by selecting any two numbers (two voltage values) recited in the immediately preceding sentence, e.g., 0.28 V to 0.30 V, about 0.27 V to about 0.31 V, 0.26 V to 0.30 V, about 0.28 V to about 0.32 V, etc. In an embodiment, the bias voltage is less than 0.30, 0.31 or 0.32V.

[0249] Bias voltage in enzyme sensing electrodes For comparison, an enzymatic glucose sensor applies a bias voltage in the range of 0.5-0.6 V. In an enzymatic sensing sensor, this bias voltage does not cause oxidation of glucose at the sensing electrode or elsewhere. Rather, the glucose-specific enzyme oxidizes the glucose molecule, which releases electrons for the electron carrier, which is oxidized by the bias voltage at the conductive layer. Thus, the bias voltage causes oxidation of the electron carrier at the enzymatic electrode.

[0250] Working Example Various aspects and features of the invention will now be further described in connection with examples and experiments.

[0251] Preparation of reverse micellar phase Example 1.1 The platinum solution was dissolved in 0.500 g (0.965 mmol) of chloroplatinic acid hexahydrate H 2 PtCl 6 6H 2The platinum solution was prepared by dissolving 24.5 g of purified water with stirring. 25 g of a surfactant, Triton X-100™ (Sigma-Aldrich), was added to the aqueous platinum solution to provide an aqueous composition containing the surfactant and platinum ions. The concentration of platinum ions in the aqueous composition was about 0.02 M. A reverse micellar phase was prepared in the aqueous composition by adjusting the temperature to 70° with stirring.

[0252] Example 1.2 The reverse micelle phase was prepared by adding PtCl 4 6H 2 O to H 2 PtCl 6 6H 2 Prepare the aqueous composition by repeating Example 1.1, except that instead of O, an amount is used which provides a platinum ion concentration of about 0.02M in the aqueous composition.

[0253] Example 1.3 The reverse micellar phase was 2 PtCl 2 (OH) 4 , H 2 PtCl 6 6H 2 Prepare the aqueous composition by repeating Example 1.1, except that instead of O, an amount is used which provides a platinum ion concentration of about 0.02M in the aqueous composition.

[0254] Example 1.4 The reverse micellar phase was 2 Pt(SO 4 )(OH) 4 6H 2 O to H 2 PtCl 6 6H 2 Prepare the aqueous composition by repeating Example 1.1, except that instead of O, an amount is used which provides a platinum ion concentration of about 0.02M in the aqueous composition.

[0255] Example 1.5 The reverse micellar phase was prepared by TiCl4·6H 2 O to H 2 PtCl 6·6H 2 Prepare by repeating Example 1.1, except that it is used in an amount that provides a titanium ion concentration of about 0.02 M in the aqueous composition instead of O.

[0256] Example 1.6 Prepare by repeating Example 1.1, except that the reverse micelle phase is used with NP-40TM as the surfactant instead of Triton X-100, and except that it provides a platinum ion concentration of about 0.02 M in the aqueous composition, and further except that the amount and temperature of the surfactant are adjusted to achieve the reverse micelle phase of the surfactant.

[0257] Example 1.7 Prepare by repeating Example 1.1, except that the reverse micelle phase is used with polysorbate 80 as the surfactant instead of Triton X-100, and except that it provides a platinum ion concentration of about 0.02 M in the aqueous composition, and further except that the amount and temperature of the surfactant are adjusted to achieve the reverse micelle phase of the specific surfactant.

[0258] Example 1.8 Prepare by repeating Example 1.1, except that the reverse micelle phase is used with isocetes-20 as the surfactant instead of Triton X-100, and except that it provides a platinum ion concentration of about 0.02 M in the aqueous composition, and further except that the amount and temperature of the surfactant are adjusted to achieve the reverse micelle phase of the specific surfactant.

[0259] Example 1.9 Prepare by repeating Example 1.1, except that the reverse micelle phase is used with poloxamer 407 as the surfactant instead of Triton X-100, and except that it provides a platinum ion concentration of about 0.02 M in the aqueous composition, and further except that the amount and temperature of the surfactant are adjusted to achieve the reverse micelle phase of the specific surfactant.

[0260] Example 1.10 A reverse micelle phase is prepared by repeating Example 1.1, except that monolaurin is used as the surfactant instead of Triton X-100 to provide a platinum ion concentration of about 0.02 M in the aqueous composition, and further, the amount of surfactant and temperature are adjusted to achieve a reverse micelle phase for the particular surfactant.

[0261] Preparation of reducing agent Example 2.1 A reducing agent solution was prepared by adding 30 g (0.170 mol) of ascorbic acid as a reducing agent to 250 ml of purified water with stirring. The reducing agent solution was heated to 70° C. The concentration of ascorbic acid in the reducing agent solution was 0.6 M, which is 60 times the concentration of the metal ions in Examples 1.1 to 1.10.

[0262] Example 2.2 An aqueous reducing agent solution was prepared by repeating Example 2.1, except that formaldehyde was used as the reducing agent instead of ascorbic acid. The amount of formaldehyde was adjusted to provide its concentration of about 0.6 M in the aqueous reducing agent solution.

[0263] Example 2.3 An aqueous reducing agent solution was prepared by repeating Example 2.1, except that acetic acid was used instead of ascorbic acid as the reducing agent. The amount of acetic acid was adjusted to provide a concentration of about 0.6 M in the aqueous reducing agent solution.

[0264] Example 2.4 An aqueous reducing agent solution was prepared by repeating Example 2.1, except that hypophosphite was used instead of ascorbic acid as the reducing agent. The amount of hypophosphite was adjusted to provide a concentration of about 0.6 M in the aqueous reducing agent solution.

[0265] Formation of nanoparticle colloids Example 3.1 The aqueous solution of reducing agent prepared in Example 2.1 was added to the aqueous composition of Example 1.1 at 70° C. immediately after preparing the reverse micelle phase. In the resulting liquid composition, the concentration of platinum ions was about 0.0028 M and the concentration of ascorbic acid was about 0.50 M. The resulting liquid composition was continuously stirred at 70° C. for about 4 hours. A black platinum colloid was obtained.

[0266] Examples 3.2-3.10 Example 3.1 is repeated using the reverse micellar phases prepared in Examples 1.2-1.10 in place of the reverse micellar phase prepared in Example 1.1. This provides the metal colloids of Examples 3.2-3.10, respectively.

[0267] Particle size analysis of nanoparticle colloids Example 4.1 The Korea Polymer Testing and Research Institute (KOPTRI) performed dynamic light scattering particle size analysis on the platinum colloid obtained from Example 3.1 using a Photal Otsuka Electronics Zeta Potential & Particle Size Analyzer ELS-Z2. In the analysis, a sample of the Example 3.1 platinum colloid was dispersed in purified water and had a refractive index of 1.3328, a viscosity of 0.8878 cp, and a dielectric constant of 78.3 at 25°C.

[0268] FIG. 14 shows the particle size distribution for the colloids obtained from Example 3.1. The particle diameters are primarily between about 9 nm and about 14 nm. This size distribution is interpreted as representing reverse micelles. The size distribution does not show a diameter size of 1-5 nm, which would be interpreted as most platinum nanoparticles being contained or encapsulated inside the reverse micelles. Similar results were obtained from multiple runs of the experiments according to Examples 1.1, 2.1 and 3.1.

[0269] Examples 4.2-4.10 The analysis of Example 4.1 is repeated using each of the colloids prepared in Examples 3.2-3.10 in place of the colloid prepared in Example 3.1. Particle size distributions for each of the colloids prepared in Examples 3.2-3.10 are obtained.

[0270] Removal of surfactants Example 5.1 50ml of 0.3M HCl aqueous solution was added to 60ml of the platinum colloid prepared in Example 3.1. The acid-added platinum colloid was centrifuged at 3800 rpm for 10 minutes. The clear supernatant was then discarded and the black bottom was collected. The sequence of adding HCl aqueous solution, centrifugation and collecting the black bottom was repeated four more times to remove the surfactant and obtain the platinum colloid.

[0271] The resulting platinum colloid was then washed with purified water to remove HCl. 50 ml of purified water was added to the collected platinum colloid. The water-added platinum colloid was centrifuged at 3800 rpm for 10 minutes. The clear supernatant was then discarded and the black bottom was collected. The sequence of adding purified water, centrifugation and collecting the black bottom was repeated four more times to remove HCl and obtain HCl-washed platinum colloid.

[0272] Examples 5.2-5.10 Example 5.1 is repeated using the nanoparticle colloids obtained from Examples 3.2-3.10 in place of the nanoparticle colloids prepared in Example 3.1, and the colloids of Examples 5.2-5.10 are collected, respectively.

[0273] Example 5.11 Example 5.1 was repeated with 0.3 M HNO instead of aqueous HCl. 3 Repeat with the aqueous solution.

[0274] Example 5.12 Example 5.1 is repeated using 0.3 M aqueous NaOH instead of the aqueous HCl.

[0275] Particle size analysis of cluster colloids Example 6.1 Korea Polymer Testing and Research Institute (KOPTRI) performed dynamic light scattering particle size analysis on the platinum colloid obtained from Example 5.1 using a Photal Otsuka Electronics Zeta Potential & Particle Size Analyzer ELS-Z2, similar to Example 4.1. For the analysis, a sample of the Example 5.1 colloid was dispersed in water and had a refractive index of 1.3328, a viscosity of 0.8878 cp, and a dielectric constant of 78.3 at 25°C.

[0276] FIG. 15 shows the particle size distribution for the colloids obtained from Example 5.1. The particle diameters are mainly between about 60 nm and about 200 nm. This size distribution is interpreted as representing irregularly shaped clusters formed from nanoparticles. Considering that the particle sizes in Example 4.1 are mainly between about 9 nm and about 14 nm (the size of the reverse micelles, not the size of the clusters), it is understood that the clusters were formed in the process of Example 5.1, where the surfactant molecules were detached from the platinum nanoparticles by the addition of an acidic solution, and the surfactant was removed by centrifugation and collection at the bottom. Similar results were obtained from multiple runs of the experiments according to Examples 1.1, 2.1, 3.1 and 5.1.

[0277] Examples 6.2-6.10 Example 6.1 is repeated using each of the colloids prepared in Examples 3.2-3.10 in place of the colloid prepared in Example 3.1. Particle size distributions for each of the colloids prepared in Examples 3.2-3.10 are obtained.

[0278] Platinum recovery - yield Example 7 The cluster colloid obtained in Example 5.1 was subjected to drying. The dry weight of the colloid was 0.143 g. The resulting colloid in Example 5.1 was prepared from 60 ml of the nanoparticle colloid prepared in Example 3.1, which contained 0.188 g. In the overall process, the platinum yield was 76.1%.

[0279] Fabrication of electrodes using clustered nanoporous layers Example 8.1 - Electrode Base As shown in FIG. 16A, a silver layer 1603 and a conductive carbon layer 1605 were formed on a polyimide substrate 1601. The silver layer 1603 was formed to a thickness of about 20 μm by printing a silver ink containing silver particles. The conductive carbon layer 1605 was formed to a thickness of about 20 μm by printing a carbon ink containing carbon particles. A polyimide insulating film 1602 was laminated on the substrate 1601 around the silver layer 1603 and the conductive carbon layer 1605 to form a conductive layer. Polar base 1606 provided.

[0280] Example 8.2 - Formation of a nanoporous layer The cluster colloid obtained in Example 5.1 was diluted to a concentration of 60 mg / ml. Using a microsyringe, 0.2 μL of the diluted cluster colloid was dropped onto the conductive carbon layer of the electrode base 1606. The electrode base with the colloid dropped onto it was placed in a 60° C. oven for 30 minutes to form an electrode 1607 including a platinum nanoporous layer 1609 as shown in FIG. 16B.

[0281] Example 8.3 - Roughness factor The electrochemical cell of FIG. 1 was prepared using a CH Instruments Inc. electrochemical analyzer CHI660 as the potentiostat 104, and using the electrode 1607 prepared in Example 8.2 as the working electrode 103, a platinum wire as the counter electrode 105, and Ag / AgCl (3M KCl) as the reference electrode 106. The silver layer 1603 of the electrode 1607 was connected to the potentiostat 104. 1M H 2 SO 4The aqueous solution was added to the electrochemical cell shown in FIG.

[0282] Cyclic voltammetry was performed using a potential sweep from -0.2 V to +1.2 V. The actual surface area of ​​the platinum nanoporous layer was obtained by measuring the amount of protons adsorbed on the surface of the platinum nanoporous layer using cyclic voltammetry. The top surface area (geometric area) of the platinum nanoporous layer was measured. The roughness factor was calculated by dividing the actual surface area by the geometric area. The roughness factor of the nanoporous layer obtained from Example 8.2 was 1147.

[0283] Example 8.4 - Repeat of Examples 8.1-8.2 Example 8.1 was repeated multiple times to prepare additional electrode bases. Example 8.2 was repeated multiple times using additional electrode bases to prepare additional electrodes 1607 including a platinum nanoporous layer 1609.

[0284] Example 8.5 - Repeat of Example 8.3 Example 8.3 was repeated for the five electrodes 1607 prepared in Example 8.4. The roughness factor values ​​of the nanoporous layers were 1187, 1171, 1143, 1190 and 1119.

[0285] Example 8.6 - SEM Photo Figure 17A is an SEM photograph taken from the top of electrode 1607 obtained from Example 8.4. The darker center represents the area of ​​the conductive carbon layer. Figure 17B is an SEM photograph of a cross section of electrode 1607 showing, from top to bottom, platinum nanoporous layer 1609, carbon conductive layer 1605, and silver layer 1603. Figure 17C includes three SEM photographs of another electrode 1607 prepared in Example 8.4. The three photographs were taken from the top at different magnifications.

[0286] Glucose sensing in PBS Example 9.1 - Preparation of Solutions of Glucose and Other Test Materials D-(+)-glucose powder purchased from Sigma-Aldrich was dissolved in purified water to prepare a 1M glucose stock solution. Ascorbic acid purchased from Sigma-Aldrich was dissolved in purified water to prepare a 0.05M ascorbic acid aqueous solution. Acetaminophen purchased from Sigma-Aldrich was dissolved in purified water to prepare a 0.05M acetaminophen aqueous solution. Maltose purchased from Sigma-Aldrich was dissolved in purified water to prepare a 0.5M maltose aqueous solution.

[0287] Example 9.2 - Preparation of PBS 0.1M NaH in purified water 2 PO 4 A 500 ml solution containing 0.1 M NaCl in purified water was prepared. 2 HPO 4 and 0.15 M NaCl. The two solutions were mixed to prepare 1 L of stock phosphate buffered saline (PBS), pH 7.4.

[0288] Example 9.3 - Preparation of glucose sensing system in PBS 20 ml of PBS prepared in Example 9.2 was placed in a beaker in which the temperature of the PBS was maintained at 37° C. The electrochemical cell of FIG. 1 was prepared using an electrochemical analyzer CHI660 from CH Instruments Inc. as the potentiostat 104 and using the electrode 1607 prepared in Example 8.4 as the working electrode 103, a platinum wire as the counter electrode 105, and Ag / AgCl (3M KCl) as the reference electrode 106. The silver layer 1603 of the electrode 1607 was connected to the potentiostat 104. The electrode was immersed in the PBS and electrically connected to the electrochemical analyzer.

[0289] Example 9.4 - Current Measurement For the system prepared in Example 9.3, a bias voltage of 0.4 V was applied between the working electrode 103 (electrode 1607) and the reference electrode 106. Upon application of the bias voltage, the current from the working electrode 103 was continuously measured. The electrochemical cell was kept for 12 minutes to condition the glucose sensing system in PBS without adding any substance thereto. A current value of 0.087 μA was then obtained for no glucose contained in the PBS. Figure 18 shows the current profiles obtained from the electrochemical cell for Examples 9.5-9.11 below. In Figure 18, "AA" stands for ascorbic acid and "AP" stands for acetaminophen.

[0290] Example 9.5 - Sensing of 1 mM glucose in PBS After conditioning the glucose sensing system, 20 μl of glucose stock solution prepared in Example 9.1 was added to the PBS in Example 9.3 to produce PBS containing 1 mM glucose. Immediately after addition, the glucose-added PBS was stirred for 3-4 seconds, which caused a temporary peak in the current. The current from the working electrode was continuously measured. When the current stabilized, a current value of 0.54 μA was obtained for 1 mM glucose in PBS.

[0291] Example 9.6 - Sensing of 3 mM glucose in PBS After the current stabilized in Example 9.5, 40 μl of glucose stock solution prepared in Example 9.1 was added to the PBS obtained from Example 9.4 to produce PBS containing 3 mM total glucose. Immediately after addition, the glucose-spiked PBS was stirred for 3-4 seconds, which caused a temporary peak in the current. The current from the working electrode was continuously measured. When the current stabilized, a current value of 1.19 μA was obtained for 3 mM glucose in PBS.

[0292] Example 9.7 - Sensing of 6 mM glucose in PBS After the current stabilized in Example 9.6, 60 μl of glucose stock solution prepared in Example 9.1 was added to the PBS obtained from Example 9.5 to produce PBS containing 6 mM total glucose. Immediately after addition, the glucose-spiked PBS was stirred for 3-4 seconds, which caused a temporary peak in the current. The current from the working electrode was continuously measured. When the current stabilized, a current value of 2.09 μA was obtained for 6 mM glucose in PBS.

[0293] Example 9.8 - Sensing 10 mM glucose in PBS After the current stabilized in Example 9.7, 80% of the glucose stock solution prepared in Example 9.1 was added. 1 μl was added to the PBS obtained from Example 9.6 to produce a PBS containing 10 mM total glucose. Immediately after addition, the glucose-spiked PBS was stirred for 3-4 seconds, which caused a transient peak in the current. The current from the working electrode was continuously measured. When the current stabilized, a current value of 2.89 μA was obtained for 10 mM glucose in PBS.

[0294] Example 9.9 - Sensing of 0.11 mM Ascorbic Acid in PBS After the current stabilized in Example 9.8, 44 μl of the aqueous ascorbic acid solution prepared in Example 9.1 was added to the PBS obtained from Example 9.7 to produce PBS containing 0.11 mM ascorbic acid (AA). Immediately after addition, the PBS with added ascorbic acid was stirred for 3-4 seconds, which caused a temporary peak in the current. The current from the working electrode was continuously measured. When the current stabilized, a current value of 2.93 μA was obtained for the sum of 10 mM glucose and 0.11 mM ascorbic acid in PBS.

[0295] Example 9.10 - Sensing of 0.17 mM Acetaminophen in PBS After the current stabilized in Example 9.9, 68 μl of the acetaminophen aqueous solution prepared in Example 9.1 was added to the PBS obtained from Example 9.8 to produce PBS containing 0.17 mM acetaminophen (AP). Immediately after addition, the PBS with added acetaminophen was stirred for 3-4 seconds, which caused a temporary peak in the current. The current from the working electrode was continuously measured. When the current stabilized, a current value of 3.21 μA was obtained for the sum of 10 mM glucose, 0.11 mM ascorbic acid, and 0.17 mM acetaminophen in PBS.

[0296] Example 9.11 - Sensing of 13.9 mM Maltose in PBS After the current stabilized in Example 9.10, 556 μl of the maltose aqueous solution prepared in Example 9.1 was added to the PBS obtained from Example 9.9 to produce PBS containing 13.9 mM maltose. Immediately after addition, the maltose-added PBS was stirred for 3-4 seconds, which caused a temporary peak in the current. The current from the working electrode was continuously measured. When the current stabilized, a current value of 4.74 μA was obtained for the sum of 10 mM glucose, 0.11 mM ascorbic acid, 0.17 mM acetaminophen, and 13.9 mM maltose in PBS.

[0297] Example 9.12 - Glucose Level Formula In Examples 9.5-9.11, the current values ​​represent and correspond to the concentration of glucose in PBS. Similar experiments are performed many more times with the similarly prepared glucose sensing system using the same and other glucose concentrations to obtain data of current values ​​and corresponding glucose concentrations. A correlation between the glucose concentration in PBS and the current values ​​is obtained by processing the data. The glucose concentration is calculated using the correlation and the current values ​​obtained from Examples 9.5-9.11.

[0298] Sensing glucose in serum Example 10.1 - Preparation of a glucose sensing system in serum Human serum was purchased from Sigma-Aldrich. The glucose content in the serum was measured using a YSI. The serum was determined to contain 5.8 mM glucose therein, which corresponds to a blood glucose level of 104 mg / dl. 10 ml of serum was placed in a beaker in which the temperature of the serum was maintained at 37° C. An electrochemical cell was prepared similarly to Example 9.3, except that one electrode 1607 prepared in Example 8.4 was used as the working electrode 103, and further, the working electrode, reference electrode, and counter electrode were immersed in the serum.

[0299] Example 10.2 - Preconditioning of the glucose sensing system in serum A 0.4 V bias voltage was applied between the working electrode 103 and the reference electrode 106 of the electrochemical cell prepared in Example 10.1. The bias voltage was maintained in the electrochemical system for more than 3 hours for system conditioning, i.e., until the background current was low enough to sense glucose oxidation. The bias voltage was then disconnected from the system.

[0300] Example 10.3 - Current Measurement Immediately after removing the bias voltage in Example 10.2, the same bias voltage was reapplied to the system and measurement of the current from the working electrode was started. The electrochemical cell was maintained for 1.2 hours for further conditioning of the glucose sensing system in serum without adding any substance thereto. When the current stabilized, a current value of 96 nA was obtained for 5.8 mM glucose originally contained in serum. Figure 19 shows the current profile measured from the electrochemical cell of Examples 10.4-10.9 below. In Figure 19, "AA" stands for ascorbic acid and "AP" stands for acetaminophen.

[0301] Example 10.4 - Sensing 10 mM glucose in serum After conditioning the glucose sensing system, 42 μl of glucose stock solution prepared in Example 9.1 was added to the serum in Example 10.2 to generate serum containing 10 mM total glucose. Immediately after addition, the glucose-spiked serum was stirred for 3-4 seconds, which caused a transient peak in the current. The current from the working electrode was continuously measured. When the current stabilized, a current value of 110 nA was obtained for 10 mM glucose in serum.

[0302] Example 10.5 - Sensing 15 mM glucose in serum After the current stabilized in Example 10.4, 50 μl of glucose stock solution prepared in Example 9.1 was added to the serum in Example 10.3 to produce serum containing 15 mM total glucose. Immediately after addition, the glucose-spiked serum was stirred for 3-4 seconds, which caused a transient peak in the current. The current from the working electrode was continuously measured. When the current stabilized, a current value of 132 nA was obtained for 15 mM glucose in serum.

[0303] Example 10.6 - Sensing 20 mM glucose in serum After the current stabilized in Example 10.5, 50 μl of glucose stock solution prepared in Example 9.1 was added to the serum in Example 10.4 to produce serum containing 20 mM total glucose. Immediately after addition, the glucose-spiked serum was stirred for 3-4 seconds, which caused a transient peak in the current. The current from the working electrode was continuously measured. When the current stabilized, a current value of 159 nA was obtained for 20 mM glucose in serum.

[0304] Example 10.7 - Sensing of 0.11 mM Ascorbic Acid in Serum After the current stabilized in Example 10.6, 22 μl of the aqueous ascorbic acid solution prepared in Example 9.1 was added to the serum obtained from Example 10.5 to produce serum containing 0.11 mM ascorbic acid (AA). Immediately after addition, the serum spiked with ascorbic acid was stirred for 3-4 seconds, which caused a temporary peak in the current. The current from the working electrode was continuously measured. When the current stabilized, a current value of 163 nA was obtained for the sum of 20 mM glucose and 0.11 mM ascorbic acid in the serum.

[0305] Example 10.8 - Sensing 0.17 mM acetaminophen in serum After the current stabilized in Example 10.7, 34 μl of the aqueous acetaminophen solution prepared in Example 9.1 was added to the serum obtained from Example 10.6 to produce serum containing 0.17 mM acetaminophen (AP). Immediately after addition, the spiked serum was stirred for 3-4 seconds, which caused a transient peak in the current. The current from the working electrode was continuously measured. When the current stabilized, a current value of 223 nA was recorded in the blood. Obtained for a sum of 20 mM glucose, 0.11 mM ascorbic acid and 0.17 mM acetaminophen in the supernatant.

[0306] Example 10.9 - Sensing 13.9 mM maltose in serum After the current stabilized in Example 10.8, 278 μl of the aqueous maltose solution prepared in Example 9.1 was added to the serum obtained from Example 10.7 to produce serum containing 13.9 mM maltose. Immediately after addition, the serum with added maltose was stirred for 3-4 seconds, which caused a temporary peak in the current. The current from the working electrode was continuously measured. When the current stabilized, a current value of 231 nA was obtained for the sum of 20 mM glucose, 0.11 mM ascorbic acid, 0.17 mM acetaminophen and 13.9 mM maltose in the serum.

[0307] Example 10.10 - Glucose Level Formula In Examples 10.4-10.9, the current values ​​represent and correspond to the concentration of glucose in serum. Similar experiments are performed many more times with the glucose sensing system prepared in the same way, using the same and other glucose concentrations, to obtain data of current values ​​and corresponding glucose concentrations. The correlation between the glucose concentration in serum and the current values ​​is obtained by processing the data. The glucose concentration is calculated using the correlation and the current values ​​obtained from Examples 10.4-10.9.

[0308] Non-clustered nanoporous layer Example 11.1 - Electroplating from a reverse micellar phase This disclosure hereby incorporates in its entirety the examples and explanations of U.S. Patent No. 8,343,690 (the '690 patent). The experiments appearing in columns 6-9 of the '690 patent are specifically incorporated herein as examples for producing nanoporous layers by electroplating and using the layers for glucose sensing.

[0309] Example 11.2 - Electroplating from the Hexagonal Phase This disclosure hereby incorporates the disclosure of U.S. Patent No. 7,892,415 (the '415 patent) in its entirety. The experiments appearing in columns 5-6 of the '415 patent are specifically incorporated herein as examples for producing hexagonally structured nanoporous layers by electroplating and using the layers for glucose sensing.

[0310] Example 11.3 - Electroplating from the Hexagonal Phase This disclosure hereby incorporates in its entirety the disclosure of “Electrochemistry Communications, Vol. 4, No. 8, August 2002, pp. 610-612” into this specification.

[0311] Example 11.4 - Chemical precipitation from a hexagonal phase This disclosure hereby incorporates in its entirety the disclosure of Science, Vol. 278, Oct. 31, 1997, pp. 838-840.

[0312] Preparation of maltose blocking layer Example 12.1 - Preparation of mPD in water M-phenylenediamine (mPD) purchased from Sigma-Aldrich was dissolved in purified water to provide aqueous mPD solutions containing 0.1, 0.3, 0.5, 1.0, 2.0 and 5.0 mM mPD.

[0313] Example 12.2 - Preparation for Cyclic Voltammetry Electrochemical analyzer CHI Multi 1 manufactured by CH Instruments Inc. An electrochemical cell was prepared using a 030C as a potentiostat 104 and the electrode 1607 prepared in Example 8.4 as the working electrode 103, a platinum wire as the counter electrode 105, and Ag / AgCl (3M KCl) as the reference electrode 106. The counter electrode 105 and the reference electrode 106 were electrically connected to form a two-electrode system.

[0314] Example 12.3 - Electrochemical Polymerization at 0.1 mM, 10 mV / sec In the electrochemical cell prepared in Example 12.2, the 0.1 mM mPD aqueous solution prepared in Example 12.1 was added instead of the test fluid 102. Cyclic voltammetry was performed using a potential sweep from +0.5 V to +1.0 V at a scan rate of 10 mV / s for two sweep segments, as shown in Figure 22. A poly-mPD maltose-blocking layer 301 was obtained on the nanoporous layer 117.

[0315] Example 12.4 - Electrochemical Polymerization at 0.1 mM, 100 mV / sec Example 12.3 was repeated, except that the scan rate was 100 mV / sec, thereby forming a poly-mPD layer on the nanoporous layer 117.

[0316] Example 12.5 - Electrochemical polymerization at 0.1 mM, 200 mV / sec Example 12.3 was repeated, except that the scan rate was 200 mV / sec, thereby forming a poly-mPD layer on the nanoporous layer 117.

[0317] Example 12.6 - Electrochemical polymerization at 0.3 mM, 10 mV / sec Example 12.3 was repeated, except that the 0.3 mM mPD aqueous solution prepared in Example 12.1 was added instead of the 0.1 mM mPD aqueous solution, thereby forming a poly-mPD layer on the nanoporous layer 117.

[0318] Example 12.7 - Electrochemical polymerization at 0.3 mM, 100 mV / sec Example 12.6 was repeated, except that the scan rate was 100 mV / sec, thereby forming a poly-mPD layer on the nanoporous layer 117.

[0319] Example 12.8 - Electrochemical polymerization at 0.3 mM, 200 mV / sec Example 12.6 was repeated, except that the scan rate was 200 mV / sec, thereby forming a poly-mPD layer on the nanoporous layer 117.

[0320] Example 12. Electrochemical Polymerization at 9-0.5 mM, 10 mV / sec Example 12.3 was repeated, except that the 0.5 mM mPD aqueous solution prepared in Example 12.1 was added instead of the 0.1 mM mPD aqueous solution, thereby forming a poly-mPD layer on the nanoporous layer 117.

[0321] Example 12. Electrochemical Polymerization at 10-0.5 mM, 100 mV / sec Example 12.6 was repeated, except that the scan rate was 100 mV / sec, thereby forming a poly-mPD layer on the nanoporous layer 117.

[0322] Example 12.11 - Electrochemical Polymerization at 0.5 mM, 200 mV / sec Example 12.6 was repeated, except that the scan rate was 200 mV / sec, thereby forming a poly-mPD layer on the nanoporous layer 117.

[0323] Example 12.12-Electrochemical Polymerization at 1.0 mM, 10 mV / sec Example 12.3 was repeated, except that the 1.0 mM mPD aqueous solution prepared in Example 12.1 was added instead of the 0.1 mM mPD aqueous solution, thereby forming a nanoporous layer 117. A poly-mPD layer was formed on top.

[0324] Example 12.13 - Electrical Shock The electrochemical cell of FIG. 23 was constructed for chronoamperometry using a layer of poly-mPD prepared in Example 12.12 as the porous polymer layer 302 and 1M H 2 SO 4 An aqueous solution was prepared using the electrolyte solution. An electric shock was applied to the porous polymer layer 302 by applying a single pulse from +0.0V to +1.0V with a pulse width of 1.0 seconds.

[0325] Example 12.14 - Electrochemical Polymerization and Electrical Shock at 1.0 mM, 100 mV / sec Example 12.6 was repeated, except that the scan rate was 100 mV / sec, thereby forming a poly-mPD layer on the nanoporous layer 117. Example 12.13 was then repeated with the poly-mPD layer formed on the nanoporous layer.

[0326] Example 12.15-Electrochemical Polymerization and Electrical Shock at 1.0 mM, 200 mV / sec Example 12.6 was repeated, except that the scan rate was 200 mV / sec, thereby forming a poly-mPD layer on the nanoporous layer 117. Example 12.13 was then repeated with the poly-mPD layer formed on the nanoporous layer.

[0327] Example 12.16 - Electrochemical Polymerization and Electrical Shock at 2.0 mM, 10 mV / sec Example 12.3 was repeated, except that the 2.0 mM mPD aqueous solution prepared in Example 12.1 was added instead of the 0.1 mM mPD aqueous solution, thereby forming a poly-mPD layer on the nanoporous layer 117. Example 12.13 was then repeated with the poly-mPD layer formed on the nanoporous layer.

[0328] Example 12.17 - Electrochemical polymerization and electric shock at 2.0 mM, 100 mV / sec Example 12.6 was repeated, except that the scan rate was 100 mV / sec, thereby forming a poly-mPD layer on the nanoporous layer 117. Example 12.13 was then repeated with the poly-mPD layer formed on the nanoporous layer.

[0329] Example 12.18 - Electrochemical polymerization and electric shock at 2.0 mM, 200 mV / sec Example 12.6 was repeated, except that the scan rate was 200 mV / sec, thereby forming a poly-mPD layer on the nanoporous layer 117. Example 12.13 was then repeated with the poly-mPD layer formed on the nanoporous layer.

[0330] Example 12.19 - Electrochemical Polymerization and Electrical Shock at 5.0 mM, 10 mV / sec Example 12.3 was repeated, except that the 5.0 mM mPD aqueous solution prepared in Example 12.1 was added instead of the 0.1 mM mPD aqueous solution, thereby forming a poly-mPD layer on the nanoporous layer 117. Example 12.13 was then repeated with the poly-mPD layer formed on the nanoporous layer.

[0331] Example 12. Electrochemical Polymerization and Electrical Shock at 20-5.0 mM, 100 mV / sec Example 12.6 was repeated, except that the scan rate was 100 mV / sec, thereby forming a poly-mPD layer on the nanoporous layer 117. Example 12.13 was then repeated with the poly-mPD layer formed on the nanoporous layer.

[0332] Example 12.21 - Electrochemical Polymerization and Electrical Shock at 5.0 mM, 200 mV / sec Example 12.6 was repeated, except that the scan rate was 200 mV / sec, thereby forming a poly-mPD layer on the nanoporous layer 117. Example 12.13 was then repeated with the poly-mPD layer formed on the nanoporous layer.

[0333] Sensing glucose without interference from maltose Example 13.1 - Preparation of serum Human serum was purchased from Sigma-Aldrich. The glucose content in serum was measured using a YSI. The serum was determined to contain 5.8 mM glucose in it, which corresponds to a blood glucose level of 104 mg / dl.

[0334] Example 13.2 - Preparation of a glucose sensing system in serum 10 ml of serum prepared in Example 13.1 was placed in a beaker in which the temperature of the serum was maintained at 37° C. An electrochemical cell was prepared similarly to Example 10.2, except that the working electrode 103 included a poly-mPD maltose-blocking layer 301 on a nanoporous layer prepared in Example 12.3 using a 0.1 mM mPD solution and a scan rate of 10 mV / sec.

[0335] Example 13.1 - Preparation of a glucose sensing system in serum An electrochemical cell was prepared by repeating Example 10.2, except that the working electrode 103 included a poly-mPD maltose-blocking layer 301 on the nanoporous layer prepared in Example 12.3 (using a 0.1 mM mPD solution and a scan rate of 10 mV / sec), and further, the working electrode, reference electrode and counter electrode were immersed in serum.

[0336] Example 13.2 - Conditioning of the glucose sensing system in serum In the electrochemical cell system prepared in Example 13.1, a bias voltage of 0.4 V was applied between the working electrode 103 and the reference electrode 106. The bias voltage was maintained in the electrochemical system for more than 3 hours to precondition the system. The bias voltage was then disconnected from the system and reconnected. Once the bias voltage was reapplied, the current from the working electrode began to be measured. The electrochemical cell was maintained in serum to further condition the glucose sensing system. When the current stabilized, a current value of 96 nA was measured for 5.8 mM glucose originally contained in serum.

[0337] Example 13.3 - Electrode with Maltose-Blocking Layer (0.1 mM, 10 mV / sec) In the system prepared in Example 13.2, a glucose stock solution prepared as in Example 9.1 was added to the serum to produce serum with a total glucose concentration of 10 mM. Further glucose stock solutions were then added to produce serum with total glucose concentrations of 15 mM and 20 mM (with a fixed time interval between additions). An ascorbic acid solution prepared in Example 9.1 was then added to the serum to produce serum with 0.11 mM ascorbic acid. An acetaminophen solution prepared in Example 9.1 was then added to the resulting serum to produce serum with 0.17 mM acetaminophen. An maltose solution prepared in Example 9.1 was then added to the resulting serum to produce serum with 13.9 mM maltose. Immediately after each addition, the serum was stirred for 3-4 seconds, which caused a temporary peak in the current. Figure 25 shows the current monitored in this example in red. Changes in current were observed in response to the addition of glucose, ascorbic acid (AA) and acetaminophen (AP). However, after the addition of maltose, the current was below 5 nA / mMcm, except for the peak caused by stirring. 2 No current change was observed beyond 0.05 V. Thus, the maltose-blocking layer in this example effectively blocked maltose but did not interfere with glucose sensing.

[0338] Example 13.4 - Electrodes with Maltose-Blocking Layer (0.1 mM, 100 mV / sec) The working electrode 103 contained a maltose-blocking layer prepared as in Example 12.4. Examples 13.1-13.3 were repeated, except that 0.1 mM mPD solution was used at a scan rate of 100 mV / sec. Figure 25 shows in green the current monitored in this example. Changes in current were observed in response to the addition of glucose, ascorbic acid, and acetaminophen. However, after the addition of maltose, the current was below 5 nA / mMcm, except for the peak caused by stirring. 2 No current change was observed beyond 0.05 μm. The maltose-blocking layer in this example effectively blocked maltose but did not interfere with glucose sensing.

[0339] Example 13.5 - Electrodes with Maltose-Blocking Layer (0.1 mM, 200 mV / sec) Examples 13.1-13.3 were repeated, except that the working electrode 103 contained a maltose-blocking layer prepared as in Example 12.5 (using a 0.1 mM mPD solution at a scan rate of 200 mV / sec). Figure 25 shows in purple the current monitored in this example. Changes in current were observed in response to the addition of glucose, ascorbic acid and acetaminophen. However, after the addition of maltose, the current was below 5 nA / mMcm, except for the peak caused by agitation. 2 No current change was observed beyond 0.05 μm. The maltose-blocking layer in this example effectively blocked maltose but did not interfere with glucose sensing.

[0340] Example 13.6 - Electrodes with Maltose-Blocking Layer (0.3 mM, 10 mV / sec) Examples 13.1-13.3 were repeated, except that the working electrode contained a maltose-blocking layer prepared in Example 12.6 (using 0.3 mM mPD solution at a scan rate of 10 mV / sec). Figure 26 shows in red the current monitored in this example. Changes in current were observed in response to the addition of glucose, ascorbic acid, and acetaminophen. However, after the addition of maltose, the current was below 5 nA / mMcm, except for the peak caused by stirring. 2 No current change was observed beyond 0.05 μm. The maltose-blocking layer in this example effectively blocked maltose but did not interfere with glucose sensing.

[0341] Example 13.7 - Electrodes with Maltose-Blocking Layer (0.3 mM, 100 mV / sec) Examples 13.1-13.3 were repeated, except that the working electrode contained a maltose-blocking layer prepared in Example 12.7 (using 0.3 mM mPD solution at a scan rate of 100 mV / sec). Figure 26 shows in green the current monitored in this example. Changes in current were observed in response to the addition of glucose, ascorbic acid, and acetaminophen. However, after the addition of maltose, the current was below 5 nA / mMcm, except for the peak caused by stirring. 2 No current change was observed beyond 0.05 μm. The maltose-blocking layer in this example effectively blocked maltose but did not interfere with glucose sensing.

[0342] Example 13.8 - Electrode with Maltose-Blocking Layer (0.3 mM, 200 mV / sec) Examples 13.1-13.3 were repeated, except that the working electrode contained a maltose-blocking layer prepared in Example 12.8 (using 0.3 mM mPD solution at a scan rate of 200 mV / sec). Figure 26 shows in purple the current monitored in this example. Changes in current were observed in response to the addition of glucose, ascorbic acid, and acetaminophen. However, after the addition of maltose, the current was below 5 nA / mMcm, except for the peak caused by agitation. 2No current change was observed beyond 0.05 μm. The maltose-blocking layer in this example effectively blocked maltose but did not interfere with glucose sensing.

[0343] Example 13.9 - Electrode with Maltose-Blocking Layer (0.5 mM, 10 mV / sec ) Examples 13.1-13.3 were repeated, except that the working electrode contained a maltose-blocking layer prepared in Example 12.9 (using 0.5 mM mPD solution at a scan rate of 10 mV / sec). Figure 27 shows in red the current monitored in this example. Changes in current were observed in response to the addition of glucose, ascorbic acid, and acetaminophen. However, after the addition of maltose, the current was below 5 nA / mMcm, except for the peak caused by agitation. 2 No current change was observed beyond 0.05 μm. The maltose-blocking layer in this example effectively blocked maltose but did not interfere with glucose sensing.

[0344] Example 13.10 - Electrode with Maltose-Blocking Layer (0.5 mM, 100 mV / sec) Examples 13.1-13.3 were repeated, except that the working electrode contained a maltose-blocking layer prepared in Example 12.9 (using 0.5 mM mPD solution at a scan rate of 100 mV / sec). Figure 27 shows in green the current monitored in this example. Changes in current were observed in response to the addition of glucose, ascorbic acid, and acetaminophen. However, after the addition of maltose, the current was below 5 nA / mMcm, except for the peak caused by agitation. 2 No current change was observed beyond 0.05 μm. The maltose-blocking layer in this example effectively blocked maltose but did not interfere with glucose sensing.

[0345] Example 13.11 - Electrode with Maltose-Blocking Layer (0.5 mM, 200 mV / sec) Examples 13.1-13.3 were repeated, except that the working electrode contained a maltose-blocking layer prepared in Example 12.11 (using 0.5 mM mPD solution at a scan rate of 200 mV / sec). Figure 27 shows in purple the current monitored in this example. Changes in current were observed in response to the addition of glucose, ascorbic acid, and acetaminophen. However, after the addition of maltose, the current was below 5 nA / mMcm, except for the peak caused by agitation. 2 No current change was observed beyond 0.05 μm. The maltose-blocking layer in this example effectively blocked maltose but did not interfere with glucose sensing.

[0346] Example 13.12 - Electrode with Maltose-Blocking Layer (1.0 mM, 10 mV / sec) Examples 13.1-13.3 were repeated, except that the working electrode was prepared as in Example 12.12 (using 1.0 mM mPD solution at a scan rate of 10 mV / sec) and further included a maltose-blocking layer that was subjected to an electric shock as in Example 12.13. Figure 28 shows in red the current monitored in this example. Changes in current were observed in response to the addition of glucose, ascorbic acid, and acetaminophen. However, after the addition of maltose, the current was below 5 nA / mMcm, except for the peak caused by agitation. 2 No current change was observed beyond 0.05 μm. The maltose-blocking layer in this example effectively blocked maltose but did not interfere with glucose sensing.

[0347] Example 13.13 - Electrode with Maltose-Blocking Layer (1.0 mM, 100 mV / sec) Examples 13.1-13.3 were repeated, except that the working electrode was prepared as in Example 12.14 (using a 1.0 mM mPD solution at a scan rate of 100 mV / sec) and further included a maltose-blocking layer with an electric shock as in Example 12.13. Figure 28 shows in green the current monitored in this example. Changes in current were observed in response to the addition of glucose, ascorbic acid, and acetaminophen. However, after the addition of maltose, the current was below 5 nA / mMcm, except for the peak caused by agitation. 2 No current change was observed beyond 0.01%. The maltose-blocking layer in this example was effectively blocked ATP but did not interfere with glucose sensing.

[0348] Example 13.14 - Electrode with Maltose-Blocking Layer (1.0 mM, 200 mV / sec) Examples 13.1-13.3 were repeated, except that the working electrode was prepared as in Example 12.15 (using 1.0 mM mPD solution at a scan rate of 200 mV / sec) and further included a maltose-blocking layer with an electric shock. Figure 28 shows in purple the current monitored in this example. Changes in current were observed in response to the addition of glucose, ascorbic acid, and acetaminophen. However, after the addition of maltose, the current was below 5 nA / mMcm, except for the peak caused by agitation. 2 No current change was observed beyond 0.05 μm. The maltose-blocking layer in this example effectively blocked maltose but did not interfere with glucose sensing.

[0349] Example 13.15 - Electrode with Maltose-Blocking Layer (2.0 mM, 10 mV / sec) Examples 13.1-13.3 were repeated, except that the working electrode was prepared as in Example 12.16 (using a 2.0 mM mPD solution at a scan rate of 10 mV / sec) and further included a maltose-blocking layer with an electric shock as in Example 12.15. Figure 29 shows in red the current monitored in this example. Changes in current were observed in response to the addition of glucose, ascorbic acid, and acetaminophen. However, after the addition of maltose, the current was below 5 nA / mMcm, except for the peak caused by agitation. 2 No current change was observed beyond 0.05 μm. The maltose-blocking layer in this example effectively blocked maltose but did not interfere with glucose sensing.

[0350] Example 13.16 - Electrode with Maltose-Blocking Layer (2.0 mM, 100 mV / sec) Examples 13.1-13.3 were repeated, except that the working electrode was prepared as in Example 12.17 (using a 2.0 mM mPD solution at a scan rate of 100 mV / sec) and further included a maltose-blocking layer with an electric shock as in Example 12.15. Figure 29 shows in green the current monitored in this example. Changes in current were observed in response to the addition of glucose, ascorbic acid, and acetaminophen. However, after the addition of maltose, the current was below 5 nA / mMcm, except for the peak caused by agitation. 2 No current change was observed beyond 0.05 μm. The maltose-blocking layer in this example effectively blocked maltose but did not interfere with glucose sensing.

[0351] Example 13.17 - Electrode with Maltose-Blocking Layer (2.0 mM, 200 mV / sec) Examples 13.1-13.3 were repeated, except that the working electrode was prepared as in Example 12.18 (using a 2.0 mM mPD solution at a scan rate of 200 mV / sec) and further included a maltose-blocking layer with an electric shock as in Example 12.15. Figure 29 shows in purple the current monitored in this example. Changes in current were observed in response to the addition of glucose, ascorbic acid, and acetaminophen. However, after the addition of maltose, the current was below 5 nA / mMcm, except for the peak caused by agitation. 2 No current change was observed beyond 0.05 μm. The maltose-blocking layer in this example effectively blocked maltose but did not interfere with glucose sensing.

[0352] Example 13.18 - Electrode with Maltose-Blocking Layer (5.0 mM, 10 mV / sec) A working electrode was prepared as in Example 12.19 (using 5.0 mM mPD solution at a scan rate of 10 mV / sec) and further treated with maltodextrin with an electric shock as in Example 12.15. Examples 13.1-13.3 were repeated, except that a source-blocking layer was included. Figure 30 shows in red the current monitored in this example. Changes in current were observed in response to the addition of glucose, ascorbic acid, and acetaminophen. However, after the addition of maltose, the current was below 5 nA / mMcm, except for the peak caused by agitation. 2 No current change was observed beyond 0.05 μm. The maltose-blocking layer in this example effectively blocked maltose but did not interfere with glucose sensing.

[0353] Example 13.19 - Electrode with Maltose-Blocking Layer (5.0 mM, 100 mV / sec) Examples 13.1-13.3 were repeated, except that the working electrode was prepared as in Example 12.20 (using a 5.0 mM mPD solution at a scan rate of 100 mV / sec) and further included a maltose-blocking layer with an electric shock as in Example 12.15. Figure 30 shows in green the current monitored in this example. Changes in current were observed in response to the addition of glucose, ascorbic acid, and acetaminophen. However, after the addition of maltose, the current was below 5 nA / mMcm, except for the peak caused by agitation. 2 No current change was observed beyond 0.05 μm. The maltose-blocking layer in this example effectively blocked maltose but did not interfere with glucose sensing.

[0354] Example 13.20 - Electrode with Maltose-Blocking Layer (5.0 mM, 200 mV / sec) Examples 13.1-13.3 were repeated, except that the working electrode was prepared as in Example 12.21 (using a 5.0 mM mPD solution at a scan rate of 200 mV / sec) and further included a maltose-blocking layer with an electric shock as in Example 12.15. Figure 30 shows in purple the current monitored in this example. Changes in current were observed in response to the addition of glucose, ascorbic acid, and acetaminophen. However, after the addition of maltose, the current was below 5 nA / mMcm, except for the peak caused by agitation. 2 No current change was observed beyond 0.05 μm. The maltose-blocking layer in this example effectively blocked maltose but did not interfere with glucose sensing.

[0355] Example 13.21 - Electrode with Maltose-Blocking Layer (1.0 mM, 10 mV / sec) Example 13.12 is repeated, except that the poly-mPD layer prepared in Example 12.12 (using a 1.0 mM mPD solution at a scan rate of 10 mV / sec) is not subjected to electric shock.

[0356] Example 13.22 - Electrode with Maltose-Blocking Layer (1.0 mM, 100 mV / sec) Example 13.12 is repeated, except that the poly-mPD layer prepared in Example 12.14 (1.0 mM mPD solution used at a scan rate of 100 mV / sec) is not subjected to electric shock.

[0357] Example 13.23 - Electrode with Maltose-Blocking Layer (1.0 mM, 200 mV / sec) Example 13.12 is repeated, except that the poly-mPD layer prepared in Example 12.15 (using a 1.0 mM mPD solution at a scan rate of 200 mV / sec) is not subjected to electrical shock.

[0358] Example 13.24 - Electrode with Maltose-Blocking Layer (2.0 mM, 10 mV / sec) The poly-mPD layer prepared in Example 12.16 (2.0 mM mPD solution at 10 mV / sec Example 13.12 is repeated, except that the electrode (used at a scan rate of 100 s) is not subjected to an electric shock. No change in current is observed upon each addition of glucose, meaning that the poly-mPD layer effectively blocks glucose.

[0359] Example 13.25 - Electrode with Maltose-Blocking Layer (2.0 mM, 100 mV / sec) Example 13.12 is repeated, except that the poly-mPD layer prepared in Example 12.17 (2.0 mM mPD solution used at a scan rate of 100 mV / sec) is not subjected to electric shock. No change in current is observed upon each addition of glucose, meaning that the poly-mPD layer effectively blocks glucose.

[0360] Example 13.26 - Electrode with Maltose-Blocking Layer (2.0 mM, 200 mV / sec) Example 13.12 is repeated, except that the poly-mPD layer prepared in Example 12.18 (2.0 mM mPD solution used at a scan rate of 200 mV / sec) is not subjected to electric shock. No change in current is observed upon each addition of glucose, meaning that the poly-mPD layer effectively blocks glucose.

[0361] Example 13.27 - Electrode with Maltose-Blocking Layer (5.0 mM, 10 mV / sec) Example 13.12 is repeated, except that the poly-mPD layer prepared in Example 12.19 (5.0 mM mPD solution used at a scan rate of 10 mV / sec) is not subjected to electric shock. No change in current is observed upon each addition of glucose, meaning that the poly-mPD layer effectively blocks glucose.

[0362] Example 13.28 - Electrode with Maltose-Blocking Layer (5.0 mM, 100 mV / sec) Example 13.12 is repeated, except that the poly-mPD layer prepared in Example 12.20 (5.0 mM mPD solution used at a scan rate of 100 mV / sec) is not subjected to electric shock. No change in current is observed upon each addition of glucose, meaning that the poly-mPD layer effectively blocks glucose.

[0363] Example 13.29 - Electrode with Maltose-Blocking Layer (5.0 mM, 200 mV / sec) Example 13.12 is repeated, except that the poly-mPD layer prepared in Example 12.21 (5.0 mM mPD solution used at a scan rate of 200 mV / sec) is not subjected to electric shock. No change in current is observed upon each addition of glucose, meaning that the poly-mPD layer effectively blocks glucose.

[0364] Another electric shock Example 14.1-2 Pulse Electric Shock Example 12.13 is repeated, except with a pulse width of 0.5 seconds and two pulses spaced 0.5 seconds apart.

[0365] Example 14.2-2 Pulse Electric Shock Repeat Example 14.1 except each pulse is from +0.0V to +2.0V.

[0366] Example 14.3 - Electrical shock with multiple pulses Example 12.13 is repeated, except for a series of 10 pulses with a pulse width of 0.1 seconds and an interval of 0.1 seconds between two pulses.

[0367] Example 14.4 - Electrical shock with multiple pulses Repeat Example 14.1 except each pulse is from +0.0V to +2.0V.

[0368] Example 14.5 - Electric shock at a single slope Example 12.13 is repeated except that the potential is gradually increased from +0.0 V to +1.0 V over a period of 1 second.

[0369] Example 14.6 - Electrical shocks at multiple gradients Repeat Example 14.5, except that the ramp potential is repeated 5 times with an interval of 0.1 between two ramps.

[0370] Example 14.7 - Electric shock at a single slope Example 12.13 is repeated except that the potential is gradually increased from +0.0 V to +2.0 V over a period of 2 seconds.

[0371] Example 14.8 - Electrical shock at multiple gradients Repeat Example 14.7, except that the ramp potential is repeated 5 times with an interval of 0.1 between two ramps.

[0372] Conditioning the working electrode Example 15.1 - Preparation of a glucose sensing system in serum Example 10.2 was repeated to prepare an electrochemical cell for glucose sensing in serum. The working electrode 103 was one of the electrodes 1607 (including a platinum nanoporous layer 1609) prepared in Example 8.4, without an electrolyte ion-blocking layer.

[0373] Example 15.2 - Conditioning of the working electrode (electrolyte ion-no blocking layer) In the electrochemical cell prepared in Example 15.1, a bias voltage of 0.4 V was applied between the working electrode 103 and the reference electrode 106. Unlike in Example 10.3, the current from the working electrode was measured continuously as soon as the bias voltage was applied. FIG. 42A shows the profile of the current profile measured from the electrochemical cell, where the working electrode 103 does not include an electrolyte ion-blocking layer. Referring to FIG. 42A, at 10,000 seconds (about 3 hours), 20,000 seconds and 30,000 seconds, the current still decreases at a significant rate. FIG. 42B is a close-up of the profile in FIG. 42A, showing that a glucose stock solution prepared as in Example 9.1 was successfully added after the conditioning of the working electrode was completed.

[0374] Example 15.3 - Preparation of Working Electrode with PMMA Electrolyte Ion-Blocking Layer PMMA (product number 445746) purchased from Sigma-Aldrich was dissolved in dimethylformamide (DMF) to obtain a 2 wt% PMMA solution. Using a microsyringe, 0.2 μL of the PMMA solution was dropped onto the platinum nanoporous layer 1609 of one of the electrodes 1607 prepared in Example 8.4. Once the solvent had dried up, a PMMA electrolyte ion-blocking layer 505 was formed on the platinum nanoporous layer 1609.

[0375] Example 15.4 - Preparation of a glucose sensing system in serum Example 10.2 was repeated to prepare an electrochemical cell for glucose sensing in serum, except that the working electrode having a PMMA electrolyte ion-blocking layer prepared in Example 15.1 was used as the working electrode 103.

[0376] Example 15.5 - Conditioning the Working Electrode In the electrochemical cell prepared in Example 15.4, a bias voltage of 0.4 V was applied between the working electrode 103 and the reference electrode 106. As soon as the bias voltage was applied, the current from the working electrode was continuously measured. Figure 43 shows the current profile measured from the electrochemical cell, where the working electrode 103 includes an electrolyte ion-blocking layer. A glucose stock solution prepared as in Example 9.1 was successfully added after the conditioning of the working electrode was completed. The peaks in Figure 43 represent the stirring after each addition.

[0377] Example 15.6 - Comparison of conditioning times Figure 44 is an overlay of the current profiles of Figure 42 (Example 15.2) and Figure 43 (Example 15.5). The current for Example 15.5 (including an electrolyte ion-blocking layer) settles and stabilizes by about 600 seconds, while the current for Example 15.2 (without an electrolyte ion-blocking layer) decreases at a significant rate in the same time frame.

[0378] Example 15.7 - Preparation of working electrode with PHEMA layer PHEMA (product number 529265) purchased from Sigma-Aldrich was dissolved in dimethylformamide (DMF) to obtain a 2 wt% PHEMA solution. Using a microsyringe, 0.2 μL of the PHEMA solution was dropped onto the platinum nanoporous layer 1609 of one of the electrodes 1607 prepared in Example 8.4. Once the solvent had completely dried, a PHEMA electrolyte ion-blocking layer 505 was formed on the platinum nanoporous layer 1609.

[0379] Example 15.8 - Preparation of working electrode with PMMA-EG-PMMA layer PMMA-EG-PMMA (product number 463183) purchased from Sigma-Aldrich was dissolved in dimethylformamide (DMF) to obtain a 2 wt% PMMA-EG-PMMA solution. Using a microsyringe, 0.2 μL of the PMMA-EG-PMMA solution was dropped onto the platinum nanoporous layer 1609 of one of the electrodes 1607 prepared in Example 8.4. Once the solvent had dried up, a PMMA-EG-PMMA electrolyte ion-blocking layer 505 was formed on the platinum nanoporous layer 1609.

[0380] Example 15.8 - Preparation of a glucose sensing system and conditioning in serum An electrochemical cell for glucose sensing in serum was prepared by repeating Example 15.4, except that the working electrode prepared in Examples 15.7 and 15.8 was used as the working electrode 103. Further, Example 15.5 was repeated with the prepared electrochemical cell.

[0381] Manufacturing of CGM subcutaneous electrode units Example 16.1 - Formation of a conductive layer on a base A polyimide film with a thickness of 150 μm was used as the base substrate 503. A silver layer 1603 was printed on the polyimide film to obtain silver conductive elements 110C, 110W and 110R with a thickness of about 20 μm in the shape shown in Figure 35. Then, a conductive carbon layer 1605 was printed on the silver conductive elements 110C and 110W with a thickness of about 20 μm. No carbon layer was formed on the silver layer conductive element 110R.

[0382] Example 16.2 - Placement and cutting of insulating layer A polyimide film with a thickness of 50 μm was used as the insulating layer 707. The polyimide film was cut to a size to cover the intermediate product of FIG. 35 while exposing the terminal portion 705. The polyimide film was drilled to provide three openings to expose areas for the working electrode, the reference electrode and the counter electrode. Then, the pre-cut polyimide was placed on the intermediate product of FIG. 35 such that the adhesive layer was in contact with the polyimide base 503 to provide the intermediate product of FIG. 36. Then, the polyimide base 503 and the polyimide insulating layer 707 outside the conductive element were cut to provide the intermediate product of FIG. 37.

[0383] Example 16.3 - Formation of a clustered nanoporous layer The cluster colloid obtained in Example 5.1 was diluted to 60 mg / ml with purified water. Using a microsyringe, 0.2 μL of the diluted cluster colloid was dropped onto the exposed carbon layer 1605 through one opening for the working electrode 501 of the intermediate product prepared in Example 16.2. The cluster colloid dropped onto the carbon layer 1605 was dried to provide a clustered nanoporous layer 117, and the intermediate product in FIG. 38A was obtained.

[0384] Example 16.4 - Formation of an Electrolyte Ion-Blocking Layer PMMA (product number 445746) purchased from Sigma-Aldrich was dissolved in dimethylformamide (DMF) to obtain a 2 wt% PMMA solution. Using a microsyringe, 0.2 μL of the PMMA solution was dropped onto the nanoporous layer 117 of the intermediate product prepared in Example 16.3. Once the solvent had completely dried, a PMMA electrolyte ion-blocking layer 505 was formed on the nanoporous layer 117.

[0385] Example 16.5 - Formation of a biocompatible layer A biocompatible layer (pHEMA) is formed on the electrolyte ion-blocking layer 505 as shown in FIG. 38B to obtain the non-enzymatic CGM electrode unit of FIG.

[0386] Example 16.6 - Formation of a biocompatible layer pHEMA (product number 192066) purchased from Sigma-Aldrich was dissolved in dimethyl sulfoxide (DMSO) to obtain a 0.5 wt% pHEMA solution. Using a microsyringe, 1.0 μL of the pHEMA solution was dropped onto the electrolyte ion-blocking layer 505 of the intermediate product prepared in Example 16.4. Once the solvent had completely dried, a pHEMA biocompatible layer 507 was formed as shown in FIG. 38B, resulting in the non-enzymatic CGM electrode unit 701 of FIG. 33.

[0387] CGM Animal Testing Example 17.1 - Preparation for CGM Animal Studies The non-enzymatic CGM electrode unit prepared in Example 16.6 was subcutaneously inserted into the rat's body so that the electrodes 103, 105 and 106 were in contact with the rat's interstitial fluid. The CGM electrode unit 701 was connected to a UXN potentiostat developed by UXN Co., Ltd. (the applicant of this application) and Seoul National University Hospital. FIG. 45A is a photograph of the UXN potentiostat. FIG. 45B is a photograph showing the CGM electrode unit 701 connected to the UXN potentiostat of FIG. 45A. FIG. 45C is a photograph showing the UXN potentiostat with its case. The UXN potentiostat includes a wireless module for wireless communication with a computer and can be wirelessly controlled by the computer. A glucose solution was prepared for injection into the rat's vein to induce changes in glucose levels in the rat's blood and interstitial fluid.

[0388] Example 17.2 - Continuous monitoring of glucose levels in rats The subcutaneous insertion of the CGM electrode unit 701 was maintained for five consecutive days. On the first day, the rats were injected twice with glucose solution. On subsequent days, the glucose solution was injected once per day. The UXN potentiostat measured the current from the CGM electrode unit 701 for a period of about 1.5 hours after each (first) injection. Also, every 2-5 minutes during the period of about 1.5 hours, a small amount of the rat's blood was taken from its tail and applied to a test strip for a Roche Accu-Chek® blood glucose meter, which provided the glucose concentration in the blood.

[0389] Example 17.3 - Rat CGM measurements and blood glucose plotting FIG. 46 shows the CGM measured by the UXN potentiostat in Example 17.2. The current from the electrode module is shown in blue. The red dots in FIG. 46 represent blood glucose concentrations obtained from a Roche Accu Chek® blood glucose meter. Assuming that there is a time lag of about 10 minutes between the glucose level in the interstitial fluid and the glucose level in the blood, the data was calibrated by shifting the blue signal in time, which was shifted relative to the red dots. It is understood that the sharp peaks in the blue signal are mainly due to the body movement of the rat during the measurement. Based on the graph in FIG. 45, it is believed that there is a strong correlation between blood glucose concentrations using a Roche Accu Chek® blood glucose meter and CGM monitoring using the non-enzymatic CGM electrode unit 701 prepared in Example 16.6.

[0390] Example 17.4 - Clark Error Grid Analysis FIG. 47 is a Clarke Error Grid for the non-enzymatic CGM electrode unit 701 prepared in Example 16.6, based on the measurements presented in the graph of FIG. 46. The reference sensor for this Clarke Error Grid analysis is a Roche Accu-Chek® blood glucose meter. The grid has five regions. Region A includes values ​​within 20% of the reference sensor; Region B includes values ​​that are outside 20% of Region A but would not lead to improper treatment; Region C includes values ​​that potentially lead to unnecessary treatment; Region D includes values ​​that indicate a potentially dangerous failure to detect hypoglycemia or hyperglycemia; and Region E includes values ​​that would disrupt treatment of hypoglycemia for hyperglycemia, and vice versa. As summarized in the table below the grid, the analysis shows that over 91% of the points were within Regions A and B.

[0391] Combination of features This disclosure provides much discussion and information about many features related to nanoporous structures and / or glucose sensing technology. It is the object of this disclosure to provide many devices, systems and methods related to those features. Two or more features disclosed above can be combined together to form a device, system or method, to the extent that the specific combination may be combined even if not presented in this disclosure. It is also the object of this disclosure to pursue claims directed to many of those features disclosed herein. Some of those features are presented in claim form in the following section. Many claims are presented in reference form by reference to one or more other claims. Applicant notes that some claims that reference multiple claims may include combinations of features that are mutually inconsistent (hereinafter "incorrect combinations"). However, Applicant recognizes that such claims may still include one or more combinations of features that are not mutually inconsistent (hereinafter "correct combinations"). By presenting a claim that may include both correct and incorrect combinations, Applicant intends to confirm its or the inventor's possession of a correct combination and provide specific support for the correct combination for subsequent claims of a correct combination.

Claims

1. A nanoporous layer comprising a multitude of nanoparticles forming irregularly shaped bodies, adjacent ones of the irregularly shaped bodies are in contact with each other and with other ones of the irregularly shaped bodies to form a three-dimensional interconnected network of irregularly shaped bodies; wherein adjacent ones of the irregularly shaped bodies define irregularly shaped unoccupied spaces that connect to other unoccupied spaces defined by other ones of the irregularly shaped bodies, forming a three-dimensional interconnected network of irregularly shaped spaces; within the three-dimensional interconnected network of irregularly shaped bodies, adjacent ones of the nanoparticles, where there are no intervening nanoparticles between the adjacent ones, define interparticle nanopores between the adjacent ones; A nanoporous layer, wherein at least a portion of said interparticle nanopores have a size ranging from about 0.5 nm to about 3 nm.

2. The interparticle nanopores are distributed substantially throughout the interior of the three-dimensional interconnected network of irregularly shaped bodies; the unoccupied spaces of the three-dimensional interconnected network of irregularly shaped spaces are distributed substantially throughout the nanoporous layer; 10. The nanoporous layer of claim 1, wherein said three-dimensional interconnected network of irregularly shaped spaces is generally complementary to said three-dimensional interconnected network of irregularly shaped bodies.

3. The nanoporous layer does not contain organic molecules therein, or, if present, contains organic molecules in an amount less than 0.5 parts by weight per 100 parts by weight of the nanoparticles; The nanoporous layer of claim 1 or claim 2, wherein the nanoporous layer has a roughness factor of about 100 to about 2500.

4. A nanoporous layer described in any of claims 1 to 3, wherein at least a portion of the nanoparticles have a generally ovoid or spherical shape with a length in the range of about 2 nm to about 5 nm.

5. A substrate including a conductive surface; A nanoporous layer according to any one of claims 1 to 4 formed on the conductive surface; 1. A glucose sensing electrode comprising: A glucose-sensing electrode that does not contain a glucose-specific enzyme.

6. The substrate comprises a conductive metal layer and a conductive carbon layer formed on the conductive metal layer, The glucose sensing electrode of claim 5 , wherein the substrate comprises at least one of a conductive material and a semi-conductive material that provides the conductive surface.

7. When a bias voltage of 0.2 to 0.45 V is applied between the glucose sensing electrode in contact with a glucose-containing liquid and a reference electrode, the glucose sensing electrode is configured to cause oxidation of glucose in the nanoporous layer and to generate a current which is the sum of a glucose-oxidation current caused by the oxidation of glucose only and a background current caused by other electrochemical interactions between the glucose-containing liquid and the glucose sensing electrode; 7. The glucose sensing electrode of claim 5, wherein, at steady state, the glucose-oxidation current is at a level higher than 10 nA / mMcm2 when the glucose-containing liquid contains glucose at a concentration of 4-20 mM (72-360 mg / dL).

8. An electrolyte ion-blocking layer formed on the nanoporous layer; a biocompatible layer formed on the electrolyte ion-blocking layer; and Further comprising: A glucose sensing electrode as described in any one of claims 5 to 7, wherein when contacted with a liquid containing glucose, Na + , K + , Ca 2+ , Cl - , PO 4 3- and CO 3 2- , the electrolyte ion-blocking layer is configured to prevent Na + , K + , Ca 2+ , Cl - , PO 4 3- and CO 3 2- contained in the liquid from diffusing towards the nanoporous layer, such that there is a substantial discontinuity in the total concentration of Na + , K + , Ca 2+ , Cl - , PO 4 3- and CO 3 2- between the two sides of the electrolyte ion-blocking layer.

9. The glucose sensing electrode of claim 8, wherein the total concentration on one side of the electrolyte ion-blocking layer is greater than 0% and less than about 10% of the total concentration on the other side of the electrolyte ion-blocking layer.

10. The electrolyte ion-blocking layer comprises a porous, hydrophobic polymer layer; 9. The glucose sensing electrode of claim 8, wherein the polymer layer is configured to restrict the mobility of Na + , K + , Ca 2+ , Cl - , PO 4 3- and CO 3 2- through the polymer layer while not restricting the mobility of glucose molecules through the polymer layer.

11. A glucose sensing electrode described in any one of claims 8 to 10, wherein the electrolyte ion-blocking layer includes at least one selected from the group consisting of poly(methyl methacrylate) (PMMA), poly(hydroxyethyl methacrylate) (PHEMA), and poly(methyl methacrylate-co-ethylene glycol dimethacrylate) (PMMA-EG-PMMA).

12. A single body; a first electrode formed on the single body, the first electrode comprising the glucose sensing electrode of claim 5; a second electrode formed on the single body and configured to contact a liquid when the first electrode contacts the liquid; A glucose sensing device comprising:

13. 13. The device of claim 12, wherein the nanoparticles of the nanoporous layer comprise at least one selected from the group consisting of platinum (Pt), gold (Au), palladium (Pd), rhodium (Rh), titanium (Ti), ruthenium (Ru), tin (Sn), nickel (Ni), copper (Cu), indium (In), thallium (Tl), zirconium (Zr), iridium (Ir), and oxides of one or more of these metals.

14. Providing a device according to claim 12 or claim 13; applying a bias voltage between the first electrode and the second electrode while a test fluid contacts both the first electrode and the second electrode, thereby causing oxidation of glucose contained in the test fluid at the glucose sensing electrode; Measuring a current flowing from the first electrode; processing the measured value of the current, with or without additional data, to provide a glucose level corresponding to glucose contained in the test fluid; A method for non-enzymatic glucose sensing comprising:

15. A method for producing a colloid, comprising the steps of: providing a liquid composition comprising a surfactant and metal ions, the surfactant being in a reverse micellar phase defining a plurality of hydrophilic spaces that contain at least a portion of the metal ions; adding a reducing agent to the liquid composition to cause reduction of at least a portion of the metal ions to form nanoparticles, thereby providing a first colloid, wherein at least a portion of the nanoparticles are within at least some of the plurality of hydrophilic spaces, and no electric potential is applied for the reduction of the at least a portion of the metal ions; removing said surfactant from said first colloid such that said surfactant is present in an amount of 0-2 parts by weight per 100 parts by weight of said nanoparticles, thereby providing a second colloid comprising many irregularly shaped clusters of nanoparticles dispersed in a liquid; Including, The method, wherein the irregularly shaped clusters comprise nanoparticles having a generally ovoid or spherical shape with lengths ranging from about 2 nm to about 5 nm.

16. The method of claim 1, wherein some molecules of the surfactant are bound to nanoparticles in the first colloid; 16. The method of claim 15, wherein removing the surfactant further comprises adding an acid or a base to the first colloid to detach at least a portion of the molecules from the nanoparticles.

17. The method of claim 15, further comprising adjusting a concentration of the nanoparticles in the second colloid after removal of the surfactant to provide a colloid composition in which the nanoparticles are present in an amount of about 0.01 wt % to about 2 wt % based on the total weight of the colloid composition.

18. A method for producing a nanoporous layer, comprising the steps of: providing a colloidal composition comprising a number of irregularly shaped clusters of nanoparticles dispersed in a liquid, said irregularly shaped clusters comprising nanoparticles having a generally ovoid or spherical shape with lengths in the range between about 2 nm and about 5 nm; dispensing said colloidal composition onto a substrate; drying the dispensed colloidal composition to form a nanoporous layer; Including, No electrical potential is applied to the liquid composition to form the nanoporous layer; drying the dispensed colloidal composition, such that the irregularly shaped clusters contained in the dispensed colloidal composition are deposited on the substrate, such that adjacent ones of the irregularly shaped clusters contact each other and also contact other ones of the irregularly shaped clusters, thereby forming a three-dimensional interconnected network of irregularly shaped bodies; wherein adjacent ones of the irregularly shaped clusters define irregularly shaped unoccupied spaces that connect to other unoccupied spaces defined by other ones of the irregularly shaped clusters, forming a three-dimensional interconnected network of irregularly shaped spaces; said three-dimensional interconnected network of irregularly shaped bodies comprising many nanoparticles originating from said irregularly shaped clusters in said colloidal composition; A method in which, within the three-dimensional interconnected network of irregularly shaped bodies, adjacent ones of the nanoparticles, where there are no intervening nanoparticles between the adjacent particles, define interparticle nanopores between the adjacent particles.

19. The method of claim 18, wherein the nanoporous layer does not contain organic molecules therein or, if present, contains organic molecules in an amount less than 0.5 parts by weight per 100 parts by weight of the nanoparticles.

20. The method of claim 18 or claim 19, wherein at least a portion of the interparticle nanopores have a size in the range of about 0.5 nm to about 3 nm.

Citation Information

Patent Citations

  • Nano platinum-cobalt / porous gold / graphene composite material and preparation method thereof

    CN106770567A

  • MESOPOROUS PLATINUM ELECTRODE AND METHOD FOR DETECTING BIOCHEMICAL SUBSTRATES USING THE SAME

    JP2006500582A

  • Method for manufacturing porous metal structure

    JP2009068045A

  • Method for producing copper porous body, and coating film layer of copper porous body

    JP2011111652A

  • Molecular sensor with mesoporous metal film, redox catalyst, and lithium ion battery electrode

    JP2016173293A